Active agent-containing articles that exhibit consumer acceptable article in-use properties
Fibrous structures with an edge seal along the outer circumference address issues of structural integrity and solubility, ensuring balanced flexibility and efficient dissolution, meeting consumer expectations for smooth foaming solutions.
Patent Information
- Application Number
- JP2024177968
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2017-01-27
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-23
AI Technical Summary
Existing fibrous structures containing active agents face challenges in achieving consumer-acceptable product use characteristics such as structural integrity, flexibility, solubility, and end seal strength, leading to premature disintegration or separation during handling and use.
The development of fibrous structures with an edge seal positioned along the outer circumference, providing sufficient end seal strength and width, along with balanced flexibility and solubility, to maintain structural integrity during manufacturing, dispensing, and consumer handling.
The solution ensures the fibrous structures maintain structural integrity and flexibility while ensuring efficient dissolution, meeting consumer expectations for smooth and silky foaming solutions, enhancing overall consumer performance.
Smart Images

Figure 2025011226000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to active agent-containing articles, e.g., fibrous structures, and more specifically, fibrous structures comprising one or more, e.g., a plurality of, fibrous elements comprising one or more active agents releasable from at least one of the fibrous elements, e.g., filaments and / or fibers, wherein the article exhibits consumer-acceptable article use characteristics, such as end seal strength, end seal width, flexibility, solubility, and / or article dimensions. [Background technology]
[0002] Articles, such as fibrous structures comprising one or more fibrous elements, such as filaments, comprising one or more active agents releasable from at least one of the filaments, are known in the art. However, formulators of such articles have been unable to achieve consumer-acceptable article use properties. For example, consumers desire that articles, especially those comprising two or more fibrous structure plies, exhibit sufficient structural integrity so that the article does not prematurely disintegrate or separate during manufacturing, during distribution in a package, when dispensed from a package by a consumer, or in the consumer's hands before and / or during use by the consumer. In addition, consumers desire that the article exhibit sufficient flexibility during use, so that the article is not too rigid, but also not too flexible, either alone or in combination with one or more other consumer-acceptable article use properties described herein. Additionally, consumers desire that the article, whether hand dissolution in a personal cleansing article such as shampoo, hair conditioner, body wash and / or hand soap, or machine dissolution in a laundry and / or dishwashing article, exhibit sufficient solubility during use, either alone or in combination with one or more other consumer-acceptable article use properties described herein.
[0003] With respect to structural integrity, one problem with current articles comprising one or more fibrous elements having one or more active agents therein is providing suitable edge seals such that the article resists premature separation of the article during manufacturing, upon application of a coating to the outer surface of one of the article's inner plies, during distribution within a package, upon dispensing from the package by the consumer, or in the consumer's hands prior to and / or during use by the consumer, without adversely affecting flexibility, solubility, and / or other desirable properties. Summary of the Invention [Problem to be solved by the invention]
[0004] Thus, there is a need for articles, e.g., articles comprising one or more fibrous elements, e.g., multi-ply fibrous structures, including a plurality of fibrous elements, such as filaments, that include one or more active agents releasable from at least one of the filaments that exhibit consumer-acceptable article use characteristics. In particular, there is a need for such articles that further include suitable edge seals that exhibit sufficient edge seal strength and edge seal width to enable the article to exhibit consumer-favorable characteristics, such as article flexibility, article dimensions, and overall consumer-favorable performance, such as production of a smooth, silky, lathering solution in the consumer's hand prior to application to a surface, and containment in the consumer's hand prior to / during initial dissolution. [Means for solving the problem]
[0005] The present disclosure meets the above needs by providing articles having one or more fiber elements including one or more active agents releasable from at least one of the fiber elements, the articles exhibiting consumer acceptable article use characteristics, such as one or more dimensional requirements. Specifically, the present disclosure meets the above needs by providing such articles further including an edge generally positioned along at least a portion of the article's circumference, the articles exhibiting sufficient edge strength and edge seal width, and the articles exhibiting consumer-friendly and acceptable use characteristics, such as article dimensions, flexibility, and solubility, as described herein.
[0006] In one embodiment of the present disclosure, an article is provided having one or more fiber elements, at least one of the fiber elements comprising one or more filament forming materials and one or more active agents releasable from the fiber element, an end seal is positioned generally along at least a portion of a circumference of the article, and the article exhibits an end seal strength of about 0.1 N / in to about 4 N / in when measured according to the End Seal Strength Test Method.
[0007] In another embodiment of the present disclosure, there is provided an article having one or more fibrous elements, at least one of which comprises one or more filament forming materials and one or more active agents releasable from the fibrous element, an end seal generally positioned along at least a portion of a circumference of the article, and the end seal has an end seal width of about 0.5 mm to about 4 mm as measured according to the End Seal Strength Test Method.
[0008] In yet another embodiment of the present disclosure, there is provided an article having one or more fibrous elements, at least one of which comprises one or more filament forming materials and one or more active agents releasable from the fibrous elements, an end seal generally positioned along at least a portion of a circumference of the article, the end seal having an end seal width of from about 0.5 mm to about 4 mm as measured according to the End Seal Strength Test Method, and the article exhibiting an end seal strength of from about 0.1 N / in to about 4 N / in as measured according to the End Seal Strength Test Method. [Brief description of the drawings]
[0009] [Figure 1] 1 is a schematic diagram of an embodiment of a fiber element (in this case a filament) according to the present disclosure. [Diagram 2] FIG. 1 is a schematic diagram of an example of a fibrous structure including a plurality of filaments according to the present disclosure. [Diagram 3] 3 is another schematic diagram of the article of FIG. 2, showing article dimensions. [Figure 4]1 is a scanning electron micrograph of a cross-section of an embodiment of a fibrous structure according to the present disclosure. [Diagram 5] FIG. 2 is a schematic diagram of a cross-sectional view of another embodiment of a fibrous structure according to the present disclosure. [Figure 6] FIG. 2 is a schematic diagram of a cross-sectional view of another embodiment of a fibrous structure according to the present disclosure. [Figure 7] 1 is a scanning electron micrograph of a cross-sectional view of another embodiment of a fibrous structure according to the present disclosure. [Figure 8] FIG. 2 is a schematic diagram of a cross-sectional view of another embodiment of a fibrous structure according to the present disclosure. [Figure 9] FIG. 2 is a schematic diagram of a cross-sectional view of another embodiment of a fibrous structure according to the present disclosure. [Figure 10] FIG. 2 is a schematic diagram of a cross-sectional view of another embodiment of a fibrous structure according to the present disclosure. [Figure 11] FIG. 2 is a schematic diagram of a cross-sectional view of another embodiment of a fibrous structure according to the present disclosure. [Figure 12] FIG. 1 is a schematic diagram of an article having an end seal. [Figure 13] FIG. 13 is a schematic diagram of a cross-sectional view of the article of FIG. [Figure 14] 1 is a schematic diagram of an embodiment of a manufacturing process for an embodiment of a fibrous structure according to the present disclosure. [Figure 15] FIG. 15 is a schematic diagram of one embodiment of a die, including an enlarged view, used in the process of FIG. 14. [Figure 16] 2 is a schematic diagram of an embodiment of another manufacturing process for an embodiment of a fibrous structure according to the present disclosure. [Figure 17] 2 is a schematic diagram of another embodiment of a manufacturing process for another embodiment of a fibrous structure according to the present disclosure. [Figure 18] 2 is a schematic diagram of another embodiment of a manufacturing process for another embodiment of a fibrous structure according to the present disclosure. [Figure 19] 1 is a representative image of one embodiment of a patterned belt useful in the manufacturing process of a fibrous structure according to the present disclosure. [Figure 20] FIG. 2 is a schematic diagram of a rule die cutter. [Figure 21A]FIG. 2 is a schematic diagram of a top view of a tool useful in forming the article. [Figure 21B] FIG. 21B is a schematic diagram of a cross-sectional view of FIG. 21A taken along line AA. [Figure 21C] FIG. 21C is a schematic diagram of a cross-sectional view of the tool tip shown in FIG. 21B. [Figure 22] FIG. 1 is a schematic diagram of a heated mechanical press useful in the process of forming an article. [Diagram 23] FIG. 1 is a schematic diagram of one example of an instrumental configuration used in measuring solubility according to the present disclosure. [Figure 24] FIG. 19 is a schematic diagram of FIG. 18 during dissolution testing. [Diagram 25] FIG. 20 is a schematic diagram of the plan view of FIG. 19. [Figure 26A] 1 is a schematic diagram of one embodiment of an apparatus configuration used in measuring modified circular bend properties of a fibrous structure according to a modified circular bend test method. [Figure 26B] FIG. 26B is a schematic diagram of a plan view of a portion of FIG. 26A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Definition of Terms As used herein, "fibrous structure" refers to a structure comprising one or more fibrous elements and, optionally, one or more particles. In one embodiment, a fibrous structure according to the present disclosure refers to an association of fibrous elements and, optionally, particles, that together form a structure, such as a unitary structure, capable of performing a function.
[0011] The fibrous structures of the present disclosure may be homogeneous or layered. If layered, the fibrous structure may include at least two and / or at least three and / or at least four and / or at least five, e.g., one or more fiber element layers, one or more particle layers, and / or one or more fiber element / particle mixed layers. A layer may include a particle layer within the fibrous structure or between fiber element layers within the fibrous structure. A layer including fiber elements may be referred to as a ply. A ply may be a fibrous structure, which may be homogeneous or layered, as described herein.
[0012] In one embodiment, a single-ply fibrous structure according to the present disclosure or a multi-ply fibrous structure including one or more fibrous structure plies according to the present disclosure has a basis weight of 5000 g / m2 or more when measured according to the basis weight test method described herein. 2 In one embodiment, a single-ply or multi-ply fibrous structure according to the present disclosure may exhibit a basis weight of less than 10 g / m2 when measured according to the Basis Weight Test Method. 2 Super~approx. 5000g / m 2 , and / or 10 g / m 2 Super ~ about 3000g / m 2 , and / or 10 g / m 2 Super ~ about 2000g / m 2 , and / or 10 g / m 2 Super ~ about 1000g / m 2 and / or 20 g / m 2 ~about 800g / m 2 , and / or 30 g / m 2 ~about 600g / m 2 , and / or 50 g / m 2 Super~approx. 500g / m 2 and / or 300 g / m 2 Super ~ about 3000g / m 2 , and / or 500 g / m 2 Super ~ about 2000g / m 2 It may exhibit a basis weight of greater than 100 g.
[0013] In one embodiment, the fibrous structure of the present disclosure is a "monolithic fibrous structure."
[0014] As used herein, a "unitary fibrous structure" is an arrangement comprising two or more and / or three or more multiple fibrous elements that are intertwined or otherwise bonded to each other to form a fibrous structure and / or fibrous structure ply. The unitary fibrous structures of the present disclosure may be one or more plies within a multi-ply fibrous structure. In one embodiment, the unitary fibrous structures of the present disclosure may comprise three or more different fibrous elements. In another embodiment, the unitary fibrous structures of the present disclosure may comprise two or more different fibrous elements.
[0015] As used herein, "article" refers to a consumer unit, a consumer unitary dose unit, a consumer salable unit, a single dose unit, or other form of use that includes an integral fibrous structure and / or includes one or more fibrous structures of the present disclosure.
[0016] As used herein, "fiber element" means an elongated particle whose length is significantly greater than its average diameter, i.e., the ratio of length to average diameter is at least about 10. A fiber element can be a filament or a fiber. In one example, the fiber element is a single fiber element, rather than a yarn that includes multiple fiber elements.
[0017] The fiber elements of the present disclosure may be spun from a filament-forming composition, also referred to as a fiber element-forming composition, by a suitable spinning process operation (e.g., meltblowing, spunbonding, electrospinning, and / or rotary spinning, etc.).
[0018] The fiber elements of the present disclosure may be monocomponent (a single integral solid piece rather than two distinct parts such as a core / sheath bicomponent) and / or multicomponent. For example, the fiber elements may comprise bicomponent fibers and / or filaments. The bicomponent fibers and / or filaments may be in any form, such as side-by-side, sheath-core, islands-in-the-sea, etc.
[0019] As used herein, "filament" means an elongated particulate as defined above having a length of 2 inches or more, and / or 3 inches or more, and / or 4 inches or more, and / or 6 inches or more.
[0020] Filaments are typically considered to be essentially continuous or substantially continuous. Filaments are relatively longer than fibers. Non-limiting examples of filaments include meltblown filaments and / or spunbond filaments. Non-limiting examples of polymers that can be spun into filaments include natural polymers such as starch, starch derivatives, cellulose (e.g., rayon and / or lyocell), cellulose derivatives, hemicellulose, and hemicellulose derivatives, as well as synthetic polymers including, but not limited to, polyvinyl alcohol, thermoplastic polymer filaments such as polyester, nylon, polyolefins (e.g., polypropylene filaments, and polyethylene filaments), and biodegradable thermoplastic fibers such as polylactic acid filaments, polyhydroxyalkanoate filaments, polyesteramide filaments, and polycaprolactone filaments.
[0021] As used herein, "fiber" means an elongated particle as defined above exhibiting a length of less than 2 inches and / or less than 1.5 inches and / or less than 1 inch.
[0022] Typically, the fibers are considered to be discontinuous in nature. Non-limiting examples of fibers include staple fibers produced by spinning a filament or filament tow of the present disclosure and then chopping the filament or filament tow into pieces less than 2 inches.
[0023] In one embodiment, one or more fibers may be formed from the filaments of the present disclosure, such as when the filaments are cut into shorter lengths (e.g., lengths less than 5.08 cm). Thus, in one embodiment, the present disclosure also includes fibers made from the filaments of the present disclosure, such as fibers that include one or more filament-forming materials and one or more additives (e.g., activators). Thus, references to filaments of the present disclosure herein also include fibers made from such filaments, unless otherwise specified. Fibers are typically considered to be essentially discontinuous, as opposed to filaments, which are considered to be essentially continuous.
[0024] As used herein, "filament-forming composition" and / or "fiber element-forming composition" refer to a composition suitable for producing fiber elements of the present disclosure, such as by meltblowing and / or spunbonding. The filament-forming composition includes one or more filament-forming materials, which materials exhibit properties that make them suitable for spinning into fiber elements. In one embodiment, the filament-forming material includes a polymer. In addition to the one or more filament-forming materials, the filament-forming composition may include one or more additives (e.g., one or more active agents). Furthermore, the filament-forming composition may include one or more polar solvents (e.g., water) in which one or more (e.g., all) of the filament-forming materials and / or one or more (e.g., all) of the active agents may be dissolved and / or dispersed prior to spinning the fiber elements (e.g., filaments derived from the filament-forming composition).
[0025] In one embodiment as shown in Figure 1, fiber elements, such as filaments 10 of the present disclosure produced from a fiber element forming composition of the present disclosure, may have one or more additives 12, such as one or more active agents, such as a coating composition including one or more active agents that may be the same as or different from the active agents in the fiber element and / or particle, present within the filament rather than on the filament. The total concentration of fiber element forming materials, and the total concentration of active agents present in the fiber element forming composition, may be any suitable amount, so long as a fiber element of the present disclosure can be produced therefrom.
[0026] In one example, one or more additives, e.g., active agents, may be present in the fiber element and one or more additional additives, e.g., active agents, may be present on the surface of the fiber element. In another example, the fiber elements of the present disclosure may include one or more additives, e.g., active agents, that are originally present in the fiber element upon manufacture but bloom to the surface of the fiber element before and / or upon exposure to the intended use conditions of the fiber element.
[0027] As used herein, "filament-forming material" and / or "fiber element-forming material" refer to materials such as polymers or monomers from which polymers can be made that exhibit suitable properties for making fiber elements. In one embodiment, the filament-forming material includes one or more substituted polymers, such as anionic, cationic, zwitterionic, and / or nonionic polymers. In other embodiments, the polymer may include hydroxyl polymers, such as polyvinyl alcohol ("PVOH"), partially hydrolyzed polyvinyl acetate, and / or polysaccharides (e.g., starch), and / or starch derivatives (e.g., ethoxylated starch), and / or acid-diluted starch, carboxymethyl cellulose, hydroxypropyl cellulose, hydroxyethyl cellulose. In another embodiment, the polymer may include polyethylene and / or terephthalate. In yet another embodiment, the filament-forming material is a polar solvent-soluble material.
[0028] As used herein, "particles" refers to solid additives such as powders, granules, capsules, microcapsules, and / or prills. In one embodiment, the particles exhibit a median particle size of 2000 μm or less when measured according to the Median Particle Size Test Method described herein. In another embodiment, the particles exhibit a median particle size of about 1 μm to about 2000 μm, and / or about 1 μm to about 1600 μm, and / or about 1 μm to about 800 μm, and / or about 5 μm to about 500 μm, and / or about 10 μm to about 300 μm, and / or about 10 μm to about 100 μm, and / or about 10 μm to about 50 μm, and / or about 10 μm to about 30 μm when measured according to the Median Particle Size Test Method described herein. The shape of the particles may be spherical, rod-shaped, dish-shaped, tubular, square, rectangular, disk-shaped, star-shaped, fibrous, or may have a regular or irregular random shape.
[0029] "Active agent-containing particles," as used herein, refer to solid additives that contain one or more active agents. In one example, the active agent-containing particles are active agents in the form of particles (in other words, the particles contain 100% active agent). The active agent-containing particles may exhibit a median particle size of 2000 μm or less, when measured according to the Median Particle Size Test Method described herein. In another example, the active agent-containing particles exhibit a median particle size of about 1 μm to about 2000 μm, and / or about 1 μm to about 800 μm, and / or about 5 μm to about 500 μm, and / or about 10 μm to about 300 μm, and / or about 10 μm to about 100 μm, and / or about 10 μm to about 50 μm, and / or about 10 μm to about 30 μm, when measured according to the Median Particle Size Test Method described herein. In one example, the one or more active agents are in the form of particles exhibiting a median particle size of 20 μm or less, as measured according to the Median Particle Size Test Method described herein.
[0030] In one embodiment of the present disclosure, the fibrous structure comprises a plurality of particles, e.g., active agent-containing particles, and a plurality of fibrous elements in a ratio of 1:100 or more, and / or 1:50 or more, and / or 1:10 or more, and / or 1:3 or more, and / or 1:2 or more, and / or 1:1 or more, and / or 2:1 or more, and / or 3:1 or more, and / or 4:1 or more, and / or 5:1 or more, and / or 7:1 or more, and / or In some embodiments, the weight ratio of particles, e.g., active agent-containing particles to fiber elements is 8:1 or greater, and / or 10:1 or greater, and / or from about 10:1 to about 1:100, and / or from about 8:1 to about 1:50, and / or from about 7:1 to about 1:10, and / or from about 7:1 to about 1:3, and / or from about 6:1 to 1:2, and / or from about 5:1 to about 1:1, and / or from about 4:1 to about 1:1, and / or from about 3:1 to about 1.5:1.
[0031] In another embodiment of the present disclosure, the fibrous structure comprises a plurality of particles, e.g., active agent-containing particles, and a plurality of fibrous elements, in a weight ratio of particles, e.g., active agent-containing particles to fibrous elements, of about 10:1 to about 1:1, and / or about 8:1 to about 1.5:1, and / or about 7:1 to about 2:1, and / or about 6:1 to about 2.5:1.
[0032] In yet another embodiment of the present disclosure, the fibrous structure comprises a plurality of particles, e.g., active agent-containing particles, and a plurality of fibrous elements, in a weight ratio of particles, e.g., active agent-containing particles to fibrous elements, of about 1:1 to about 1:100, and / or about 1:15 to about 1:80, and / or about 1:2 to about 1:60, and / or about 1:3 to about 1:50, and / or about 1:3 to about 1:40.
[0033] In another embodiment, the fibrous structure of the present disclosure has a basis weight of less than 1 g / m2 when measured according to the basis weight test method described herein. 2 and / or 10 g / m 2 and / or 20 g / m 2 and / or 30 g / m 2 and / or 40 g / m 2 More than and / or about 1 g / m 2 to about 5000g / m 2 and / or about 3500 g / m 2and / or about 2000 g / m 2 and / or about 1 g / m 2 ~About 2000g / m 2 , and / or about 10 g / m 2 ~About 1000g / m 2 , and / or about 10 g / m 2 ~about 500g / m 2 , and / or about 20 g / m 2 ~about 400g / m 2 , and / or about 30 g / m 2 ~about 300g / m 2 , and / or about 40 g / m 2 ~about 200g / m 2 In one embodiment, the fibrous structure includes two or more layers of particles, e.g., active agent-containing particles, with a basis weight of about 1 g / m. In another embodiment, the fibrous structure includes two or more layers of particles, e.g., active agent-containing particles, with each layer of particles having a basis weight of about 1 g / m. 2 ~about 500g / m 2 In one embodiment, the plurality of particles is present in the article within two or more plies in a multi-ply article. In one embodiment, the plurality of particles is present in the article between two or more plies in a multi-ply article. In another embodiment, the plurality of particles is present in the article as a particle layer in the article between two or more plies in a multi-ply article.
[0034] In another embodiment, the fibrous structure of the present disclosure has a basis weight of less than 1 g / m2 when measured according to the basis weight test method described herein. 2 and / or 10 g / m 2 and / or 20 g / m 2 and / or 30 g / m 2 and / or 40 g / m 2 More than and / or about 1 g / m 2 to about 5000g / m 2 and / or about 1 g / m 2 to about 3000g / m 2 and / or about 10 g / m 2 to about 5000g / m 2 and / or about 3000 g / m 2 and / or about 2000 g / m 2 and / or about 20 g / m 2~About 2000g / m 2 up to and / or about 30 g / m 2 ~About 1000g / m 2 , and / or about 30 g / m 2 ~about 500g / m 2 , and / or about 30 g / m 2 ~about 300g / m 2 , and / or about 40 g / m 2 ~about 100g / m 2 , and / or about 40 g / m 2 ~about 80g / m 2 In one example, the fibrous structure comprises a plurality of fibrous elements having a basis weight of about 1 g / m 2 ~about 500g / m 2 In one embodiment, the plurality of fibrous elements are present in the article in two or more plies within a multi-ply article.
[0035] As used herein, "additive" refers to any material present in a fiber element of the present disclosure that is not a filament-forming material. In one example, the additive includes an active agent. In another example, the additive includes a processing aid. In yet another example, the additive includes a filler. In one example, the additive includes any material present in a fiber element whose absence would not impair the fiber element structure of the fiber element (in other words, the absence of the material would not impair the solid form of the fiber element). In another example, the additive, e.g., an active agent, includes a non-polymeric material.
[0036] In other examples, the additive may include a plasticizer for the fiber element. Non-limiting examples of plasticizers suitable for the present disclosure include polyols, copolyols, polycarboxylic acids, polyesters, and dimethicone copolyols. Examples of useful polyols include, but are not limited to, glycerin, diglycerin, propylene glycol, ethylene glycol, butylene glycol, pentylene glycol, cyclohexanedimethanol, hexanediol, 2,2,4-trimethylpentane-1,3-diol, polyethylene glycol (200-600), pentaerythritol, sugar alcohols such as sorbitol, mannitol, lactitol, and other monohydric and polyhydric low molecular weight alcohols (e.g., C2-C8 alcohols); monosaccharides, disaccharides, and oligosaccharides such as fructose, glucose, sucrose, maltose, lactose, high fructose corn syrup solids, and dextrins, and ascorbic acid.
[0037] In one example, the plasticizer includes glycerin, and / or propylene glycol, and / or glycerol derivatives such as propoxylated glycerol, hi yet another example, the plasticizer is selected from the group consisting of glycerin, ethylene glycol, polyethylene glycol, propylene glycol, glycidol, urea, sorbitol, xylitol, maltitol, sugars, ethylene bisformamide, amino acids, and mixtures thereof.
[0038] In other examples, the additives may include rheology modifiers, such as shear modifiers and / or extension modifiers. Non-limiting examples of rheology modifiers include, but are not limited to, polyacrylamides, polyurethanes, and polyacrylates that may be used in the fiber elements of the present disclosure. Non-limiting examples of rheology modifiers are commercially available from Dow Chemical Company (Midland, MI).
[0039] In yet another embodiment, the additive may include one or more colors and / or dyes that are incorporated into the fiber elements of the present disclosure to provide a visual signal when the fiber elements are exposed to intended use conditions and / or when an active agent is released from the fiber elements and / or when the morphology of the fiber elements changes.
[0040] In yet another embodiment, the additive may include one or more release agents and / or lubricants. Non-limiting examples of suitable release agents and / or lubricants include fatty acids, fatty acid salts, fatty alcohols, fatty esters, sulfonated fatty acid esters, fatty amine acetates, fatty amides, silicones, amino silicones, fluoropolymers, and mixtures thereof. In one embodiment, the release agents and / or lubricants may be applied to the fibrous elements, in other words, after the fibrous elements are formed. In one embodiment, one or more release agents / lubricants may be applied to the fibrous elements before collecting the fibrous elements in a collecting device to form a fibrous structure. In another embodiment, one or more release agents / lubricants may be applied to a fibrous structure formed from the fibrous elements of the present disclosure before contacting one or more fibrous structures, such as a stack of fibrous structures. In yet another example, one or more release agents / lubricants may be applied to the fibrous elements and / or fibrous structures of the present disclosure before the fibrous elements and / or fibrous structures contact a surface (e.g., a surface of an apparatus used in a processing system) to facilitate release of the fibrous elements and / or fibrous structures and / or to prevent plies of the fibrous elements and / or fibrous structures of the present disclosure from sticking, even unintentionally, to one another. In one example, the release agent / lubricant comprises a particulate.
[0041] In yet other embodiments, the additive may include one or more antiblocking and / or detackifying agents. Non-limiting examples of suitable antiblocking and / or detackifying agents include starch, starch derivatives, crosslinked polyvinylpyrrolidone, crosslinked cellulose, microcrystalline cellulose, silica, metal oxides, calcium carbonate, talc, mica, and mixtures thereof.
[0042] As used herein, "intended use conditions" refers to the temperature, physical, chemical, and / or mechanical conditions to which the fiber elements, particles, and / or fiber structures of the present disclosure are exposed when used for one or more of their designed applications. For example, if the fiber elements, particles, and / or fiber structures comprising the fiber elements are designed to be used in a washing machine for laundry care purposes, the intended use conditions include the temperature, chemical, physical, and / or mechanical conditions present in the washing machine, including any wash water, during a laundry washing operation. In another example, if the fiber elements, particles, and / or fiber structures comprising the fiber elements are designed to be used by humans as a shampoo for hair care purposes, the intended use conditions include the temperature, chemical, physical, and / or mechanical conditions present in a shampoo of human hair. Similarly, when the fibrous structure comprising fibrous elements, and / or particles, and / or fibrous elements is designed to be used in a dishwashing operation, either by hand or in a dishwasher, the intended conditions of use include the temperature, chemical, physical, and / or mechanical conditions present in the dishwashing water and / or in the dishwasher during the dishwashing operation.
[0043] As used herein, "active agent" refers to an additive that produces an intended effect in the environment outside the fiber elements, and / or particles, and / or fiber structures comprising the fiber elements of the present disclosure, e.g., when the fiber elements, and / or particles, and / or fiber structures are exposed to the intended conditions of use of the fiber elements, and / or particles, and / or fiber structures comprising the fiber elements. In one example, the active agent includes additives that treat surfaces, e.g., hard surfaces (i.e., kitchen counters, bathtubs, toilets, urinals, sinks, floors, walls, teeth, cars, windows, mirrors, dishes) and / or soft surfaces (i.e., fabrics, hair, skin, carpets, crops, plants). In another example, the active agent includes additives that produce a chemical reaction (i.e., foaming, effervescing, coloring, warming, cooling, foaming, disinfecting, and / or purifying, and / or chlorinating, e.g., water purification, and / or water disinfection, and / or water chlorination). In yet another example, the active agent includes additives that treat the environment (i.e., deodorize, purify, fragrance the air). In one example, the active agent is formed in situ, such as during the formation of the fiber elements and / or particles that contain the active agent, for example, the fiber elements and / or particles may include a water-soluble polymer (e.g., starch) and a surfactant (e.g., an anionic surfactant). The water-soluble polymer and surfactant can create a polymer complex, or coacervate, that functions as the active agent used to treat the surface of the fabric.
[0044] "Treating" as used herein with respect to the treatment of a surface means that the active agent provides a benefit to the surface or environment. Treatment includes regulating and / or rapidly improving the appearance, cleanliness, odor, purity, and / or feel of the surface or environment. In one example, treatment with respect to the treatment of a keratinous tissue (e.g., skin and / or hair) surface means regulating and / or rapidly improving the cosmetic appearance and / or feel of the keratinous tissue. For example, "regulating the condition of the skin, hair, or nails (keratinous tissue)" includes thickening of the skin, hair, or nails (e.g., building up of the epidermal and / or dermal and / or subcutaneous (e.g., subcutaneous fat or muscle) layers of the skin, and building up of the stratum corneum of the nails and hair shafts, if applicable), to reduce atrophy of the skin, hair, or nails, increasing the convolution of the dermal-epidermal boundary (also known as the interpapillary ridge), elastosis, sagging, deformation of the skin or hair, etc. Examples of treatments include preventing loss of elasticity of the skin or hair (loss, damage, and / or inactivation of functional skin elastin), such as loss of recovery from rosacea, preventing melanotic or non-melanotic changes in skin, hair, or nail color, such as dark circles under the eyes, age spots (e.g., uneven redness due to rosacea, etc.) (hereinafter referred to as "erythema"), paleness (paleness), discoloration caused by telangiectasias or spider veins, and gray hair. Treatments may include providing benefits to fabrics during washing or softening in a washing machine, providing benefits to hair during shampooing, conditioning, or coloring of hair, or providing benefits to the environment, such as a toilet bowl, by cleaning or disinfecting.
[0045] In another example, treating refers to removing stains and / or odors from fabric articles (e.g., clothing, towels, linens) and / or hard surfaces (e.g., counters and / or tableware such as pots and pans).
[0046] As used herein, "fabric care active" means an active that, when applied to a fabric, provides a benefit and / or improvement to the fabric. Non-limiting examples of benefits and / or improvements to fabrics include cleaning (e.g., by surfactants), stain removal, stain reduction, wrinkle removal, color recovery, static control, wrinkle resistance, permanent press, abrasion reduction, abrasion resistance, pill removal, pill resistance, stain removal, stain resistance (including stain release), shape retention, shrink reduction, softness, fragrance, antibacterial, antiviral, anti-odor, and odor elimination.
[0047] As used herein, "dishwashing active" means an active that, when applied to tableware, glassware, pots, pans, kitchen utensils, and / or cooksheets, provides a benefit and / or improvement to the tableware, glassware, plastic articles, pots, pans, and / or cooksheets. Non-limiting examples of benefits and / or improvements to tableware, glassware, plastic articles, pots, pans, kitchen utensils, and / or cooksheets include food and / or soil removal, cleaning (e.g., surfactant) stain removal, stain reduction, grease removal, water stain removal and / or water stain prevention, glass and metal care, sanitizing, shine, and polishing.
[0048] As used herein, "hard surface active" means an active that, when applied to floors, counters, sinks, windows, mirrors, showers, baths, and / or toilets, provides a benefit and / or improvement to the floors, counters, sinks, windows, mirrors, showers, baths, and / or toilets. Non-limiting examples of benefits and / or improvements to floors, counters, sinks, windows, mirrors, showers, baths, and / or toilets include food and / or soil removal, cleaning (e.g., with surfactants), stain removal, stain reduction, grease removal, water stain removal and / or water stain prevention, soap scum removal, sanitizing, brightening, polishing, and freshening.
[0049] As used herein, "keratinous tissue active agent" means an active agent that may be useful in treating a keratinous tissue (e.g., hair, skin, or nail) condition. In the case of hair care active agents, "treating" or "treatment" or "treat" includes regulating and / or immediately improving the cosmetic appearance and / or feel of keratinous tissue. For example, "regulating the condition of the skin, hair, or nails" includes thickening the skin, hair, or nails to reduce atrophy of the skin, hair, or nails (e.g., building up the epidermal and / or dermal and / or sub-dermal [e.g., subcutaneous fat or muscle] layers of the skin and, where applicable, building up the keratinous layers of the nails and hair shafts); increasing the convolution of the dermal-epidermal border (also known as interpapillary ridges); preventing loss of recoil of the skin or hair due to elastosis, sagging, deformation, all together with loss of elasticity of the skin or hair (loss, damage, and / or inactivation of functional skin elastin); melanin or non-melanin changes in skin, hair, or nail pigmentation such as bags under the eyes, mottling (e.g., uneven red coloring due to rosacea, etc.) (hereinafter referred to as "red mottling"), sallowness (pale color), telangiectasias or spider veins, and discoloration caused by gray hair. Another example of a keratinous tissue active agent may be an active agent used in shampooing, conditioning, or dyeing hair.
[0050] As used herein, "weight ratio" refers to the ratio between two materials on a dry basis. For example, the weight ratio of the filament-forming material to the active agent in a fiber element is the ratio of the weight (g or %) of the filament-forming material on a dry weight basis in the fiber element to the weight (g or % - the same units as the weight of the filament-forming material) of the additive (e.g., active agent) on a dry weight basis in the fiber element. In another embodiment, the weight ratio of the particle to the fiber element in a fiber structure is the ratio of the weight (g or %) of the particle on a dry weight basis in the fiber structure to the weight (g or % - the same units as the weight of the particle) of the fiber element on a dry weight basis in the fiber wall material.
[0051] As used herein, "water-soluble material" refers to a material that is miscible in water, in other words, capable of forming a stable homogeneous solution (that does not separate for more than 5 minutes after forming the homogeneous liquid) with water at ambient conditions.
[0052] As used herein, "ambient conditions" means approximately 23°C ± 1.0°C and a relative humidity of 50% ± 2%.
[0053] As used herein, "weight average molecular weight" means the weight average molecular weight determined using gel permeation chromatography according to the protocol found in Colloids and Surfaces A. Physico Chemical & Engineering Aspects, Vol. 162, 2000, p. 107-121.
[0054] As used herein, "article dimension" refers to the length, width, height, mass, volume, density, etc. of an article.
[0055] As used herein with respect to fiber elements, "length" means the length along the longest axis of the fiber element from one end to the other end. If the fiber element has internal twists, curls, or bends, the length will be the length along the entire path of the fiber element from one end to the other end. With respect to the dimensions of an article, "length" may be defined differently. For example, with respect to an irregularly shaped article, the length refers to the maximum Feret or caliper diameter, which is the longest distance between two parallel planes that border the article. For example, with respect to a linearly shaped article, the length refers to the distance from one edge to the opposite edge. In one embodiment, the average length may be provided by measuring ten substantially similar replicate articles, tabulating the average of the length measurements of the ten individual articles, and reporting the value to the nearest 0.01 cm, and the length measurements of the individual articles may be measured by any suitable instrument that is calibrated, NIST traceable, and capable of measuring to the nearest 0.01 cm.
[0056] As used herein with respect to fiber elements, "diameter" is measured according to the diameter test method described herein. In one embodiment, fiber elements of the present disclosure exhibit a diameter of less than 100 μm, and / or less than 75 μm, and / or less than 50 μm, and / or less than 25 μm, and / or less than 20 μm, and / or less than 15 μm, and / or less than 10 μm, and / or less than 6 μm, and / or greater than 1 μm, and / or greater than 3 μm.
[0057] As used herein with respect to article dimensions, "width" may refer to measurements according to its conventional definition. For example, for linear shaped articles, width refers to the distance from one edge to the opposite edge. However, for irregular shaped articles, width refers to the maximum Feret or caliper diameter, which is the longest distance between two parallel planes that border the article. In one embodiment, an average width may be provided by measuring 10 substantially similar replicate articles, tabulating the average of the width measurements of the 10 individual articles, and reporting the value to the nearest 0.01 cm, and the width measurements of the individual articles may be measured by any suitable instrument that is calibrated, NIST traceable, and capable of measuring to the nearest 0.01 cm.
[0058] As used herein with respect to article dimensions, "height" may refer to a measurement according to its conventional definition. The height or thickness of an article may be measured, for example, by the thickness test method described herein.
[0059] As used herein with respect to article dimensions, "volume" may refer to a measurement according to its conventional definition. For example, the volume of an article may be calculated by measuring the projected area of the article, viewed perpendicular to the plane of the length and width of the article, and multiplying this area by the height of the article. In one example, an average volume may be provided by measuring ten substantially similar replicate articles, tabulating the average of the volume measurements of the ten individual articles, and reporting the value to the nearest 0.01 cc.
[0060] As used herein with respect to an article, "mass" may refer to a measurement according to its conventional definition. For example, the mass of an article may be measured using a top-pan analytical balance with a resolution of ±0.01 g, with the balance protected from air currents and other disturbances by a windshield. After conditioning the article, the mass of the article may be measured to the nearest 0.01 g. In one example, the average mass may be provided by measuring 10 substantially similar replicate articles, tabulating the average of the measurements of the mass of the 10 individual articles, and reporting the value to the nearest 0.01 g.
[0061] As used herein with respect to an article, "density" may refer to a measurement according to its conventional definition, and thus density may be calculated by dividing the mass of an article by its volume. In one example, density may be reported to the nearest 0.01 g / cc.
[0062] As used herein, "triggering conditions" refers, in one embodiment, to anything as an action or event that acts as a stimulus and initiates or causes a change in the fiber elements and / or particles and / or fiber structures of the present disclosure (e.g., loss or change in the physical structure of the fiber elements and / or fiber structures and / or release of additives such as active agents). In another embodiment, the triggering conditions may be present in an environment (such as water) when the fiber elements and / or particles and / or fiber structures of the present disclosure are added to the water. In other words, no change occurs in the water apart from the fact that the fiber elements and / or fiber structures of the present disclosure have been added to the water.
[0063] As used herein with respect to morphological changes of fiber elements and / or particles, "morphological change" means that the fiber elements undergo a change in their physical structure. Non-limiting examples of morphological changes of fiber elements and / or particles of the present disclosure include dissolving, melting, expanding, contracting, shattering, bursting, lengthening, shortening, and combinations thereof. The fiber elements and / or particles of the present disclosure may completely or substantially lose their physical structure, may change in morphology, or may retain or substantially retain their physical structure when exposed to intended use conditions.
[0064] "Weight on a dry fibrous element basis" and / or "weight on a dry particle basis" and / or "weight on a dry fibrous structure basis" refer to the weight of the fibrous element, particle, and / or fibrous structure, respectively, measured immediately after the fibrous element, particle, and / or fibrous structure, respectively, has been conditioned for 2 hours in a conditioned room at a temperature of 23° C.±1.0° C. and a relative humidity of 50%±10%. In one embodiment, weight on a dry fibrous element basis and / or weight on a dry particle basis and / or weight on a dry fibrous structure means that the fibrous element, particle, and / or fibrous structure contains less than 20% by weight, and / or less than 15% by weight, and / or less than 10% by weight, and / or less than 7% by weight, and / or less than 5% by weight, and / or less than 3% by weight, and / or 0% by weight, and / or more than 0% by weight moisture (e.g., water (e.g., free water)) when measured according to the Moisture Content Test Method described herein, based on the dry weight of the fibrous element, particle, and / or fibrous structure.
[0065] As used herein, for example, with respect to the total concentration of one or more active agents present in a fiber element, and / or particle, and / or fiber structure, "total concentration" means the sum of all weights or weight percents of the test materials (e.g., active agents). In other words, the fiber elements and / or particles and / or fiber structure may comprise 25% by weight of anionic surfactant based on the dry fiber elements and / or on the dry particles and / or on the dry fiber structure, 15% by weight of nonionic surfactant based on the dry fiber elements and / or on the dry particles and / or on the dry fiber structure, 10% by weight of a chelate based on the dry fiber elements and / or on the dry particles and / or on the dry fiber structure, and 5% by weight of fragrance based on the dry fiber elements and / or on the dry particles and / or on the dry fiber structure, so that the total concentration of active agents present in the fiber elements and / or particles and / or fiber structure is more than 50% by weight, i.e. 55% by weight, based on the dry fiber elements and / or on the dry particles and / or on the dry fiber structure.
[0066] As used herein, "textile structure product" refers to a solid form (e.g., a rectangular solid, sometimes referred to as a sheet) that includes one or more active agents (e.g., fabric care actives, dishwashing actives, hard surface actives, and combinations thereof). In one embodiment, the textile structure product of the present disclosure includes one or more surfactants, one or more enzymes (such as in the form of pellet enzymes), one or more fragrances, and / or one or more suds suppressors. In another embodiment, the textile structure product of the present disclosure includes builders and / or chelating agents. In another embodiment, the textile structure product of the present disclosure includes bleach (such as encapsulated bleach).
[0067] As used herein, "different morphology" or "different" means with respect to a material (such as the entire fiber element, and / or the filament-forming material within the fiber element, and / or the active agent within the fiber element), that one material (such as the fiber element, and / or the filament-forming material, and / or the active agent) is chemically, physically, and / or structurally different from another material (such as the fiber element, and / or the filament-forming material, and / or the active agent). For example, a filament-forming material in filament form is different from the same filament-forming material in fiber form. Similarly, a starch polymer is different from a cellulose polymer. However, the same material with different molecular weights, such as starches with different molecular weights, are not different materials from each other for purposes of this disclosure.
[0068] As used herein, a "random mixture of polymers" means two or more different filament-forming materials that are randomly combined to form fiber elements. As a result, two or more different filament-forming materials that are ordered and combined to form fiber elements, such as sheath-core bicomponent fiber elements, are not random mixtures of different filament-forming materials for purposes of this disclosure.
[0069] As used herein with respect to fibrous elements and / or particles, "associate", "associated", "association" and / or "associating" means combining fibrous elements and / or particles by direct or indirect contact such that a fibrous structure is formed. In one example, fibrous elements and / or particles that are joined may be bonded to one another, for example, by adhesive and / or thermal bonding. In another example, fibrous elements and / or particles may be bonded to one another by being deposited on the same fibrous structure that makes up the belt and / or patterned belt.
[0070] In one embodiment, two or more fibrous structure plies may be bonded together by an adhesive, such as a chemical bonding agent, e.g., a water-based adhesive. In another embodiment, two or more fibrous structure plies may be bonded together by mechanical interlocking of fibrous elements, e.g., filaments, from one fibrous structure ply to an adjacent fibrous structure ply of a multi-ply fibrous structure, e.g., a multi-ply article. In another embodiment, two or more fibrous structure plies may be bonded together by a pressure bond formed between two adjacent fibrous structure plies of a multi-ply fibrous structure, e.g., a multi-ply article.
[0071] As used herein, "machine direction" or "MD" means the direction parallel to the direction in which a fibrous structure flows through a fibrous structure manufacturing equipment and / or a fibrous structure product making machine.
[0072] As used herein, "cross machine direction" or "CD" means the coplanar direction of a fibrous structure and / or fibrous structure product comprising the fibrous structure that is perpendicular to the machine direction.
[0073] As used herein, a "ply" or "multiple plies" refers to an individual fibrous structure optionally arranged in a substantially continuous face-to-face relationship with another ply to form a multi-ply fibrous structure. It is also contemplated that a single fibrous structure may be effectively formed into two or multiple "plies", e.g., by folding over itself. A ply may include layers of filaments, filament / particle blends, and / or particles. In another example, there may be layers of filaments or particles between the plies.
[0074] As used herein, the articles "a" and "an," e.g., "an anionic surfactant" or "a fiber," as used herein, are understood to mean one or more of the materials claimed or described.
[0075] All percentages and ratios are calculated by weight unless otherwise specified. All percentages and ratios are calculated based on the total composition unless otherwise specified.
[0076] Unless otherwise specified, all component or composition concentrations refer to the active level of that component or composition and are exclusive of impurities, e.g., residual solvents or by-products, that may be present in commercial sources.
[0077] Item dimensions and end seal characteristics The fibrous structures of the present disclosure may include a plurality of fibrous elements, e.g., a plurality of filaments, such as a plurality of active agent-containing filaments, and optionally one or more particles, e.g., water soluble active agent-containing particles, and / or water insoluble particles, e.g., one or more active agent-containing particles, such as zeolites, porous zeolites, perfume loaded zeolites, active agent loaded zeolites, silica, perfume loaded silica, active agent loaded zeolites, perfume microcapsules, clays, and mixtures thereof.
[0078] Without being bound by theory, it is believed that edge seal strength, edge seal width, and / or article dimensions may contribute to achieving a combination of article performance factors that are most favorable to the consumer prior to dissolution in the consumer's hand, including consumer-favorable article flexibility and containment or positioning in the palm of the consumer's hand just prior to and during initial dissolution.
[0079] It is further believed that achieving the proper balance in edge seal strength and edge seal width, respectively, and providing the desired article dimensions may contribute to achieving the most consumer-favorable performance, such as the production of a smooth, silky, lathering solution that fits in the palm of the consumer's hand prior to application to the surface to be treated. It is further believed that a superior combination of article performance in the dry state, as measured by flexibility and dispensing during initial dissolution, the ability to fit in the palm of the consumer's hand just prior to and during initial dissolution, and performance upon application to the surface to be treated, may be provided as measured by the Hand Dissolution Test Method.
[0080] In certain examples, an article may have one or more fiber elements, at least one of which comprises one or more filament-forming materials and one or more active agents releasable from the fiber element. Such an article may further comprise an edge seal generally positioned along at least a portion of the circumference of the article. By providing an edge seal with sufficient edge seal strength, the article may remain intact during manufacturing, dispensing, dispensing, and consumer handling prior to use. However, if the edge seal strength is too great, the article may not meet consumer expectations. For example, if the edge seal is too strong, it may be too dense and non-porous, such that the edge seal may not dissolve easily even if other parts of the article dissolve sufficiently. It is believed that the present disclosure provides a desirable edge seal strength range, such that an article may include an edge seal that can retain its structural integrity without adversely affecting flexibility, solubility, and / or other consumer-acceptable article use characteristics.
[0081] In certain examples, edge seal strength can be improved by increasing the edge seal width. However, providing an edge seal width that is too large may adversely affect consumer acceptable article use characteristics. For example, an edge seal width that is too large may result in an unattractive appearance to consumers, increased article cost, and increased risk of insufficient dissolution. It has also been discovered that edge seals that contain high concentrations of particles may not be able to meet edge seal strength requirements as a result of the particles interfering with bonds within the edge seal. Nevertheless, the presence of particles in the edge seal may enable desirable dissolution of the edge seal and the entire article. Without being bound by theory, it is believed that the particles may help keep the edge seal open and porous so that the edge seal may be accessible to dissolution mechanisms. As with edge seal strength, it is believed that a balance needs to be achieved in the edge seal width and the amount of particles used in the edge seal. It is further believed that such a balance is achieved by the articles of the present disclosure.
[0082] In certain embodiments, the article may exhibit an edge seal strength of about 0.1 N / in to about 4 N / in, or any value therebetween. Thus, in certain embodiments, the article may exhibit an edge seal strength of about 0.1 N / in to about 3 N / in, about 0.2 N / in to about 3 N / in, about 0.2 N / in to about 2 N / in, about 0.2 N / in to about 1 N / in, about 0.3 N / in to about 1 N / in, or about 0.3 N / in to about 0.8 N / in. In one embodiment, the article may exhibit an edge seal strength of about 0.4 N / in. Edge seal strength measurements are taken according to the edge seal strength test method described herein.
[0083] In certain embodiments, the edge seal may have an edge seal width of about 0.5 mm to about 4 mm, or any value therebetween. Thus, in certain embodiments, the edge seal may have an edge seal width of about 0.8 mm to about 3.5 mm, about 1 mm to about 3 mm, about 1.2 mm to about 2.8 mm, about 1.5 mm to about 2.5 mm, or about 1.6 mm to about 2 mm. In one embodiment, the edge seal may have an edge seal width of about 1.7 mm. Edge seal width measurements are taken according to the edge seal strength test method described herein.
[0084] In certain embodiments, the article may have a length of about 1 cm to about 20 cm, about 2 cm to about 20 cm, about 2 cm to about 18 cm, about 3 cm to about 15 cm, about 3 cm to about 12 cm, about 4 cm to about 8 cm, about 4 cm to about 6 cm, or about 5 cm to about 6 cm. In certain embodiments, the article may have a length of about 1 cm to about 10 cm, about 2 cm to about 10 cm, or about 7 cm to about 9 cm.
[0085] In certain embodiments, the article may have a width of about 1 cm to about 11 cm, about 2 cm to about 11 cm, about 2 cm to about 10 cm, about 3 cm to about 9 cm, about 4 cm to about 8 cm, or about 4 cm to about 6 cm. In certain embodiments, the article may have a width of about 1 cm to about 6 cm, about 2 cm to about 6 cm, about 3 cm to about 5 cm, or about 3.5 cm to about 4.5 cm. In other embodiments, the article may have a width of about 6 cm to about 8 cm.
[0086] In certain embodiments, the ratio of the length of the article to the width of the article can be from about 3:1 to about 0.5:1, from about 5:2 to about 0.5:1, or from about 2:1 to about 1:1.
[0087] The article may have a height or thickness of about 0.01 mm or more, about 0.05 mm or more, about 0.1 mm or more, about 0.5 mm or more, about 1 mm or more, about 2 mm or more, about 3 mm or more, or about 4 mm or more. In certain embodiments, the article may have a height or thickness of about 50 mm or less, about 20 mm or less, about 10 mm or less, about 8 mm or less, about 6 mm or less, about 5 mm or less, about 4 mm or less, about 3 mm or less, about 2 mm or less, about 1 mm or less, about 0.5 mm or less, or about 0.3 mm. Thus, in certain embodiments, the article may have a height of about 0.01 mm to about 50 mm, about 0.01 mm to about 44 mm, about 0.1 mm to about 50 mm, about 0.1 mm to about 44 mm, about 1 mm to about 20 mm, or about 1 mm to about 5 mm. In certain embodiments, the article may have a height or thickness of about 3 mm to about 12 mm, or about 4 mm to about 10 mm. Height or thickness measurements are taken in accordance with the Thickness Test Method described herein.
[0088] The article may have a volume of about 0.25 cubic centimeters (cc) to about 60 cc, about 0.5 cc to about 60 cc, about 0.5 cc to about 50 cc, about 1 cc to about 40 cc, about 1 cc to about 30 cc, about 2 cc to about 20 cc, about 3 cc to about 20 cc, about 4 cc to about 15 cc, or about 4 cc to about 10 cc. In certain embodiments, the article may have a volume of about 3 cc to about 6 cc. In certain embodiments, the article may have a volume of about 20 cc to about 35 cc, or about 24 cc to about 30 cc.
[0089] The article may have a mass of about 50 g or less, about 40 g or less, about 30 g or less, about 25 g or less, about 20 g or less, about 15 g or less, about 10 g or less, about 7.5 g or less, about 5 g or less, about 4 g or less, about 3 g or less, 2 g or less, about 1.5 g or less, about 1.25 g or less, about 1 g or less, about 0.75 g or less, or about 0.5 g or less. In certain embodiments, the article may have a mass of about 0.25 g to about 50 g, about 0.25 g to about 40 g, about 0.25 g to about 30 g, about 0.25 g to about 25 g, about 0.25 g to about 20 g, about 0.5 g to about 15 g, about 0.5 g to about 10 g, about 0.5 g to about 5 g, about 0.5 g to about 4 g, about 0.5 g to about 3 g, about 0.5 g to about 2.5 g, about 1 g to about 2 g, etc. In certain embodiments, the article may have a mass of about 5 g to about 15 g, or about 8 g to about 12 g.
[0090] The article may have a density of about 0.05 g / cc or more, about 0.08 g / cc or more, about 0.1 g / cc or more, about 0.15 g / cc or more, about 0.2 g / cc or more, about 0.25 g / cc or more, about 0.3 g / cc or more, about 0.35 g / cc or more, about 0.4 g / cc or more. In certain embodiments, the article may have a density of about 0.8 g / cc or less, about 0.6 g / cc or less, about 0.5 g / cc or less, about 0.4 g / cc or less, about 0.35 g / cc or less, about 0.3 g / cc or less, about 0.25 g / cc or less, about 0.2 g / cc or less, about 0.15 g / cc or less, about 0.12 g / cc or less, about 0.1 g / cc or less, about 0.08 g / cc or less, or about 0.05 g / cc or less. Thus, in certain embodiments, the article may have a density of about 0.05 g / cc to about 0.8 g, about 0.08 g / cc to about 0.8 g / cc, about 0.1 g / cc to about 0.8 g / cc, about 0.2 g / cc to about 0.6 g / cc, about 0.2 g / cc to about 0.4 g / cc, In certain embodiments, the article may have a density of about 0.3 g / cc to about 0.5 g / cc.
[0091] In certain embodiments, the article has one or more of a width of about 1 cm to about 11 cm, a length of about 1 cm to about 20 cm, a height of about 0.01 mm to about 50 mm, a mass of about 0.25 g to about 40 g, a volume of about 0.25 cc to about 60 cc, and a density of about 0.05 g / cc to about 0.8 g / cc. In certain embodiments, the article has one or more of a width of about 1 cm to about 11 cm, a length of about 1 cm to about 20 cm, and a height of about 0.01 mm to about 50 mm. In certain embodiments, the article has one or more of a mass of about 0.25 g to about 40 g, a volume of about 0.25 cc to about 60 cc, and a density of about 0.05 g / cc to about 0.8 g / cc. In certain embodiments, the article has one or more of a width of about 1 cm to about 11 cm, a length of about 1 cm to about 20 cm, and a height of about 0.01 mm to about 50 mm, as well as one or more of a mass of about 0.25 g to about 40 g, a volume of about 0.25 cc to about 60 cc, and a density of about 0.05 g / cc to about 0.8 g / cc.
[0092] Item composition and additional characteristics In addition to the article dimensions above, and optionally one or more of the end seal strength and / or end seal width values above, articles, such as fibrous structures of the present disclosure, may exhibit one or more of the following properties: a. an average maximum peak force when measured according to the modified circular bend test method described herein that is less than 20.00 N, and / or less than 15.00 N, and / or less than 10.00 N, and / or less than 8.50 N, and / or less than 7.50 N, and / or less than 5.00 N, and / or greater than 0 N, and / or greater than 0 to less than 20.00 N; b. an average bending stiffness, when measured according to the modified circular bend test method described herein, of less than 3000.0 N / m, and / or less than 2500.0 N / m, and / or less than 2200.0 N / m, and / or less than 1900.0 N / m, and / or less than 1600.0 N / m, and / or less than 1200.0 N / m, and / or less than 1000.0 N / m, and / or less than 800.0 N / m, and / or less than 500.0 N / m, and / or greater than 100.0 N / m, and / or less than 3000.0 N / m to greater than 100.0 N / m; and c. An average hand dissolution of less than 30 dissolution strokes, and / or less than 29 dissolution strokes, and / or less than 25 dissolution strokes, and / or less than 20 dissolution strokes, and / or less than 15 dissolution strokes, and / or less than 10 dissolution strokes, and / or less than 5 dissolution strokes, and / or less than 30 dissolution strokes to greater than 0 dissolution strokes, and / or less than 25 dissolution strokes to at least 1 dissolution stroke, when measured according to the Hand Dissolution Test Method described herein.
[0093] In one embodiment, one or more plies of a fibrous structure according to the present disclosure may be bonded to one or more other plies of a fibrous structure, such as another fibrous structure ply according to the present disclosure, by bonding the plies together, for example, by glue, adhesive, water, heat bonding, crimping, intertwining of fibers from one ply to another, needle punching of fibers from one ply to another, temporary bonding of the plies, bonding of the plies in discontinuous zones / regions between the plies or only in distinct zones / regions, a combination of the ply bonding methods described herein, or other suitable means of bonding the plies together. In another embodiment, two or more fibrous structure plies may be bonded together by mechanical intertwining of filaments from one fibrous structure ply to an adjacent fibrous structure ply.
[0094] Articles, such as fibrous structures according to the present disclosure, when measured according to the Hand Dissolution Test Method described herein, may exhibit an average hand dissolution value of less than 30 dissolution strokes, and / or less than 29 dissolution strokes, and / or less than 25 dissolution strokes, and / or less than 20 dissolution strokes, and / or less than 15 dissolution strokes, and / or less than 10 dissolution strokes, and / or less than 5 dissolution strokes.
[0095] In one example, an article, such as a fibrous structure of the present disclosure, may exhibit an average disintegration time of less than 360 seconds (s), and / or less than 200 s, and / or less than 100 s, and / or less than 60 s, and / or less than 30 s, and / or less than 10 s, and / or less than 5 s, and / or less than 2.0 s, and / or less than 1.5 s, and / or about 0 s, and / or greater than 0 s, when measured according to the dissolution test method described herein.
[0096] In one example, an article, such as a fibrous structure of the present disclosure, may exhibit an average dissolution time of less than 3600 seconds (s), and / or less than 3000 s, and / or less than 2400 s, and / or less than 1800 s, and / or less than 1200 s, and / or less than 600 s, and / or less than 400 s, and / or less than 300 s, and / or less than 200 s, and / or less than 175 s, and / or less than 100 s, and / or less than 50 s, and / or greater than 1 s, when measured according to the dissolution test method described herein.
[0097] In another example, the articles, e.g., fibrous structures of the present disclosure, exhibit an average dissolution time, when measured according to the dissolution test methods described herein, of less than 24 hours, and / or less than 12 hours, and / or less than 6 hours, and / or less than 1 hour (3600 seconds), and / or less than 30 minutes, and / or less than 25 minutes, and / or less than 20 minutes, and / or less than 15 minutes, and / or less than 10 minutes, and / or less than 5 minutes, and / or greater than 1 second, and / or greater than 5 seconds, and / or greater than 10 seconds, and / or greater than 30 seconds, and / or greater than 1 minute.
[0098] In one example, an article, such as a fibrous structure of the present disclosure, may exhibit an average disintegration time per gsm of sample of about 1.0 seconds / gsm (s / gsm) or less, and / or about 0.5 s / gsm or less, and / or about 0.2 s / gsm or less, and / or about 0.1 s / gsm or less, and / or about 0.05 s / gsm or less, and / or about 0.03 s / gsm or less, when measured according to the dissolution test method described herein.
[0099] In one example, an article, such as a fibrous structure of the present disclosure, may exhibit an average dissolution time per gsm of sample of about 10 seconds / gsm (s / gsm) or less, and / or about 5.0 s / gsm or less, and / or about 3.0 s / gsm or less, and / or about 2.0 s / gsm or less, and / or about 1.8 s / gsm or less, and / or about 1.5 s / gsm or less, when measured according to the dissolution test method described herein.
[0100] In one embodiment, the fibrous elements and / or particles may be disposed within the fibrous structure to provide the fibrous structure with two or more regions or layers containing different active agents, for example, one region of the fibrous structure may contain a bleaching agent and / or a surfactant, and another region of the fibrous structure may contain a softening agent.
[0101] As shown in FIG. 2 , certain examples of articles 20 of the present disclosure, such as multi-ply fibrous structures according to the present disclosure, may include two or more distinct fibrous structure layers, or plies 22, 24, in the z-direction of article 20 (of filaments 10 of the present disclosure forming the fibrous structure of article 20). The filaments 10 in layer 22 may be the same as or different from the filaments 10 in layer 24. Each layer, or ply 22, 24, may include a plurality of filaments that are the same, substantially the same, or different. For example, filaments that may release an active agent at a faster rate than other filaments in article 20 and / or one or more of the fibrous structure layers, or plies 22, 24, of article 20 may be the same as or different from the filaments 10 in layer 24. The layers or plies 22 and 24 may be positioned as the outer surface of the article 20. The layers or plies 22 and 24 may be bonded to one another by mechanical interlocking at their interface between the two layers or plies, and / or by thermal or adhesive bonding, and / or by depositing one of the layers or plies onto the other existing layer or ply, for example by spinning fiber elements of layer or ply 22 onto the surface of layer or ply 24. Figure 3 shows another view of the article 20 with plies 22 and 24. With regard to the article dimensions above, the length (L), width (W), and height (H) of the article are shown in Figure 3 to correspond to measurements in the x-, y-, and z-directions, respectively.
[0102] 4, another embodiment of an article 20, e.g., a fibrous structure according to the present disclosure, includes a first fibrous structure layer or ply 22 including a plurality of fibrous elements, e.g., filaments 10, a second fibrous structure layer 24 including a plurality of fibrous elements, e.g., filaments 10, and a plurality of particles or a particle layer 26 positioned between the first fibrous structure layer 22 and the second fibrous structure layer 24. A similar fibrous structure may be formed by depositing a plurality of particles on a surface of a first ply of a fibrous structure including a plurality of fibrous elements, and then bonding a second ply of a fibrous structure including a plurality of fibrous elements such that the particle or particle layer is positioned between the first and second fibrous structure plies.
[0103] As shown in FIG. 5, another embodiment of an article 20 of the present disclosure, e.g., a fibrous structure of the present disclosure, includes a first fibrous structure layer 22 including a plurality of fibrous elements, e.g., filaments 10, and the first fibrous structure layer 22 includes one or more pockets 28 (also called recesses, unfilled domes, or deflection zones), which may be in an irregular or non-random repeating pattern. One or more of the pockets 28 may include one or more particles 26. The article 20 of this embodiment further includes a second fibrous structure layer 24 bonded to the first fibrous structure layer 22 such that the particles 26 are encapsulated in the pockets 28. As described above, a similar article may be formed by depositing a plurality of particles in the pockets of a first ply of a fibrous structure including a plurality of fibrous elements, and then bonding a second ply of a fibrous structure including a plurality of fibrous elements such that the particles are encapsulated in the pockets of the first ply. In one embodiment, the pockets may be separate from the fibrous structure, creating separate pockets.
[0104] As shown in FIG. 6, another embodiment of an article 20, e.g., a multi-ply fibrous structure of the present disclosure, includes a first ply 30 of a fibrous structure according to FIG. 5 above, and a second ply 32 of a fibrous structure bonded to the first ply 30, the second ply 32 including a plurality of fibrous elements, e.g., filaments 10, and a plurality of particles 26 distributed (in this case randomly) in the x-, y-, and z-axes across the article 20.
[0105] As shown in FIG. 7 , another embodiment of an article 20 of the present disclosure, e.g., a fibrous structure of the present disclosure, includes a plurality of fibrous elements, e.g., filaments 10, such as active agent-containing filaments, and a plurality of particles 26, e.g., active agent-containing particles, distributed (in this case randomly) in the x-axis, y-axis, and z-axis throughout the article 20.
[0106] 8, another embodiment of an article 20, e.g., a fibrous structure of the present disclosure, includes a first fibrous structure layer 22 including a plurality of fibrous elements, e.g., filaments 10, a second fibrous structure layer 24 including a plurality of fibrous elements, e.g., filaments 10, e.g., active agent-containing filaments, and a plurality of particles 26, e.g., active agent-containing particles, distributed (in this case randomly) in the x-, y-, and z-axes across the second fibrous structure layer 24. Alternatively, in another embodiment, the plurality of particles 26, e.g., active agent-containing particles, may be distributed within the second fibrous structure layer 24 in an irregular or non-random repeating pattern. As discussed above, a similar article including a two-ply fibrous structure includes a first fibrous structure ply 22 including a plurality of fibrous elements, e.g., filaments 10, a second fibrous structure ply 24 including a plurality of fibrous elements, e.g., filaments 10, e.g., active agent-containing filaments, and a plurality of particles 26, e.g., active agent-containing particles, distributed (in this case randomly) in the x-, y-, and z-axes across the second fibrous structure ply 24. Alternatively, in another embodiment, the plurality of particles 26, e.g., active agent-containing particles, may be distributed within the second fibrous structure ply 24 in an irregular or non-random repeating pattern.
[0107] FIG. 9 illustrates another embodiment of an article 20, e.g., a multi-ply fibrous structure of the present disclosure, including a first fibrous structure layer 22 including a plurality of fibrous elements, e.g., filaments 10, a second fibrous structure layer 24 including a plurality of fibrous elements, e.g., filaments 10, e.g., active agent-containing filaments, a first ply 30 of fibrous structure as shown in FIG. 8 including a plurality of particles 26, e.g., active agent-containing particles, distributed (in this case randomly) in the x-axis, y-axis, and z-axis across the second fibrous structure ply 24, and a second ply 32 of fibrous structure bonded to the first ply 30, the first fibrous structure layer 22 including a plurality of fibrous elements, e.g., filaments 10, and a second fibrous structure layer 24 including a plurality of fibrous elements, e.g., filaments 10, and a plurality of particles 26, e.g., active agent-containing particles, distributed (in this case randomly) in the x-axis, y-axis, and z-axis across the second fibrous structure ply 24. a second ply 32 including a first fibrous structure layer 22 including a plurality of fibrous elements, e.g., filaments 10, a second layer 24 including active agent-containing filaments, and a plurality of particles 26, e.g., active agent-containing particles, distributed (in this case randomly) across the second fibrous structure layer 24 in the x-axis, y-axis, and z-axis; and a third ply 34 of fibrous structure bonded to the second ply 32, the third ply 34 including a first fibrous structure layer 22 including a plurality of fibrous elements, e.g., filaments 10, a second fibrous structure layer 24 including a plurality of fibrous elements, e.g., filaments 10, a
[0108] As shown in Figure 10, another embodiment of an article 20, such as a multi-ply fibrous structure of the present disclosure, includes a first ply 30 of a fibrous structure including a plurality of fibrous elements, such as filaments 10, a second ply 32 of a fibrous structure bonded to the first ply 30, the second ply 32 of a fibrous structure including a plurality of fibrous elements, such as filaments 10, and a third ply 34 of a fibrous structure bonded to the second ply 32, the third ply 34 of a fibrous structure including a plurality of fibrous elements, such as filaments 10. In one embodiment of Figure 10, the filaments 10 of each ply may include an active agent-containing filament.
[0109] 11 illustrates another embodiment of an article 20 of the present disclosure, a multi-ply fibrous structure 20 of the present disclosure, including a first ply 30 of a fibrous structure including a plurality of fibrous elements, e.g., filaments 10, a second ply 32 of a fibrous structure including a plurality of fibrous elements, e.g., filaments 10, a third ply 34 of a fibrous structure including a plurality of fibrous elements, e.g., filaments 10, a fourth ply 36 of a fibrous structure including a plurality of fibrous elements, e.g., filaments 10, and a fifth ply 38 of a fibrous structure including a plurality of fibrous elements, e.g., filaments 10. In this embodiment, the article 20 further includes one or more particles or particle layers 26 positioned between at least two adjacent fibrous structure plies, e.g., plies 30 and 32, or plies 32 and 34, or plies 34 and 36, or plies 36 and 38. Plies 30, 32, 34, 36, and 38 are bonded with one or more other plies to form a unitary structure, minimizing dissociation of particles 26 from article 20, if present within article 20. In another embodiment, one or more particles or particle layers 26 positioned between at least two adjacent fibrous structure plies are present in an irregular pattern, a non-random repeating pattern, or only in selected zones between the plies.
[0110] FIG. 12 illustrates another embodiment of an article 20, which includes one or more fiber elements including one or more filament forming materials and one or more active agents releasable from the fiber elements. The article 20 further includes an end seal 21 generally positioned along the periphery of the article 20. As shown in FIG. 12, the end seal 21 includes end seal B. In certain embodiments, the end seal 21 may be continuous, as shown in FIG. 12. However, in other embodiments, the end seal 21 may be discontinuous, such that the end seal 21 is positioned only along a portion of the periphery of the article 20. In certain embodiments, at least one of the two or more fiber structure plies may include one or more particles, and in certain embodiments, the end seal 21 may include one or more particles therein.
[0111] In such an embodiment of the article 20 having an edge seal 21, the article 20 may include two or more fibrous structure plies, such that the article 20 is a multi-ply article. In certain embodiments, at least two of the two or more fibrous structure plies may be formed from different compositions. In certain embodiments, the article 20 may include a first outermost ply 23 and a second outermost ply 25, as shown in FIG. 13, for example, and the respective ends of the first outermost ply 23 and the second outermost ply 25 may form the edge seal 21. The article 20 may further include one or more inner plies, which may be surrounded by the first outermost ply 23 and the second outermost ply 25. It will be understood that the article 20 may include any suitable amount of inner plies, but as the amount of inner plies increases, the likelihood of melting of the edge seal occurring may become increasingly high. In certain embodiments, one or more inner plies do not form the edge seal 21. However, it will be understood that in other embodiments, the respective ends of the first outermost ply, the second outermost ply, and the one or more inner plies may form an edge seal. In certain embodiments, the one or more inner plies may include one or more particles therein, and in certain embodiments, the first outermost ply 23 and the second outermost ply 25 may be substantially free of particles.
[0112] Although the fibrous elements and / or fibrous structures of the present disclosure are in solid form, the filament-forming composition used to produce the fibrous elements of the present disclosure may be in liquid form.
[0113] In one embodiment, the fibrous structure includes a plurality of fibrous elements that are identical or substantially identical in composition to the fibrous elements according to the present disclosure. In another embodiment, the fibrous structure may include two or more different fibrous elements according to the present disclosure. Non-limiting examples of differences between the fibrous elements may include physical differences such as different diameters, lengths, textures, shapes, stiffness, elasticity; chemical differences such as crosslinking levels, solubility, melting points, Tg, active agents, filament-forming materials, colors, active agent concentrations, basis weights, filament-forming materials concentrations, the presence of any coatings on the fibrous elements, biodegradable or not, hydrophobic or not, contact angles; differences in whether the fibrous elements lose their physical structure when exposed to the intended use conditions; differences in whether the morphology of the fibrous elements changes when exposed to the intended use conditions; and differences in the rate at which the fibrous elements release one or more of their active agents when exposed to the intended use conditions. In one embodiment, two or more fibrous elements and / or particles in the fibrous structure may include different active agents. This may be the case when different actives, such as an anionic surfactant (eg, a shampoo active) and a cationic surfactant (eg, a hair conditioner active), are not compatible with each other.
[0114] In one embodiment, at least one of the one or more active agents present in the fibrous element comprises a first surfactant and the active agent-containing particle comprises a second surfactant, e.g., the first surfactant is different from the second surfactant.
[0115] In another example, the fibrous structure may exhibit different regions, e.g., regions of different basis weight, density, and / or thickness. In yet another example, the fibrous structure may include a texture on one or more of its surfaces. The surface of the fibrous structure may include a pattern, such as a non-random repeating pattern. The fibrous structure may be embossed with an embossed pattern. In another example, the fibrous structure may include apertures. The apertures may be arranged in a non-random repeating pattern.
[0116] In one example, the fibrous structure may include separate regions of fibrous elements that are distinct from other portions of the fibrous structure.
[0117] Non-limiting examples of applications for the fibrous structures of the present disclosure include, but are not limited to, washer dryer substrates, washing machine substrates, bath towels, hard surface cleaning and / or polishing substrates, floor cleaning and / or polishing substrates, components in batteries, baby wipes, adult wipes, feminine hygiene wipes, toilet paper wipes, window cleaning substrates, oil containment and / or cleaning substrates, insect control substrates, swimming pool chemical substrates, food, breath fresheners, deodorants, garbage disposal bags, packaging films and / or wraps, wound dressings, pharmaceutical delivery, building insulation, crop and / or plant covers and / or beds, starch substrates, skin care substrates, hair care substrates, air care agents, water treatment substrates and / or filters, toilet bowl cleaning substrates, candy substrates, pet food, livestock bedding, tooth whitening substrates, carpet cleaning substrates, and other suitable applications for the active agents of the present disclosure.
[0118] The fibrous structures of the present disclosure may be used as is or may be coated with one or more active agents.
[0119] In one example, the fibrous structure may exhibit a thickness of greater than 0.01 mm, and / or greater than 0.05 mm, and / or greater than 0.1 mm, and / or up to about 50 mm, and / or up to about 20 mm, and / or up to about 10 mm, and / or up to about 5 mm, and / or up to about 2 mm, and / or up to about 0.5 mm, and / or up to about 0.3 mm, when measured according to the Thickness Test Method described herein.
[0120] In certain embodiments, a product assembly may include one or more of the articles described herein.
[0121] Other non-limiting examples of fibrous structures suitable for the present disclosure are disclosed in U.S. Patent Application Publication No. 2013 / 0171421(A1) and U.S. Patent No. 9,139,802, which are incorporated by reference.
[0122] particle The particles may be water-soluble or water-insoluble. In one embodiment, some particles may be water-soluble and others may be water-insoluble. The particles (water-soluble or water-insoluble) may provide a consumer benefit in themselves. In another embodiment, the particles (water-soluble or water-insoluble) may comprise one or more active agents (in other words, the particles may comprise active agent-containing particles). In yet another embodiment, the particles consist essentially of one or more active agents (in other words, the particles (water-soluble and / or water-insoluble) may comprise 100% or more than about 100% by weight of one or more active agents on a dry particle basis). In yet another embodiment, the particles may comprise water-soluble particles. In yet another embodiment, the particles may comprise water-soluble active agent-containing particles. In another embodiment, the water-insoluble particles include zeolites, porous zeolites, perfume-loaded zeolites, active agent-loaded zeolites, silica, perfume-loaded silica, active-loaded silica, perfume microcapsules, clays, and mixtures thereof.
[0123] In one embodiment, the particles include water-soluble particles, such as water-soluble active-containing particles that include an active selected from the group consisting of bleaches, builders, enzymes, antimicrobial agents, antibacterial agents, antifungal agents, perfume delivery systems, dye transfer inhibitors, brighteners, hueing dyes, and mixtures thereof. In one embodiment, the water-soluble active-containing particles include enzyme granules. In another embodiment, the water-soluble active-containing particles include encapsulated bleaches. In another embodiment, the water-soluble active-containing particles include perfume microcapsules.
[0124] In one embodiment, at least one of the particles comprises a water insoluble particle, for example a water insoluble active agent-containing particle.
[0125] In one embodiment, the one or more particles are present as separate particles within the article.
[0126] Textile elements The fiber elements may be water soluble or water insoluble. In one embodiment, the fiber elements include one or more filament forming materials. In another embodiment, the fiber elements include one or more active agents. In yet another embodiment, the fiber elements include one or more filament forming materials and one or more active agents. In another example, the fiber elements may include water soluble fiber elements.
[0127] The fibrous elements of the present disclosure, such as filaments and / or fibers, comprise one or more filament-forming materials. In addition to the filament-forming materials, the fibrous elements may further comprise one or more active agents releasable from the fibrous elements, such as when the fibrous elements and / or fibrous structures comprising the fibrous elements are exposed to intended use conditions. In one embodiment, the total concentration of the one or more filament-forming materials present in the fibrous elements is less than 80% by weight based on the dry fibrous elements and / or the dry fibrous structures, and the total concentration of the one or more active agents present in the fibrous elements is greater than 20% by weight based on the dry fibrous elements and / or the dry fibrous structures.
[0128] In one embodiment, the fibrous elements of the present disclosure comprise about 100% and / or more than 95% and / or more than 90% and / or more than 85% and / or more than 75% and / or more than 50% by weight of one or more filament-forming materials based on the dry fibrous elements and / or on the dry fibrous structure. For example, the filament-forming materials may include polyvinyl alcohol, starch, carboxymethyl cellulose, and other suitable polymers, particularly hydroxyl polymers.
[0129] In another embodiment, a fibrous element of the present disclosure comprises one or more filament-forming materials and one or more active agents, wherein the total concentration of the filament-forming materials present in the fibrous element is from about 5% to less than 80% by weight based on the dry fibrous element and / or the dry fibrous structure, and the total concentration of the active agents present in the fibrous element is from more than 20% to about 95% by weight based on the dry fibrous element and / or the dry fibrous structure.
[0130] In one embodiment, the fibrous elements of the present disclosure comprise at least 10% by weight, and / or at least 15% by weight, and / or at least 20% by weight, and / or less than 80% by weight, and / or less than 75% by weight, and / or less than 65% by weight, and / or less than 60% by weight, and / or less than 55% by weight, and / or less than 50% by weight, and / or less than 45% by weight, and / or less than 40% by weight, based on the dry fibrous elements and / or on the dry fibrous structure. and greater than about 20% by weight, and / or at least about 30% by weight, and / or at least about 35% by weight, and / or at least about 40% by weight, and / or at least about 45% by weight, and / or at least about 50% by weight, and / or at least about 60% by weight, and / or less than about 95% by weight, and / or less than about 90% by weight, and / or less than about 85% by weight, and / or less than about 80% by weight, and / or less than about 75% by weight of active agent based on the base and / or dry fibrous structure.
[0131] In one embodiment, a fibrous element of the present disclosure comprises at least 5% by weight, and / or at least 10% by weight, and / or at least 15% by weight, and / or at least 20% by weight, and / or less than 50% by weight, and / or less than 45% by weight, and / or less than 40% by weight, and / or less than 35% by weight, and / or less than 30% by weight, and / or less than 25% by weight, of a filament-forming material based on the dry fibrous element and / or on the dry fibrous structure, and more than about 30% by weight, and / or at least about 50% by weight, and / or at least about 55% by weight, and / or at least about 60% by weight, and / or at least about 65% by weight, and / or at least about 70% by weight, and / or less than about 95% by weight, and / or less than about 90% by weight, and / or less than about 85% by weight, and / or less than about 80% by weight, and / or less than about 75% by weight, of an active agent based on the dry fibrous element and / or on the dry fibrous structure. In one embodiment, the fibrous element of the present disclosure comprises more than 80% by weight of an active agent based on the dry fibrous element and / or based on the dry fibrous structure.
[0132] In another embodiment, the one or more filament-forming materials and active agent are present in the fiber elements in a weight ratio of total concentration of filament-forming materials to active agent of 4.0 or less, and / or 3.5 or less, and / or 3.0 or less, and / or 2.5 or less, and / or 2.0 or less, and / or 1.85 or less, and / or less than 1.7, and / or less than 1.6, and / or less than 1.5, and / or less than 1.3, and / or less than 1.2, and / or less than 1, and / or less than 0.7, and / or less than 0.5, and / or less than 0.4, and / or less than 0.3, and / or greater than 0.1, and / or greater than 0.15, and / or greater than 0.2.
[0133] In yet another embodiment, the fibrous elements of the present disclosure comprise from about 10% and / or from about 15% to less than 80% by weight of a filament-forming material (e.g., polyvinyl alcohol polymer, starch polymer, and / or carboxymethyl cellulose polymer) based on the dry fibrous element and / or on the dry fibrous structure, and from more than 20% to about 90% and / or to about 85% by weight of an active agent based on the dry fibrous element and / or on the dry fibrous structure. The fibrous elements may further comprise a plasticizer (e.g., glycerin) and / or a pH adjuster (e.g., citric acid).
[0134] In yet another embodiment, the fibrous elements of the present disclosure comprise from about 10% and / or from about 15% to less than 80% by weight of a filament-forming material (e.g., polyvinyl alcohol polymer, starch polymer, and / or carboxymethyl cellulose polymer) based on the dry fibrous element and / or on the dry fibrous structure, and from more than 20% to about 90% and / or to about 85% by weight of an active agent based on the dry fibrous element and / or on the dry fibrous structure, the weight ratio of the filament-forming material to the active agent being 4.0 or less. The fibrous elements may further comprise a plasticizer (e.g., glycerin) and / or a pH adjuster (e.g., citric acid).
[0135] In yet another embodiment of the present disclosure, the fiber elements comprise one or more filament-forming materials and one or more active agents selected from the group consisting of enzymes, bleaches, builders, chelating agents, sensates, dispersants, and mixtures thereof, which are releasable and / or released when the fiber elements and / or the fiber structure comprising the fiber elements are exposed to intended use conditions. In one embodiment, the fibrous element comprises a filament-forming material in a total concentration of less than 95% by weight, and / or less than 90% by weight, and / or less than 80% by weight, and / or less than 50% by weight, and / or less than 35% by weight, and / or up to about 5% by weight, and / or up to about 10% by weight, and / or up to about 20% by weight, based on the dry fibrous element and / or on the dry fibrous structure, and an active agent selected from the group consisting of enzymes, bleaches, builders, chelating agents, fragrances, antimicrobial agents, antibacterial agents, antifungal agents, and mixtures thereof in a total concentration of more than 5% by weight, and / or more than 10% by weight, and / or more than 20% by weight, and / or more than 35% by weight, and / or more than 50% by weight, and / or more than 65% by weight, and / or up to about 95% by weight, and / or up to about 90% by weight, and / or up to about 80% by weight, based on the dry fibrous element and / or on the dry fibrous structure. In one example, the active agent includes one or more enzymes. In another example, the active agent includes one or more bleaching agents. In yet another example, the active agent includes one or more builders. In yet another example, the active agent includes one or more chelating agents. In yet another example, the active agent includes one or more fragrances. In yet another example, the active agent includes one or more antimicrobial, antibacterial, and / or antifungal agents.
[0136] In yet another embodiment of the present disclosure, the fiber elements of the present disclosure may include active agents that may pose health and / or safety concerns if dispersed into the air, for example, the fiber elements may be used to prevent enzymes within the fiber elements from dispersing into the air.
[0137] In one embodiment, the fiber elements of the present disclosure can be meltblown fiber elements. In another embodiment, the fiber elements of the present disclosure can be spunbond fiber elements. In another example, the fiber elements can be hollow fiber elements before and / or after the active agent(s) thereof are released.
[0138] The fiber elements of the present disclosure may be hydrophilic or hydrophobic. The fiber elements may be surface and / or internally treated to change the inherent hydrophilicity or hydrophobicity of the fiber elements.
[0139] In one example, the fiber elements exhibit a diameter of less than 100 μm, and / or less than 75 μm, and / or less than 50 μm, and / or less than 25 μm, and / or less than 10 μm, and / or less than 5 μm, and / or less than 1 μm, when measured according to the Diameter Test Method described herein. In another example, the fiber elements of the present disclosure exhibit a diameter of more than 1 μm, when measured according to the Diameter Test Method described herein. The diameter of the fiber elements of the present disclosure can be used to control the release rate of one or more active agents present in the fiber elements and / or the rate of loss and / or change of the physical structure of the fiber elements.
[0140] The fiber elements may include two or more different active agents. In one example, the fiber elements include two or more different active agents, where the two or more different active agents are compatible with each other. In another example, the fiber elements include two or more different active agents, where the two or more different active agents are incompatible with each other.
[0141] In one example, a fiber element may include an active agent in the fiber element and an active agent on the exterior surface of the fiber element, such as an active agent coated on the fiber element. The active agent on the exterior surface of the fiber element may be the same as or different from the active agent present in the fiber element. If different, the active agents may be compatible or incompatible with each other.
[0142] In another embodiment, the fibrous structure or article of the present disclosure may include a coating on the outer fibrous elements or filaments located on one of the surfaces of the plies of the article. The coating may be applied to the surface of the ply, and the surface having the coating may be the outer surface of the entire article, or may be an interior surface of the article. The placement of the coating depends on the benefit agent or active agent desired to be delivered. For example, a coating on the outer surface ply of the article will be more easily visible to the consumer since it is on a surface that the consumer can see. A coating on the inner surface ply of the article may be less visible since it may be hidden from the direct view of the consumer. The placement of the coating on the inner and / or outer surfaces of the article will be accomplished as part of the article manufacturing process. The coating on the inner surface ply may be different or the same as the coating on the outer surface of the article. In one embodiment, the article may have a coating on the outer and / or inner surface of the article. In another embodiment, the article may have a coating on the outer and / or inner surfaces of the plies that make up the article. In yet another embodiment, the article may have a silicone active, including amino silicone, coating or coating containing coating on the exterior and / or interior surfaces of the plies that make up the article.
[0143] In one example, the one or more active agents may be uniformly or substantially uniformly distributed throughout the fiber element. In another example, the one or more active agents may be distributed as separate regions within the fiber element. In yet another example, at least one active agent is uniformly or substantially uniformly distributed throughout the fiber element and at least one other active agent is distributed as one or more separate regions within the fiber element. In yet another example, at least one active agent is distributed as one or more separate regions within the fiber element and at least one other active agent is distributed as one or more separate regions within the fiber element that are different from the first separate region.
[0144] Filament forming material The filament-forming material is any suitable material, such as a polymer or monomers capable of producing a polymer, exhibiting suitable properties for producing filaments, such as by a spinning process.
[0145] In one embodiment, the filament-forming material may include a polar solvent-soluble material, such as an alcohol-soluble material and / or a water-soluble material.
[0146] In another embodiment, the filament-forming material may include a non-polar solvent soluble material.
[0147] In yet another embodiment, the filament forming material may comprise water soluble material and may be free of water insoluble material (less than 5% by weight, and / or less than 3% by weight, and / or less than 1% by weight, and / or 0% by weight, based on the dry fibrous element and / or on the dry fibrous structure).
[0148] In yet another embodiment, the filament-forming material can be a film-forming material. In yet another embodiment, the filament-forming material can be synthetic or naturally derived, and the material can be chemically, enzymatically, and / or physically modified.
[0149] In yet another embodiment of the present disclosure, the filament forming material may include a polymer selected from the group consisting of polymers derived from acrylic monomers such as ethylenically unsaturated carboxylic acid monomers and ethylenically unsaturated monomers, polyvinyl alcohol, polyvinyl formamide, polyvinyl amine, polyacrylates, polymethacrylates, copolymers of acrylic acid and methyl acrylate, polyvinyl pyrrolidone, polyalkylene oxides, starch and starch derivatives, pullulan, gelatin, cellulose derivatives (e.g., hydroxypropyl methylcellulose, methylcellulose, carboxymethylcellulose).
[0150] In yet another embodiment, the filament forming material may comprise a polymer selected from the group consisting of polyvinyl alcohol, polyvinyl alcohol derivatives, starch, starch derivatives, cellulose derivatives, hemicellulose, hemicellulose derivatives, proteins, sodium alginate, hydroxypropyl methylcellulose, chitosan, chitosan derivatives, polyethylene glycol, tetramethylene ether glycol, polyvinylpyrrolidone, hydroxymethylcellulose, hydroxyethylcellulose, carboxymethylcellulose, and mixtures thereof.
[0151] In another embodiment, the filament forming material comprises a polymer selected from the group consisting of pullulan, hydroxypropyl methylcellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, polyvinylpyrrolidone, carboxymethyl cellulose, sodium alginate, xanthan gum, tragacanth gum, guar gum, acacia gum, arabic gum, polyacrylic acid, methyl methacrylate copolymer, carboxyvinyl polymer, dextrin, pectin, chitin, levan, elsinan, collagen, gelatin, zein, gluten, soy protein, casein, polyvinyl alcohol, carboxylated polyvinyl alcohol, sulfonated polyvinyl alcohol, starch, starch derivatives, hemicellulose, hemicellulose derivatives, proteins, chitosan, chitosan derivatives, polyethylene glycol, tetramethylene ether glycol, hydroxymethyl cellulose, and mixtures thereof.
[0152] water soluble material Non-limiting examples of water-soluble materials include water-soluble polymers. The water-soluble polymers may be synthetic or naturally derived and may be chemically and / or physically modified. In one example, the polar solvent-soluble polymers exhibit a weight average molecular weight of at least 10,000 g / mol, and / or at least 20,000 g / mol, and / or at least 40,000 g / mol, and / or at least 80,000 g / mol, and / or at least 100,000 g / mol, and / or at least 1,000,000 g / mol, and / or at least 3,000,000 g / mol, and / or at least 10,000,000 g / mol, and / or at least 20,000,000 g / mol, and / or up to about 40,000,000 g / mol, and / or up to about 30,000,000 g / mol.
[0153] Non-limiting examples of water-soluble polymers include water-soluble hydroxyl polymers, water-soluble thermoplastic polymers, water-soluble biodegradable polymers, water-soluble non-biodegradable polymers, and mixtures thereof. In one example, the water-soluble polymer comprises polyvinyl alcohol. In another example, the water-soluble polymer comprises starch. In yet another example, the water-soluble polymer comprises polyvinyl alcohol and starch. In yet another example, the water-soluble polymer comprises carboxymethyl cellulose. In another example, the polymer comprises carboxymethyl cellulose and polyvinyl alcohol.
[0154] a. Water-Soluble Hydroxyl Polymers - Non-limiting examples of water-soluble hydroxyl polymers according to the present disclosure include polyols, such as polyvinyl alcohol, polyvinyl alcohol derivatives, polyvinyl alcohol copolymers, starch, starch derivatives, starch copolymers, chitosan, chitosan derivatives, chitosan copolymers, cellulose derivatives, such as cellulose ether and ester derivatives, cellulose copolymers, hemicellulose, hemicellulose derivatives, hemicellulose copolymers, gums, arabinans, galactans, proteins, carboxymethylcellulose and various other polysaccharides, and mixtures thereof.
[0155] In one embodiment, the water soluble hydroxyl polymer of the present disclosure comprises a polysaccharide.
[0156] As used herein, "polysaccharides" refers to natural polysaccharides and polysaccharide derivatives and / or modified polysaccharides. Suitable water-soluble polysaccharides include, but are not limited to, starch, starch derivatives, chitosan, chitosan derivatives, cellulose derivatives, hemicellulose, hemicellulose derivatives, gums, arabinans, galactans, and mixtures thereof. The water-soluble polysaccharides may exhibit a weight average molecular weight of about 10,000 g / mol to about 40,000,000 g / mol, and / or greater than 100,000 g / mol, and / or greater than 1,000,000 g / mol, and / or greater than 3,000,000 g / mol, and / or greater than about 3,000,000 g / mol to about 40,000,000 g / mol.
[0157] The water soluble polysaccharides may comprise non-cellulosic and / or non-cellulosic derivative and / or non-cellulosic copolymer water soluble polysaccharides. Such non-cellulosic water soluble polysaccharides may be selected from the group consisting of starch, starch derivatives, chitosan, chitosan derivatives, hemicellulose, hemicellulose derivatives, gums, arabinans, galactans, and mixtures thereof.
[0158] In another embodiment, the water soluble hydroxyl polymer of the present disclosure comprises a non-thermoplastic polymer.
[0159] The water soluble hydroxyl polymers may have a weight average molecular weight of about 10,000 g / mol to about 40,000,000 g / mol, and / or greater than 100,000 g / mol, and / or greater than 1,000,000 g / mol, and / or greater than 3,000,000 g / mol, and / or greater than about 3,000,000 g / mol to about 40,000,000 g / mol. Higher and lower molecular weight water soluble hydroxyl polymers may be used in combination with hydroxyl polymers having a particular desired weight average molecular weight.
[0160] For example, well-known modifications of water-soluble hydroxyl polymers, such as native starch, include chemical and / or enzymatic modifications. For example, native starch can be acid-thinned, hydroxyethylated, hydroxypropylated, and / or oxidized. Additionally, the water-soluble hydroxyl polymer can include dent corn starch.
[0161] Starches of natural origin are generally mixtures of linear amylose and branched amylopectin polymers of D-glucose units. Amylose is a substantially linear polymer of D-glucose units linked by (1,4)-α-D bonds. Amylopectin is a highly branched polymer of D-glucose units linked at the branch points by (1,4)-α-D and (1,6)-α-D bonds. Starches of natural origin, such as corn starch (64-80% amylopectin), waxy maize (93-100% amylopectin), rice (83-84% amylopectin), potato (about 78% amylopectin), and wheat (73-83% amylopectin), typically contain relatively high concentrations of amylopectin. While all starches are potentially useful herein, the present disclosure is most commonly practiced with high amylopectin native starches derived from agricultural sources, which offer the advantages of being in abundant supply, easily replenished, and inexpensive.
[0162] As used herein, "starch" includes mixtures of amylose or amylopectin fractions, as well as unmodified starches, modified starches, synthetic starches, and mixtures thereof of any natural origin, and starches may be modified by physical, chemical, or biological processes, or a combination thereof. The choice of unmodified or modified starch for the present disclosure may depend on the desired end product. In one embodiment of the present disclosure, the starch or starch mixture useful in the present disclosure has an amylopectin content of about 20% to about 100%, more typically about 40% to about 90%, and even more typically about 60% to about 85%, by weight of the starch or mixture thereof.
[0163] Suitable starches of natural origin may include, but are not limited to, corn starch, potato starch, sweet potato starch, wheat starch, sago starch, tapioca starch, rice starch, soybean starch, arrowroot starch, amioca starch, bracken starch, lotus starch, waxy corn starch, and high amylose corn starch. Starches of natural origin, especially corn starch and wheat starch, are preferred starch polymers in terms of economy and availability.
[0164] The polyvinyl alcohol herein can be grafted with other monomers to modify its properties. A wide range of monomers have been successfully grafted onto polyvinyl alcohol. Non-limiting examples of such monomers include vinyl acetate, styrene, acrylamide, acrylic acid, 2-hydroxyethyl methacrylate, acrylonitrile, 1,3-butadiene, methyl methacrylate, methacrylic acid, maleic acid, itaconic acid, sodium vinyl sulfonate, sodium allyl sulfonate, sodium methyl allyl sulfonate, sodium phenyl allyl ether sulfonate, sodium phenyl methallyl ether sulfonate, 2-acrylamido-methylpropane sulfonic acid (AMP), vinylidene chloride, vinyl chloride, vinylamine, and various acrylate esters.
[0165] In one embodiment, the water-soluble hydroxyl polymer is selected from the group consisting of polyvinyl alcohol, hydroxymethylcellulose, hydroxyethylcellulose, hydroxypropylmethylcellulose, carboxymethylcellulose, and mixtures thereof. Non-limiting examples of suitable polyvinyl alcohols include those available under the trade name CELVOL® from Sekisui Specialty Chemicals America, LLC (Dallas, TX). Other non-limiting examples of suitable polyvinyl alcohols include G Polymer available from Nippon Ghosei. Non-limiting examples of suitable hydroxypropylmethylcelluloses include those available under the trade name METHOCEL® from Dow Chemical Company (Midland, MI), including combinations with the above polyvinyl alcohols.
[0166] b. Water-Soluble Thermoplastic Polymers - Non-limiting examples of suitable water-soluble thermoplastic polymers include thermoplastic starch and / or starch derivatives, polylactic acid, polyhydroxyalkanoates, polycaprolactones, polyesteramides, and certain polyesters, and mixtures thereof.
[0167] The water-soluble thermoplastic polymers of the present disclosure may be hydrophilic or hydrophobic. The water-soluble thermoplastic polymers may be surface and / or internally treated to alter the inherent hydrophilicity or hydrophobicity of the thermoplastic polymer.
[0168] The water soluble thermoplastic polymer may include a biodegradable polymer.
[0169] Any suitable weight average molecular weight for the thermoplastic polymer may be used. For example, the weight average molecular weight of the thermoplastic polymer according to the present disclosure is greater than about 10,000 g / mol, and / or greater than about 40,000 g / mol, and / or greater than about 50,000 g / mol, and / or less than about 500,000 g / mol, and / or less than about 400,000 g / mol, and / or less than about 200,000 g / mol.
[0170] Active ingredient Active agents are a class of additives designed and intended to provide a benefit to something other than the textile elements and / or particles and / or textile structures themselves, such as, for example, providing a benefit to the environment outside the textile elements and / or particles and / or textile structures. Active agents may be any suitable additive that produces an intended effect under the intended conditions of use of the textile elements. For example, active agents may be selected from the group consisting of: personal cleansing and / or conditioning agents, such as hair care agents (e.g., shampoos and / or hair dyes), hair conditioning agents, skin care agents, sunscreens, and skin conditioning agents; laundry care and / or conditioning agents, such as fabric care agents, fabric conditioning agents, fabric softeners, fabric wrinkle inhibitors, fabric care antistatic agents ... stain removers, soil release agents, dispersants, foam suppressors, foam boosters, defoamers, and fabric refreshing agents; liquid and / or powder dishwashing agents (for hand dishwashing and / or automatic dishwashing), hard surface care and / or conditioning and / or polishing agents; other cleaning and / or conditioning agents, such as antimicrobial, antibacterial, antifungal agents, fabric colorants, fragrances, bleaching agents (e.g., oxygen bleach, hydrogen peroxide, percarbonate bleach, perborate bleach, salt chlorinated bleaching agents), bleach activators, chelating agents, builders, lotions, brighteners, air care agents, carpet care agents, dye transfer inhibitors, clay stain removers, anti-redeposition agents, polymeric stain release agents, polymeric dispersants, alkoxylated polyamine polymers, alkoxylated polycarboxylate polymers, amphiphilic graft copolymers, dissolution aids, buffer systems, water softeners, water hardeners, pH adjusters, enzymes, flocculants, foaming agents, preservatives, cosmetic agents, make-up removers, foaming agents, adhesion agents Auxiliaries, coacervate formers, clays, thickeners, latex, silica, drying agents, odor control agents, antiperspirants, cooling agents, warming agents, absorbent gelling agents, anti-inflammatory agents, dyes, pigments, acids, and bases; liquid treatment actives; agricultural actives; industrial actives; ingestible actives, such as pharmaceutical agents, dental whitening agents, tooth care agents, mouthwashes, periodontal and gingival care agents, edible agents, edible agents, vitamins, minerals; water treatment agents, such as water clarifiers and / or disinfectants, and mixtures thereof.
[0171] Non-limiting examples of suitable cosmetic, skin care, skin conditioning, hair care, and hair conditioning agents are described in the CTFA Cosmetic Ingredient Handbook, Second Edition, The Cosmetic, Toiletries, and Fragrance Association, Inc. 1988, 1992.
[0172] One or more chemical classes can be useful for one or more of the active agents listed above.For example, surfactants can be used for any number of the above active agents.Similarly, bleaching agents can be used for fabric care, hard surface cleaning, dishwashing, and even dental whitening.Therefore, those skilled in the art will understand that active agents are selected based on the desired target use of fiber elements and / or particles and / or the fiber structures made therefrom.
[0173] For example, when the fiber elements and / or particles and / or fibrous structures made therefrom are used for hair care and / or conditioning, one or more suitable surfactants, e.g., lathering surfactants, can be selected to provide a desired benefit to the consumer when the fiber elements and / or particles and / or fibrous structures in which the fiber elements and / or particles are incorporated are exposed to the intended conditions of use.
[0174] In one example, when the fibrous elements and / or particles and / or fibrous structures made therefrom are designed or intended for use in washing clothes in a laundry operation, one or more suitable surfactants, and / or enzymes, and / or builders, and / or perfumes, and / or foam suppressors, and / or bleaching agents can be selected to provide a desired benefit to the consumer when the fibrous elements and / or particles and / or fibrous structures in which the fibrous elements and / or particles are incorporated are exposed to the intended conditions of use. In another example, when the fibrous elements and / or particles and / or fibrous structures made therefrom are designed or intended for use in washing clothes in a laundry operation and / or cleaning dishes in a dishwashing operation, the fibrous elements and / or particles and / or fibrous structures can include a laundry detergent composition or a dishwashing detergent composition or an active agent used in such compositions.
[0175] In one embodiment, the active agent includes a non-fragrance active agent. In another embodiment, the active agent includes a non-surfactant. In yet another embodiment, the active agent includes a non-ingestible active agent, i.e., an active agent other than an ingestible active agent.
[0176] Surfactants Non-limiting examples of suitable surfactants include anionic surfactants, cationic surfactants, nonionic surfactants, zwitterionic surfactants, amphoteric surfactants, and mixtures thereof. Co-surfactants may also be included in the fiber elements and / or particles. For fiber elements and / or particles designed for use as laundry detergents and / or dishwashing agents, the total concentration of surfactants should be sufficient to provide cleaning, including stain and / or odor removal, and generally ranges from about 0.5% to about 95%. Furthermore, surfactant systems including two or more surfactants designed for use in fiber elements and / or particles for laundry detergents and / or dishwashing agents may include an all-anionic surfactant system, a mixture surfactant system including a mixture of anionic and nonionic surfactants, or a mixture of nonionic-cationic surfactants or a low foaming nonionic surfactant. In certain examples, the surfactant included in the fiber elements (e.g., filaments) may be different from the surfactant included in the particles.
[0177] The surfactants described herein may be linear or branched. In one example, suitable linear surfactants include those derived from agrochemical oils, such as coconut oil, palm kernel oil, soybean oil, or other vegetable-based oils.
[0178] a. Anionic surfactants Non-limiting examples of suitable anionic surfactants include alkyl sulfates, alkyl ether sulfates, branched alkyl sulfates, branched alkyl alkoxylates, branched alkoxylate sulfates, mid-chain branched alkyl aryl sulfonates, sulfated monoglycerides, sulfonated olefins, alkyl aryl sulfonates, primary or secondary alkane sulfonates, alkyl sulfosuccinates, acyltaurates, acyl isethionates, alkyl glyceryl ether sulfonates, sulfonated methyl esters, sulfonated fatty acids, alkyl phosphates, acyl glutamates, acyl sarcosinates, alkyl sulfoacetates, acylated peptides, alkyl ether carboxylates, acyl lactylates, anionic fluorosurfactants, sodium lauroyl glutamate, and combinations thereof.
[0179] Suitable alkyl sulfates and alkyl ether sulfates for use herein include those having the corresponding formula ROSO3M and RO(C2H4O) x Included are materials having the formula SO3M, where R is an alkyl or alkenyl of about 8 to about 24 carbon atoms, x is 1 to 10, and M is a water-soluble cation, such as ammonium, sodium, potassium, and triethanolamine. Other suitable anionic surfactants are described in McCutcheon's Detergents and Emulsifiers, North American Edition (1986), Allured Publishing Corp. and McCutcheon's, Functional Materials, North American Edition (1992), Allured Publishing Corp.
[0180] In one embodiment, anionic surfactants useful in the fibrous elements and / or particles of the present disclosure include C9 to C 15 Alkylbenzene sulfonate (LAS), C8~C 20 Alkyl ether sulfates, such as alkyl poly(ethoxy) sulfates, C8-C20 Other anionic surfactants include methyl ester sulfonates (MES), secondary alkane sulfonates, methyl ester ethoxylates (MEE), sulfonated estolides, and mixtures thereof.
[0181] In another embodiment, the anionic surfactant is 11 ~C 18 Alkylbenzene sulfonates ("LAS") and primary branched and random C 10 ~C 20 Alkyl sulfate ("AS"), formula CH3(CH2) x (CHOSO3 - M + )CH3 and CH3(CH2) y (CHOSO3 -+ )CH2CH3, where x and (y+1) are integers of at least about 7, preferably at least about 9, and M is a water-soluble cation, particularly an unsaturated sulfate such as oleyl sulfate. 10 ~C 18 Secondary (2,3) alkyl sulfate, C 10 ~C 18 α-Sulfonated fatty acid ester, C 10 ~C 18 Sulfated alkyl polyglycosides, C 10 ~C 18 Alkyl alkoxy sulfate (AE x S"), where x is 1 to 30, and C 10 ~C 18 Alkyl alkoxycarboxylates include, for example, mid-chain branched alkyl sulfates containing 1 to 5 ethoxy units as described in U.S. Pat. Nos. 6,020,303 and 6,060,443; mid-chain branched alkyl alkoxy sulfates as described in U.S. Pat. Nos. 6,008,181 and 6,020,303; modified alkylbenzene sulfonates (MLAS) as described in WO 99 / 05243, WO 99 / 05242, and WO 99 / 05244; methyl ester sulfonates (MES); and alpha-olefin sulfonates (AOS).
[0182] b. Cationic surfactants Non-limiting examples of suitable cationic surfactants include those having the following formula (I):
[0183] [ka] In the formula, R 1 , R 2 , R 3 , and R 4 are each independently selected from (a) an aliphatic group of 1 to 26 carbon atoms, or (b) an aromatic, alkoxy, polyoxyalkylene, alkylcarboxy, alkylamido, hydroxyalkyl, aryl, or alkylaryl group containing up to 22 carbon atoms, and X is a salt-forming anion, such as a halogen radical (e.g., chloride, bromide), acetate radical, citrate radical, lactate radical, glycolate radical, phosphate radical, nitrate radical, sulfate radical, and alkylsulfate radical. In one embodiment, the alkylsulfate radical is methosulfate and / or ethosulfate.
[0184] Suitable quaternary ammonium cationic surfactants of general formula (I) include cetyltrimethylammonium chloride, behenyltrimethylammonium chloride (BTAC), stearyltrimethylammonium chloride, cetylpyridinium chloride, octadecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, octyldimethylbenzylammonium chloride, decyldimethylbenzylammonium chloride, stearyldimethylbenzylammonium chloride, didodecyldimethylammonium chloride, didecyldimethylammonium chloride, dioctadecyldimethylammonium chloride. , distearyl dimethyl ammonium chloride, tallow trimethyl ammonium chloride, coco trimethyl ammonium chloride, 2-ethylhexylstearyl dimethyl ammonium chloride, dipalmitoyl ethyl dimethyl ammonium chloride, ditallowoyl ethyl dimethyl ammonium chloride, distearoyl dimethyl ammonium methosulfate, PEG-2 oleyl ammonium chloride, and salts thereof, where the chloride is replaced by a halogen (e.g., bromine), acetate, citrate, lactate, glycolate, phosphate nitrate, sulfate, or alkyl sulfate.
[0185] Non-limiting examples of suitable cationic surfactants are commercially available from Akzo Nobel Surfactants (Chicago, IL) under the trade name ARQUAD®.
[0186] In one embodiment, suitable cationic surfactants include, for example, quaternary ammonium surfactants having up to 26 carbon atoms, such as: alkoxylate quaternary ammonium (AQA) surfactants, such as those described in U.S. Pat. No. 6,136,769; dimethylhydroxyethyl quaternary ammonium, such as those described in U.S. Pat. No. 6,004,922; dimethylhydroxyethyl lauryl ammonium chloride, such as those described in WO 98 / 35002, WO 98 / 35003, WO 98 / 35004, WO 98 / 35005, WO 98 / 35006, WO 98 / 35007, WO 98 / 35009, WO 98 / 35010, WO 98 / 35011, WO 98 / 35012, WO 98 / 35013, WO 98 / 35014, WO 98 / 35015, WO 98 / 35016, WO 98 / 35017, WO 98 / 35018, WO 98 / 35019 ... Nos. 3,5004, 3,5005, and 3,5006; cationic ester surfactants as described in U.S. Pat. Nos. 4,228,042, 4,239,660, 4,260,529, and 6,022,844; and amino surfactants such as amidopropyldimethylamine (APA), as described in U.S. Pat. No. 6,221,825 and WO 00 / 47708.
[0187] In one embodiment, the cationic ester surfactant is hydrolyzable under laundry wash conditions.
[0188] C. Nonionic surfactants Non-limiting examples of suitable nonionic surfactants include alkoxylated alcohols (AE) and alkylphenols, polyhydroxy fatty acid amides (PFAA), alkyl polyglycosides (APG), C 10 ~C 18 glycerol ether and the like.
[0189] In one embodiment, non-limiting examples of non-ionic detersive surfactants useful in the present disclosure include: 12 ~C 18 Alkyl ethoxylates (such as NEODOL® nonionic surfactants (Shell)); C6-C 12 Alkylphenol alkoxylates (where the alkoxylate units are a mixture of ethyleneoxy and propyleneoxy units); C with ethylene oxide / propylene oxide blocked alkylphenol ethoxylates12 ~C 18 Alcohol condensation products and C6-C 12 Condensates (such as PLURONIC® (BASF)); C 14 ~C 22 Mid-chain branched alcohols (BA); C as discussed in U.S. Pat. No. 6,153,577, U.S. Pat. No. 6,020,303 and U.S. Pat. No. 6,093,856 14 ~C 22 Medium Chain Branched Alkyl Alkoxylates, BAE x (where x is 1 to 30); the alkyl polysaccharides described in Llenado No. 4,565,647, issued Jan. 26, 1986; in particular the alkyl polyglycosides described in Llenado Nos. 4,483,780 and 4,483,779; the polyhydroxy detergent acid amides described in Llenado No. 5,332,528; and the ether-capped poly(oxyalkylated) alcohol surfactants described in Llenado No. 6,482,994 and WO 01 / 42408.
[0190] An example of a commercially available non-ionic surfactant suitable for the present disclosure is Tergitol® 15-S-9 (C 11 ~C 15 (Condensation product of linear alcohol with 9 moles of ethylene oxide) and Tergitol® 24-L-6NMW (6 moles of ethylene oxide with narrow molecular weight distribution and C 12 ~C 14 Condensation products of primary alcohols) (both sold by Dow Chemical Company); Neodol® 45-9 (C 14 ~C 15 Condensation product of linear alcohol with 9 moles of ethylene oxide), Neodol® 23-3 (C 12 ~C 13 Condensation product of 3 moles of linear alcohol with ethylene oxide), Neodol® 45-7 (C 14 ~C 15 Condensation product of linear alcohol with 7 moles of ethylene oxide), Neodol® 45-5 (C14 ~C 15 Condensation products of linear alcohols with 5 moles of ethylene oxide (sold by Shell Chemical Company); Kyro® EOB (C 13 ~C 15 (condensation product of alcohol with 9 moles of ethylene oxide) (sold by The Procter & Gamble Company); and Genapol LA O3O or O5O (C 12 ~C 14 Condensation products of alcohols with 3 or 5 moles of ethylene oxide (sold by Clariant). The nonionic surfactants may exhibit an HLB ranging from about 8 to about 17, and / or from about 8 to about 14. Condensates with propylene oxide and / or butylene oxide may also be used.
[0191] Polyethylene, polypropylene, and polybutylene oxide condensates of alkylphenols are also suitable for use as nonionic surfactants in the present disclosure. These compounds include the condensation products of alkylphenols having alkyl groups containing from about 6 to about 14 carbon atoms in either a linear or branched configuration with an alkylene oxide. Commercially available nonionic surfactants of this type include Igepal® CO-630 (available from GAF Corporation), and Triton® X-45, X-114, X-100, and X-102 (all available from Dow Chemical Company).
[0192] In automatic dishwashing applications, low foaming nonionic surfactants may be used. Suitable low foaming nonionic surfactants are disclosed in U.S. Patent No. 7,271,138, column 7, line 10 to column 7, line 60.
[0193] Examples of other suitable non-ionic surfactants are the commercially available Pluronic® surfactants (sold by BASF), the commercially available Tetronic® compounds (sold by BASF), and the commercially available Plurafac® surfactants (sold by BASF).
[0194] D. Zwitterionic surfactants Non-limiting examples of zwitterionic or amphoteric surfactants include derivatives of secondary and tertiary amines, derivatives of heterocyclic secondary and tertiary amines, or derivatives of quaternary ammonium, quaternary phosphonium, or tertiary sulfonium compounds. For examples of zwitterionic surfactants, see U.S. Pat. No. 3,929,678, column 19, line 38 to column 22, line 48; betaines, including alkyl dimethyl betaines and cocodimethylamidopropyl betaines, C8-C 18 (For example, C 12 ~C 18 ) amine oxides, and sulfo and hydroxy betaines such as N-alkyl-N,N-dimethylamino-1-propanesulfonates (wherein the alkyl group is C8 to C 18 In particular embodiments, C 10 ~C 14 (It can be said that.)
[0195] e. Amphoteric surfactants Non-limiting examples of amphoteric surfactants include aliphatic derivatives of secondary or tertiary amines, or aliphatic derivatives of heterocyclic secondary and tricyclic amines, where the aliphatic radicals can be linear or branched, and mixtures thereof. One of the aliphatic substituents may contain at least about 8 carbon atoms, such as from about 8 to about 18 carbon atoms, and at least one contains an anionic water-solubilizing group, such as carboxy, sulfonate, sulfate. For suitable examples of amphoteric surfactants, see U.S. Pat. No. 3,929,678, column 19, lines 18-35.
[0196] fragrance One or more perfumes and / or perfume ingredients, such as harmonisers and / or notes, may be incorporated into one or more filaments and / or particles of the present disclosure. The perfume may include a perfume ingredient selected from the group consisting of an aldehyde perfume ingredient, a ketone perfume ingredient, and mixtures thereof.
[0197] One or more perfumes and / or perfume ingredients may be included in the fiber elements and / or particles of the present disclosure. A wide range of natural and synthetic chemical ingredients useful as perfumes and / or perfume ingredients include, but are not limited to, aldehydes, ketones, esters, and mixtures thereof. Also included are various natural extracts and essences that may include complex mixtures of ingredients such as orange oil, lemon oil, rose extract, lavender, musk, patchouli, balsam extract, sandalwood oil, pine oil, cedar, and the like. The final perfume may include very complex mixtures of such ingredients. In one embodiment, the final perfume typically comprises from about 0.01% to about 10%, and / or from about 0.01% to about 8%, and / or from about 0.01% to about 6%, and / or from about 0.01% to about 4%, and / or from about 0.01% to about 2%, and / or from about 0.05% to about 2% by weight based on the dry fiber elements, and / or on the dry particles, and / or on the dry fiber structure.
[0198] fragrance delivery system Certain perfume delivery systems, methods of making certain perfume delivery systems, and uses of such perfume delivery systems are disclosed in U.S. Patent Application Publication No. 2007 / 0275866(A1). Non-limiting examples of perfume delivery systems include the following: I. Polymer Assisted Delivery (PAD): This perfume delivery technology uses polymeric materials to deliver perfume substances. Some examples are classical coacervation, water soluble or partially water soluble to water insoluble charged or neutral polymers, liquid crystals, hot melts, hydrogels, perfumed plastics, microcapsules, nano- and microlatexes, polymeric film formers, and polymeric absorbents, adsorbents, etc. PADs include, but are not limited to: a.) Matrix systems: the fragrance is dissolved or dispersed in a polymer matrix or particle. For example, the fragrance may be 1) dispersed in the polymer before incorporation into the product, or 2) added separately from the polymer during or after product incorporation. Although diffusion of the fragrance from the polymer is a common trigger to release or increase the release rate of fragrance from a polymer matrix system attached or applied to a desired surface (site), many other triggers are known to control the release of fragrance. Absorption and / or adsorption into or on top of polymer particles, films, solutions, etc. are aspects of this technology. Nano- or microparticles made of organic materials (e.g., latex) are examples. Suitable particles include, but are not limited to, a wide variety of materials such as polyacetals, polyacrylates, polyacrylic acids, polyacrylonitriles, polyamides, polyaryletherketones, polybutadienes, polybutylenes, polybutylene terephthalates, polychloroprenes, polyethylenes, polyethylene terephthalates, polycyclohexylene dimethylene terephthalates, polycarbonates, polychloroprenes, polyhydroxyalkanoates, polyketones, polyesters, polyethylenes, polyetherimides, polyethersulfones, polyethylene chlorinates, polyimides, polyisoprenes, polylactic acids, polymethylpentenes, polyphenylene oxides, polyphenylene sulfides, polyphthalamides, polypropylenes, polystyrenes, polysulfones, polyvinyl acetates, polyvinyl chlorides, and polymers or copolymers based on acrylonitrile-butadiene, cellulose acetate, ethylene-vinyl acetate, ethylene vinyl alcohol, styrene-butadiene, vinyl acetate-ethylene, and mixtures thereof.
[0199] "Standard" systems refer to systems that are "preloaded" with the intention of retaining the preloaded perfume bound to the polymer until the moment of perfume release. Such polymers suppress the odor of the neat product and may also provide perfume bloom and / or persistence effects depending on the rate of perfume release. One of the challenges with such systems is to achieve an ideal balance between 1) in-product stability (keeping the perfume inside the carrier until needed) and 2) timely release (at the time of use or from the dry site). Achieving such stability is particularly important during product storage and product aging. This challenge is particularly evident in aqueous surfactant-containing products, such as heavy duty liquid laundry detergents. Many available "standard" matrix systems effectively become "equilibrium" systems when formulated into aqueous products. An "equilibrium" or reservoir system can be selected that has acceptable in-product diffusion stability and an available release trigger (e.g., friction). An "equilibrium" system is one in which the perfume and polymer may be added separately to the product, and an equilibrium interaction between the perfume and the polymer triggers the effect at one or more consumer contact points (whereas free perfume control does not have a polymer-assisted delivery technology). The polymer may also be preloaded with perfume. However, some or all of the perfume may diffuse during product storage, reaching an equilibrium state where the desired perfume raw material (PRM) is bound to the polymer. The polymer then delivers the perfume to the surface, where release typically occurs via perfume diffusion. The use of such equilibrium polymers may reduce the intensity of the undiluted odor of the undiluted product (this is especially true for standard systems that are usually preloaded). Such polymer accumulation can "flatten" the release profile and increase persistence. As shown above, such persistence is achieved by suppressing the initial intensity, allowing the formulator to use PRMs with higher impact or lower Odor Threshold (ODT) or lower Kovats Index (KI) to obtain an initial product olfactory effect without being too intense or altered initially. It is important that perfume release occurs within the time frame of application to impact the desired consumer touch point.Suitable microparticles and microlatexes and their manufacturing methods can be found in US Patent Application Publication No. 2005 / 0003980A1. Matrix systems also include hot melt adhesives and perfumed plastics. In addition, hydrophobically modified polysaccharides can be incorporated into perfumed products to increase perfume accumulation and / or modify perfume release. All such matrix systems, including polysaccharides and nanolatexes, can be combined with other PDTs, including other PAD systems, such as PAD reservoir systems, to form perfume microcapsules (PMCs). Polymer-assisted delivery (PAD) matrix systems include those described in the following references: U.S. Patent Application Publication Nos. 2004 / 0110648A1, 2004 / 0092414A1, 2004 / 0091445A1, and 2004 / 0087476A1, and U.S. Patent Nos. 6,531,444, 6,024,943; 6,042,792; 6,051,540; 4,540,721, and 4,973,422.
[0200] Silicone is also an example of a polymer that can be used as a PDT, and can provide a perfume benefit in a manner similar to polymer-assisted delivery "matrix systems". Such PDTs are referred to as silicone-assisted delivery (SAD). Silicone can be preloaded with perfume or used as a balance system as described for PAD. Suitable silicones and their manufacturing methods can be found in International Patent Publication No. 2005 / 102261, US Patent Application Publication No. 20050124530(A1), US Patent Application Publication No. 2005 / 0143282A1, and International Patent Publication No. 2003 / 015736. Functionalized silicones can also be used, as described in US Patent Application Publication No. 2006 / 003913(A1). Examples of silicones include polydimethylsiloxane and polyalkyldimethylsiloxane. Other examples include those with amine functionality that can be used to provide amine-assisted delivery (AAD), and / or polymer-assisted delivery (PAD), and / or amine reaction product (ARP) related benefits. Other such examples can be found in U.S. Patent No. 4,911,852, U.S. Patent Application Publication Nos. 2004 / 0058845(A1), 2004 / 0092425(A1), and 2005 / 0003980(A1).
[0201] b.) Reservoir Systems: Reservoir systems are also known as core / shell technology, i.e., where the perfume is surrounded by a perfume release-controlling membrane that may act as a protective shell. The material inside the microcapsule is referred to as the core, internal phase, or fill, while the wall is sometimes referred to as the shell, coating, or membrane. Microparticles, pressure-sensitive capsules, or microcapsules are examples of this technology. The microcapsules of the present disclosure are formed by a variety of procedures, including, but not limited to, coating, extrusion, spray drying, interfacial polymerization, in-situ polymerization, and matrix polymerization. The shell materials available vary greatly in their stability to water. The most stable are polyoxymethylene urea (PMU)-based materials, which may retain certain PRMs for longer periods in aqueous solutions (or products). Such systems include, but are not limited to, urea-formaldehyde, and / or melamine-formaldehyde. Stable shell materials include water-soluble or water-dispersible acrylic acid alkyl acid copolymers, polyacrylate-based materials obtained as the reaction product of oil-soluble or dispersible amines, multifunctional acrylate or methacrylate monomers or oligomers, oil-soluble acids and initiators in the presence of anionic emulsifiers, including alkali or alkali salts. Gelatin-based microcapsules may be prepared to dissolve quickly or slowly in water, depending on the degree of crosslinking. Many other capsule wall materials are available, which have different degrees of observed perfume diffusion stability. Without being bound by theory, the release rate of perfume from capsules, for example, once attached to a given surface, is usually the inverse of the perfume diffusion stability in the product. For this reason, for example, urea-formaldehyde and melamine-formaldehyde microcapsules usually require a release mechanism other than diffusion (or in addition to diffusion) for perfume release, such as mechanical force (e.g., friction force, pressure, shear stress), which breaks the capsule and increases the release rate of perfume (fragrance). Other triggers include melting, dissolution, hydrolysis or other chemical reactions, electromagnetic radiation, etc. The use of pre-loaded microcapsules requires proper selection of PRM along with the right ratio of in-product stability and on-use and / or on-site release.Urea-formaldehyde and / or melamine-formaldehyde based microcapsules are relatively stable, especially in aqueous solutions close to neutral. These materials may require a friction trigger, which is not applicable to all product applications. Other microcapsule materials (e.g., gelatin) may be unstable in aqueous products and may become less effective (compared to free fragrance control) after product aging. Scratch-and-sniff technology is yet another example of a PAD. Perfume microcapsules (PMCs) may include those described in the following references: U.S. Patent Application Publication No. 2003 / 0125222(A1); U.S. Patent Application Publication No. 2003 / 215417A1, U.S. Patent Application Publication No. 2003 / 216488A1, U.S. Patent Application Publication No. 2003 / 158344A1, U.S. Patent Application Publication No. 2003 / 165692A1, U.S. Patent Application Publication No. 2004 / 0125222(A1); 71742A1, 2004 / 071746A1, 2004 / 072719A1, 2004 / 072720A1, 2006 / 00 No. 39934(A1); No. 2003 / 203829A1, No. 2003 / 195133A1, No. 2004 / 087477A1, No. 2004 / 0 106536(A1), and U.S. Patent Nos. 6,645,479(B1); 6,200,949(B1); 4,882,220; 4,917,920; 4,514,461; 6,106,875 and 4,234,627, 3,594,328, and U.S. Reissue Nos. Examples of such compounds include those described in Japanese Patent No. 32713, International Publication Nos. 2009 / 134234(A1), 2006 / 127454(A2), 2010 / 079466(A2), 2010 / 079467(A2), 2010 / 079468(A2), and 2010 / 084480(A2).
[0202] II. Molecularly Assisted Delivery (MAD): Non-polymeric materials or molecules may also function to enhance perfume delivery. Without being bound by theory, perfumes may interact non-covalently with organic substances, leading to abnormal accumulation and / or release of perfume. Non-limiting examples of such organic substances include, but are not limited to, organic oils, waxes, mineral oils, petrolatum, hydrophobic substances such as fatty acids or esters, sugars, surfactants, liposomes, and even other perfume raw materials (perfume oils), as well as natural oils such as body oils and / or other soils. Perfume fixatives are yet another example. In one embodiment, the non-polymeric materials or molecules have a CLogP value greater than about 2. Molecularly Assisted Delivery (MAD) also includes those described in U.S. Patent Nos. 7,119,060 and 5,506,201.
[0203] III. Fiber-Assisted Delivery (FAD): The selection or use of the site may itself function to improve the delivery of perfume. In fact, the site itself may be a perfume delivery technology. For example, different types of fabrics, such as cotton or polyester, have different properties with respect to their ability to attract and / or retain and / or release perfume. The amount of perfume deposited on or in the fiber may vary depending on the selection of the fiber, as well as on the history or treatment of the fiber, and on any fiber coatings or treatments. The fibers may be woven or nonwoven, natural or synthetic. Natural fibers include those produced by plants, animals, and geological processes, including, but not limited to, cotton, linen, jute, flax, ramie, sisal, and fibers used in the manufacture of paper and clothing. Fiber-assisted delivery may consist of the use of wood fibers, such as thermomechanical pulp, bleached or unbleached kraft, or sulfite pulp. Animal fibers are primarily composed of certain proteins, such as silk, feathers, tendons, intestines, and hair (such as wool). Polymeric fibers based on synthetic chemicals include, but are not limited to, polyamide nylon, PET or PBT polyester, phenol-formaldehyde (PF), polyvinyl alcohol fibers (PVOH), polyvinyl chloride fibers (PVC), polyolefins (PP and PE), and acrylic polymers. All of these fibers can be preloaded with perfume and then added to a product that may or may not contain free perfume and / or one or more perfume delivery technologies. In one embodiment, the fibers may be loaded with perfume by adding the fibers to the product before loading with perfume, and then adding perfume that can diffuse into the fibers to the product. Without being bound by theory, the perfume may be absorbed on the fiber surface or adsorbed inside the fiber during storage of the product, for example, and then released at one or more appropriate times or consumer contact points.
[0204] IV. Amine Assisted Delivery (AAD): Amine assisted delivery technology approach uses materials containing amine groups to enhance perfume deposition or tailor perfume release during product use. This approach does not require precomplexing or prereacting the perfume raw materials with amines prior to addition to the product. In one aspect, amine-containing AAD materials suitable for use herein can be non-aromatic, e.g., polyalkylimines such as polyethyleneimine (PEI) or polyvinylamine (PVAm), or aromatic, e.g., anthranilates. Such materials can be polymeric or non-polymeric. In one aspect, such materials contain at least one primary amine. This technology provides enhanced substantivity and controlled release of low ODT perfume notes (e.g., aldehydes, ketones, enones) through amine functionality, and, without wishing to be bound by theory, further enables delivery of other PRMs through polymer-assisted delivery of polymeric amines. Without this technology, the life span of volatile top notes is very short, resulting in a high ratio of middle and base notes to top notes. The use of polymeric amines allows for more efficient use of top notes and other PRMs, as well as a longer freshness that would otherwise be achieved by using higher concentrations of top notes and other PRMs, so that the undiluted product does not smell too strong as desired. In one embodiment, the AAD system effectively delivers PRMs at a pH higher than near neutral. Without being bound by theory, it is possible that under conditions where more amines are deprotonated in the AAD system, the affinity of the deprotonated amines for PRMs such as aldehydes, including unsaturated ketones and enones such as damascones, and ketones is higher. In another embodiment, the polymeric amine effectively delivers PRMs at a pH lower than near neutral. Without being bound by theory, it is possible that under conditions where more amines are protonated in the AAD system, the affinity of the protonated amines for PRMs such as aldehydes and ketones is lower, resulting in a higher affinity of the polymer backbone for a wider range of PRMs.In such an embodiment, polymer-assisted delivery can deliver more perfume benefits, and such systems are a sub-species of AAD and can be referred to as amine-polymer-assisted delivery or APAD. When APAD is used in compositions with a pH below 7, such APAD systems can also be considered as polymer-assisted delivery (PAD). In yet another embodiment, AAD and PAD systems can interact with other materials, such as anionic surfactants or polymers, to form coacervates and / or coacervate-like systems. In another embodiment, materials containing heteroatoms other than nitrogen, such as sulfur, phosphorus, or selenium, can be used in place of amine compounds. In yet another embodiment, the above-mentioned alternative compounds can be used in combination with amine compounds. In yet another embodiment, a molecule can include an amine moiety and one or more of the alternative heteroatom moieties (e.g., thiols, phosphines, and selenols). Suitable AAD systems and methods for their preparation can be found in U.S. Patent Application Publication Nos. 2005 / 0003980(A1), 2003 / 0199422(A1), 2003 / 0036489(A1), 2004 / 0220074(A1), and U.S. Patent No. 6,103,678.
[0205] V. Cyclodextrin Delivery Systems (CD): This technology approach uses cyclic oligosaccharides or cyclodextrins to enhance perfume delivery. Typically, perfume is complexed with cyclodextrin (CD). Such complexes can be preformed, in situ, or formed on or within the site. Without being bound by theory, loss of water can shift the equilibrium towards the CD-perfume complex, especially if other auxiliary ingredients (e.g. surfactants) are not present in high concentrations to compete with the perfume for the cyclodextrin lumen. A bloom effect can result if water contact or water content increases at a later time. Additionally, cyclodextrins allow the perfume formulator more flexibility in the selection of PRMs. Cyclodextrins can be preloaded with perfume to achieve the desired perfume stability, storage, or release effect, or can be added separately from the perfume. Suitable CDs and methods for their manufacture can be found in U.S. Patent Application Publication Nos. 2005 / 0003980(A1) and 2006 / 0263313(A1), and U.S. Patent Nos. 5,552,378, 3,812,011, 4,317,881, 4,418,144, and 4,378,923.
[0206] VI. Starch Encapsulated Accord (SEA): Starch Encapsulated Accord (SEA) technology can be used to modify the properties of perfume by adding ingredients such as starch to convert liquid perfume to solid. The benefits include improved perfume retention during product storage, especially under non-aqueous conditions. When exposed to moisture, perfume bloom can be induced. Starch allows product formulators to select PRMs or concentrations of PRMs that would not normally be available in the absence of SEA, potentially providing additional benefits at other optimal times. Other examples of technology include the use of other organic and inorganic materials, such as silica, in converting perfume from liquid to solid. Suitable SEAs and methods for their manufacture can be found in U.S. Patent Application Publication No. 2005 / 0003980 (A1) and U.S. Patent No. 6,458,754 (B1).
[0207] VII. Inorganic Carrier Delivery System (ZIC): This technology relates to the use of porous zeolite or other inorganic materials to deliver perfume. Fragrance-loaded zeolite can be used with or without auxiliary components, for example, used to coat fragrance-loaded zeolite (PLZ), to change the perfume release characteristics during storage of the product, or during use, or from the drying site. Suitable zeolites and inorganic carriers, as well as their manufacturing methods, can be found in US Patent Application Publication No. 2005 / 0003980(A1) and US Patent Nos. 5,858,959, 6,245,732(B1), 6,048,830, and 4,539,135. Silica is another form of ZIC. Another example of a suitable inorganic carrier includes inorganic tubules, in which perfume or other active substances are contained within the lumen of the nanotubules or microtubules. In one embodiment, the perfume-loaded inorganic tubules (or perfume-loaded tubules (PLT)) are mineral nano- or microtubules, such as halloysite or a mixture of halloysite and other inorganic materials, such as other clays. PLT technology may also include additional components inside and / or outside the tubules to improve in-product diffusion stability, deposition at the desired site, or to control the release rate of the loaded perfume. The use of monomeric and / or polymeric materials, such as starch encapsulation bodies, allows for coating, plugging, capping, or encapsulation of PLT. Suitable PLT systems and methods for their manufacture can be found in U.S. Pat. No. 5,651,976.
[0208] VIII. Pro-Perfume (PP): This technology refers to perfume technology resulting from reacting perfume materials with other substrates or chemicals to form materials with covalent bonds between one or more PRMs and one or more carriers. PRMs are converted into new materials called pro-PRMs (i.e., pro-perfumes), which can then release the original PRMs when exposed to triggers such as water or light. Pro-perfumes can improve perfume delivery properties to increase perfume deposition, substantivity, stability, and retention. Pro-perfumes can be monomeric (non-polymeric) or polymeric, and can be preformed or formed in situ under equilibrium conditions such as may exist during storage in the product or at wet or dry sites. Non-limiting examples of pro-perfumes include Michael adducts (e.g., β-aminoketones), aromatic or non-aromatic imines (Schiff bases), oxazolidines, β-ketoesters, and orthoesters. Another embodiment includes compounds that contain one or more β-oxy- or β-thio-carbonyl moieties capable of releasing PRMs, such as, for example, α,β-unsaturated ketones, aldehydes, or carboxylic acid esters. A typical trigger for fragrance release is exposure to water, but other triggers may include enzymes, heat, light, pH changes, autoxidation, equilibrium shifts, and changes in concentration or ionic strength. In water-based products, photo-triggered pro-perfumes are particularly suitable. Such photo-pro-perfumes (PPPs) include, but are not limited to, coumarin derivatives, and those that release fragrances and / or pro-perfumes upon triggering. The released pro-perfumes may release one or more PRMs by any of the above triggers. In one embodiment, the photo-pro-perfume releases a nitrogen-based pro-perfume when exposed to light and / or moisture triggers. In another embodiment, the nitrogen-based pro-perfume released from the photo-pro-perfume releases one or more PRMs selected from, for example, aldehydes, ketones (such as enones), and alcohols. In yet another embodiment, the PPP releases a dihydroxycoumarin derivative. The light-triggered pro-perfume may also be an ester that releases a coumarin derivative and a perfume alcohol. In one embodiment, the pro-perfume is a dimethoxybenzoin derivative as described in US Patent Application Publication No. 2006 / 0020459(A1).In another embodiment, the pro-perfume is a 3',5'-dimethoxybenzoin (DMB) derivative that releases alcohol upon exposure to electromagnetic radiation. In yet another embodiment, the pro-perfume releases one or more low ODT PRMs including tertiary alcohols such as linalool, tetrahydrolinalool, or dihydromyrcenol. Suitable professional perfumes and methods for their manufacture are described in U.S. Patent Nos. 7,018,978 (B2); 6,987,084 (B2); 6,956,013 (B2); 6,861,402 (B1); 6,544,945 (B1); 6,093,691; 6,277,796 (B1); 6,165,953; 6,316,397 (B1); 6,437,150 (B1); 6,479,682 (B1); Nos. 96,918, 6,218,355(B1); 6,133,228, 6,147,037, 7,109,153(B2); 7,071,151(B2); 6,987,084(B2); 6,610,646(B2) and 5,958,870, as well as in U.S. Patent Application Publication Nos. 2005 / 0003980(A1) and 2006 / 0223726(A1).
[0209] a.) Amine Reaction Products (ARPs): For purposes of this application, ARPs are a sub-subtype or species of PPs. "Reactive" polymeric amines may be used in which the amine functional group is pre-reacted with one or more PRMs to form the amine reaction products (ARPs). Typically, the reactive amines are primary and / or secondary amines and may be part of a polymer or monomeric (non-polymeric). Such ARPs may also be mixed with additional PRMs to provide polymer-assisted and / or amine-assisted delivery benefits. Non-limiting examples of polymeric amines include polyalkylimines such as polyethyleneimine (PEI) or polymers based on polyvinylamine (PVAm). Non-limiting examples of monomeric (non-polymeric) amines include hydroxylamines (e.g., 2-aminoethanol) and its alkyl-substituted derivatives, and aromatic amines (e.g., anthranilates). ARPs may be pre-mixed with perfume or added separately for leave-on or rinse-off applications. In another embodiment, materials containing heteroatoms other than nitrogen, such as oxygen, sulfur, phosphorus, or selenium, may be used in place of the amine compounds. In yet another embodiment, the above-mentioned alternative compounds can be used in combination with amine compounds.In yet another embodiment, one molecule can include an amine moiety and one or more of alternative heteroatom moieties (e.g., thiol, phosphine and selenol).The effect can include improved perfume delivery as well as controlled release of perfume.Suitable ARPs and their preparation methods can be found in US Patent Application Publication No. 2005 / 0003980(A1) and US Patent No. 6,413,920(B1).
[0210] Antimicrobial, Antibacterial, and Antifungal Agents In some embodiments, pyridinethione particles are suitable antimicrobial actives for use in the present disclosure. In some embodiments, the antidandruff active is a 1-hydroxy-2-pyridinethione salt, in particulate form. In some embodiments, the concentration of pyridinethione particles ranges from about 0.01% to about 5%, or from about 0.1% to about 3%, or from about 0.1% to about 2% by weight of the dry fibrous elements of the fibrous structures of the present disclosure, and / or the dry particles, and / or the dry fibrous structures. In some embodiments, the pyridinethione salt is formed from heavy metals such as zinc, tin, cadmium, magnesium, aluminum, and zirconium, typically zinc, typically the zinc salt of 1-hydroxy-2-pyridinethione (known as "zinc pyridinethione" or "ZPT"), usually in platelet particle form. In some embodiments, the platelet-shaped particle form of 1-hydroxy-2-pyridinethione salt has an average particle size of about 20 micrometers or less, or about 5 micrometers or less, or about 2.5 micrometers or less, as measured according to the median particle size test method described herein.Salts formed from other cations (e.g., sodium) may also be suitable.Pyridinethione active substances are described, for example, in U.S. Patent Nos. 2,809,971, 3,236,733, 3,753,196, 3,761,418, 4,345,080, 4,323,683, 4,379,753, and 4,470,982.
[0211] In another embodiment, the antibacterial agent is selected from triclosan, triclocarban, chlorhexidine, metronidazole, and mixtures thereof.
[0212] In some embodiments, in addition to an antimicrobial active selected from polyvalent metal salts of pyrithione, the composition may further comprise one or more antifungal and / or antibacterial actives. In some embodiments, the antibacterial active is selected from the group consisting of coal tar, sulfur, azoles, selenium sulfide, sulfur particles, keratolytic agents, charcoal, Whitfield's ointment, Castellani ointment, aluminum chloride, gentian violet, octopirox (piroctone olamine), ciclopirox olamine, undecylenic acid and its metal salts, potassium permanganate, selenium sulfide, sodium thiosulfate, propylene glycol, bitter orange oil, urea preparations, griseofulvin, 8-hydroxyquinoline cicloquinol, thiobendazole, thiocarbamates, haloprogin, polyenes, hydroxypyridones, morpholines, benzylamines, allylamines (such as terbinafine), tea tree oil, clove leaf oil, coriander, palmarosa, berberine, thyme red, cinnamon oil, cinnamaldehyde, citronellic acid, hinokitol, ichthyol pale, Sensiva SC-50, Elestab The active ingredient is selected from the group consisting of HP-100, azelaic acid, lyticase, iodopropynyl butylcarbamate (IPBC), isothiazarinones such as octylisothiazarinone, and azoles, and mixtures thereof.
[0213] Bleach The fiber elements and / or particles of the present disclosure may include one or more bleaching agents. Non-limiting examples of suitable bleaching agents include peroxyacids, perborates, percarbonates, chlorine bleaches, oxygen bleaches, hypohalite bleaches, bleach precursors, bleach activators, bleach catalysts, hydrogen peroxide, bleach boosters, photobleaches, bleaching enzymes, free radical initiators, peroxygen bleaches, and mixtures thereof.
[0214] The one or more bleaching agents that may be included in the fibrous elements and / or particles of the present disclosure may be included at a concentration of about 0.05% to about 30% by weight, and / or about 1% to about 20% by weight, based on the dry fibrous elements and / or on the dry particles and / or on the dry fibrous structure. If present, bleach activators may be present in the fibrous elements and / or particles of the present disclosure at a concentration of about 0.1% to about 60% by weight, and / or about 0.5% to about 40% by weight, based on the dry fibrous elements and / or on the dry particles and / or on the dry fibrous structure.
[0215] Non-limiting examples of bleaching agents include oxygen bleaches, perborate bleaches, percarboxylic acid bleaches and their salts, peroxygen bleaches, persulfate bleaches, percarbonate bleaches, and mixtures thereof. Further non-limiting examples of bleaching agents are disclosed in U.S. Pat. No. 4,483,781, U.S. Pat. Application No. 740,446, European Patent Application No. 0133354, U.S. Pat. Nos. 4,412,934, and 4,634,551.
[0216] Non-limiting examples of bleach activators (eg, acyllactam activators) are disclosed in U.S. Patent Nos. 4,915,854, 4,412,934, 4,634,551, and 4,966,723.
[0217] In one embodiment, the bleaching agent may comprise a transition metal bleach catalyst, which may be encapsulated. The transition metal bleach catalyst typically comprises a transition metal ion, for example from a transition metal selected from the group consisting of Mn(II), Mn(III), Mn(IV), Mn(V), Fe(II), Fe(III), Fe(IV), Co(I), Co(II), Co(III), Ni(I), Ni(II), Ni(III), Cu(I), Cu(II), Cu(III), Cr(II), Cr(III), Cr(IV), Cr(V), Cr(VI), V(III), V(IV), V(V), Mo(IV), Mo(V), Mo(VI), W(IV), W(V), W(VI), Pd(II), Ru(II), Ru(III), and Ru(IV). In one embodiment, the transition metal is selected from the group consisting of Mn(II), Mn(III), Mn(IV), Fe(II), Fe(III), Cr(II), Cr(III), Cr(IV), Cr(V), and Cr(VI). The transition metal bleach catalyst typically comprises a ligand, for example a macropolycyclic ligand, such as a bridged macropolycyclic ligand. The transition metal ion may be coordinated to the ligand. Additionally, the ligand may comprise at least four donor atoms, at least two of which are bridgehead donor atoms. Non-limiting examples of suitable transition metal bleach catalysts are described in U.S. Pat. No. 5,580,485; U.S. Pat. No. 4,430,243; U.S. Pat. No. 4,728,455; U.S. Pat. No. 5,246,621; U.S. Pat. No. 5,244,594; U.S. Pat. No. 5,284,944; U.S. Pat. No. 5,194,416; U.S. Pat. No. 5,246,612; U.S. Pat. No. 5,256,779; U.S. Pat. No. 5,280,117; U.S. Pat. No. 5,274,147; U.S. Pat. No. 5,153,161; U.S. Pat. No. 5,227,084; U.S. Pat. No. 5,114,606; U.S. Pat. No. 5,114,611; European Patent No. 549,271(A1); European Patent No. 544,490(A1); European Patent No. 549,272(A1); and European Patent No. 544,440(A2). In one embodiment, suitable transition metal bleach catalysts include manganese-based catalysts, such as those disclosed in U.S. Pat. No. 5,576,282. In another embodiment, suitable cobalt bleach catalysts are described in U.S. Pat. Nos. 5,597,936 and 5,595,967.Such cobalt catalysts are readily made by known procedures, for example, as taught in U.S. Patent Nos. 5,597,936 and 5,595,967. Additionally, suitable transition metal bleach catalysts include transition metal complexes of ligands such as bispidones described in WO 05 / 042532 A1.
[0218] Non-limiting examples of bleach catalysts include catalytic systems that include transition metal cations, such as copper, iron, titanium, ruthenium, tungsten, molybdenum, or manganese cations, with defined bleach catalytic activity, auxiliary metal cations, such as zinc or aluminum cations, with little or no bleach catalytic activity, and sequestering agents, particularly ethylenediaminetetraacetic acid, ethylenediaminetetra(methylenephosphonic acid), and their water-soluble salts, with defined stability constants for the catalyst and auxiliary metal cations. Such catalysts are described in U.S. Pat. No. 4,430,243. Other types of bleach catalysts include manganese-based complexes, as disclosed in U.S. Pat. Nos. 5,246,621 and 5,244,594. Preferred examples of these catalysts include Mn.sup.IV.sub.2(uO).sub.3(1,4,7-trimethyl-1,4,7-triazacyclononane).sub.2-(PF.sub.6).sub.2 ("MnTACN"), Mn.sup.III.sub.2(uO).sub.1(u-OAc).sub.2(1,4,7-trimethyl-1,4,7-triazacyclononane).sub.2-(ClO.sub.4).sub.2, Mn.sup.IV.sub.4(uO).sub.6(1,4,7-triazacyclononane).sub.4-(ClO.sub.4).sub.2, Mn.sup.III.sub.2(uO).sub.1(u-OAc).sub.2(1,4,7-trimethyl-1,4,7-triazacyclononane).sub.2-(ClO.sub.4).sub.2, Mn.sup.IV.sub.4(uO).sub.1(u-OAc).sub.2(1,4,7-trimethyl-1,4,7-triazacyclononane).sub.2-(ClO.sub.4).sub.3, and combinations thereof. See also European Patent Application Publication No. 549,272. Other ligands suitable for use herein include 1,5,9-trimethyl-1,5,9-triazacyclododecane, 2-methyl-1,4,7-triazacyclononane, 2-methyl-1,4,7-triazacyclononane, and mixtures thereof. Bleaching catalysts useful in automatic dishwashing compositions and concentrated powder detergent compositions may be selected as appropriate for the present disclosure. See U.S. Pat. Nos. 4,246,612 and 5,227,084 for examples of suitable bleaching catalysts.See also U.S. Pat. No. 5,194,416, which teaches mononuclear manganese(IV) complexes such as Mn(1,4,7-trimethyl-1,4,7-triazacyclononane)(OCH3).sub.3-(PF.sub.6). Yet another class of bleach catalysts as disclosed in U.S. Pat. No. 5,114,606 are water-soluble complexes of manganese(II), (III), and / or (UV) with ligands that are non-carboxylate polyhydroxy compounds having at least three consecutive C-OH groups. Preferred ligands include sorbitol, iditol, dulcitol, mannitol, xylitol, arabitol, adonitol, metho-erythritol, metho-inositol, lactose, and mixtures thereof. U.S. Pat. No. 5,114,611 teaches bleach catalysts including complexes of transition metals such as Mn, Co, Fe, or Cu with non-(macro)-cyclic ligands. Non-limiting examples of ligands include pyridine, pyridazine, pyrimidine, pyrazine, imidazole, pyrazole, and triazole rings. In one embodiment, the ligand is 2,2'-bispyridylamine. In one embodiment, the bleach catalyst includes Co, Cu, Mn, Fe, -bispyridylmethane and bispyridylamine complexes such as Co(2,2'-bispyridylamine)Cl2, di(isothiocyanato)bispyridylamine-cobalt(II), trisdipyridylamine-cobalt(II) perchlorate, Co(2,2-bispyridylamine)2O2ClO4, bis-(2,2'-bispyridylamine)copper(II) perchlorate, tris(di-2-pyridylamine)iron(II) perchlorate, and mixtures thereof. Other examples of bleach catalysts include Mn gluconate, Mn(CF3SO3)2, Co(NH3)5Cl, and N4Mn(III)(uO)2Mn(IV)N4). + and dinuclear Mn complexed with N-tetradentate and N-bidentate ligands, including [Bipy2Mn(III)(uO)2Mn(IV)bipy2]-(ClO4)3.
[0219] The bleach catalyst may also be prepared by combining a water-soluble ligand with a water-soluble manganese salt in an aqueous medium and concentrating the resulting mixture by evaporation. Any convenient water-soluble salt of manganese may be used herein. Manganese (II), (III), (IV) and / or (V) are readily available on a commercial scale. In some cases, sufficient manganese may be present in the wash liquor, but generally it is preferred that the Mn cation of the detergent composition be present in the composition so that it is present in a catalytically effective amount. Thus, a sodium salt of a ligand and a member selected from the group consisting of MnSO.sub.4, Mn(ClO.sub.4).sub.2 or MnCl.sub.2 is dissolved in water in a molar ratio of ligand:Mn ranging from about 1:4 to 4:1. The water may first be deoxygenated by boiling and cooled by sparging with nitrogen. The resulting solution is evaporated (under N.sub.2 if desired) and the resulting solid is used in the bleaching and detergent compositions herein without further purification.
[0220] In an alternative mode, a water-soluble manganese source such as MnSO4 is added to the bleach / cleaning composition or to an aqueous bleach / cleaning bath containing the ligand. Some species of complex are apparently formed in situ to ensure improved bleaching performance. In such an in situ process, it is advantageous to use a significant molar excess of the ligand over manganese, with ligand:Mn typically being between 3:1 and 15:1. Additional ligands are also available to scavenge labile metal ions such as iron and copper, thereby protecting the bleach from degradation. One possible such system is described in EP 549,271.
[0221] Although the structures of the bleach catalytic manganese complexes useful in the present disclosure have not been elucidated, they may be assumed to include chelates or other hydrated coordination complexes resulting from the interaction of the carboxyl and nitrogen atoms of the ligand with the manganese cation. Similarly, the oxidation state of the manganese cation during the catalytic process is not known with certainty and may be in the (+II), (+III), (+IV) or (+V) valence state. Due to the six possible points of binding of the ligand to the manganese cation, it may be reasonably assumed that polynuclear species and / or "cage" structures may exist in the aqueous bleaching medium. The actual activity present
[0222]
number
[0223] Other bleach catalysts are described, for example, in EP 408,131 (cobalt complex catalysts), EP 384,503 and EP 306,089 (metalloporphyrin catalysts), U.S. Pat. No. 4,728,455 (manganese / multidentate ligand catalysts), EP 4,711,748 and EP 224,952 (manganese absorbed on aluminosilicate catalysts), U.S. Pat. No. 4,601,845 (aluminosilicate catalysts containing manganese and zinc or magnesium salts), and U.S. Pat. No. 4,119,557 (ferric complex catalysts), German Patent Specification No. 2,054,019 (cobalt chelate catalysts), Canadian Patent No. 866,191 (transition metal containing salts), U.S. Pat. No. 4,430,243 (chelating agents having manganese cations and non-catalytic metal cations), and U.S. Pat. No. 4,728,455 (manganese gluconate catalysts).
[0224] In one embodiment, the bleach catalyst comprises a cobalt pentaamine chloride salt having the formula [Co(NH.sub.3).sub.5Cl]Y.sub.y, particularly [Co(NH.sub.3).sub.5Cl]CI.sub.2. Other cobalt bleach catalysts useful herein are described, for example, in M. L. Tobe, "Base Hydrolysis of Transition-Metal Complexes", Adv. Inorg. Bioinorg. Mech., (1983), 2, pp. 1-94. For example, Table 1 on page 17 lists:
[0225]
number
[0226] These bleach catalysts may be readily prepared by known procedures, such as those described in the Tobe article herein and the references cited therein, U.S. Pat. No. 4,810,410 (Diakun et al., issued March 7, 1989); J. Chem. Ed. (1989), 66(12), 1043-45; The Synthesis and Characterization of Inorganic Compounds, W. L. Jolly Prentice-Hall; 1970), pp. 461-3; Inorg. Chem., 18, 1497-1502 (1979); Inorg. Chem., 21, 2881-2885 (1982); Inorg. Chem., 18, 2023-2025 (1979); Inorg. Synthesis, 173-176 (1960); and Journal of Physical Chemistry 56, 22-25 (1952). These bleaching catalysts may also be co-processed with adjunct materials to reduce color impact if desired for product aesthetics, or may be included in enzyme-containing particles as exemplified below, or compositions may be manufactured to contain catalyst "speckles."
[0227] Bleaching agents other than oxygen bleaches are also known in the art and can be used herein (e.g., photoactivated bleaches such as sulfonated zinc and / or aluminum phthalocyanines (U.S. Pat. No. 4,033,718, incorporated herein by reference), and / or preformed organic peracids such as peroxycarboxylic acids or salts thereof, and / or peroxysulfonic acids or salts thereof). In one example, a suitable organic peracid includes phthaloyl imidoperoxycaproic acid or salts thereof. When present, a photoactivated bleach initiator (e.g., sulfonated zinc phthalocyanine) may be present in the fibrous elements, and / or particles, and / or fibrous structures of the present disclosure at a concentration of about 0.025% to about 1.25% by weight, based on the dry fibrous elements, and / or dry particles, and / or dry fibrous structures.
[0228] Non-limiting examples of bleach activators are selected from the group consisting of tetraacetylethylenediamine (TAED), benzoylcaprolactam (BzCL), 4-nitrobenzoylcaprolactam, 3-chlorobenzoylcaprolactam, benzoyloxybenzenesulfonate (BOBS), nonanoyloxybenzenesulfonate (NOBS), phenylbenzoate (PhBz), decanoyloxybenzenesulfonate (C.sub.10-OBS), benzoylvalerolactam (BZVL), octanoyloxybenzenesulfonate (C.sub.8-OBS), perhydrolyzable esters, and mixtures thereof, most preferably benzoylcaprolactam and benzoylvalerolactam. Particularly preferred bleach activators in the pH range of about 8 to about 9.5 are selected from those having OBS or VL leaving groups. Quaternary substituted bleach activators (quaternary substituted bleach activators (QSBA) or quaternary substituted peracids (QSP)) may also be included.
[0229] Non-limiting examples of organic peroxides, particularly diacyl peroxides, are described extensively in Kirk Othmer, Encyclopedia of Chemical Technology, Vol. 17, John Wiley and Sons, 1982, pages 27-90, especially pages 63-72, all of which are incorporated herein by reference. If a diacyl peroxide is used, it may be one that minimizes adverse effects on spotting / filming.
[0230] Dye transfer inhibitor The fiber elements and / or particles of the present disclosure may include one or more dye transfer inhibitors. Suitable polymeric dye transfer inhibitors include, but are not limited to, polyvinylpyrrolidone polymers, polyamine N-oxide polymers, copolymers of N-vinylpyrrolidone and N-vinylimidazole, polyvinyloxazolidones, and polyvinylimidazoles, or mixtures thereof. The dye transfer inhibitors may be present in the fiber elements and / or particles and / or fiber structure products of the present disclosure at a concentration of about 0.0001% to about 10%, about 0.01% to about 5%, or even about 0.1% to about 3% by weight based on the dry fiber elements and / or dry particles and / or dry fiber structure.
[0231] Whitening Agent The fibrous elements and / or particles of the present disclosure may include active agents such as whitening agents, for example optical brighteners, which may impart color to the article being washed.
[0232] The fiber elements and / or particles may include CI optical brightener 260 in the α-crystalline form having the following structure:
[0233] [ka]
[0234] In one embodiment, the brightener is a cold water soluble brightener such as CI Optical Brightener 260 in its α-crystalline form.
[0235] In one embodiment, the brightener is predominantly in the α-crystalline form, which typically means that at least 50%, at least 75%, at least 90%, at least 99% or even substantially all of the CI optical brightener 260 by weight is in the α-crystalline form.
[0236] The whitening agent may typically be in finely divided particulate form having a weight average primary particle size of from 3 to 30 μm, from 3 to 20 μm, or from 3 to 10 μm, as measured in accordance with the Median Particle Size Test Method.
[0237] The composition may include CI optical brightener 260 in the form of beta-crystalline, and the weight ratio of (i) CI optical brightener 260 in the α-crystalline form to (ii) CI optical brightener 260 in the β-crystalline form may be at least 0.1, or at least 0.6.
[0238] BE680847 relates to a process for the manufacture of CI Optical Brightener 260 in its α-crystalline form.
[0239] Commercially available optical brighteners that may be useful in the present disclosure can be divided into subgroups, including, but not necessarily limited to, derivatives of stilbenes, pyrazolines, coumarins, carboxylic acids, methine cyanines, dibenzothiophene-5,5-dioxides, azoles, 5- and 6-membered heterocycles, and various other agents. Examples of such brighteners are disclosed in "The Production and Application of Fluorescent Brightening Agents," M. Zahradnik, published by John Wiley & Sons, (New York) (1982). Specific non-limiting examples of optical brighteners that are useful in the present compositions are those identified in U.S. Pat. Nos. 4,790,856 and 3,646,015.
[0240] Further suitable brighteners have the following structure:
[0241] [ka]
[0242] Suitable optical brightener concentrations include lower limits of about 0.01, about 0.05, about 0.1 or even about 0.2% by weight to upper limits of 0.5 or even 0.75% by weight.
[0243] In one embodiment, the whitening agent may be loaded into the clay to form particles.
[0244] Hueing Agent The composition may include a hueing agent. Suitable hueing agents include dyes, dye-clay complexes, and pigments. Suitable dyes include low molecular weight dyes and polymeric dyes. Suitable small molecule dyes include small molecule dyes selected from the group consisting of dyes classified under the Colour Index (CI) classification of direct blue, direct red, direct violet, acid blue, acid red, acid violet, basic blue, basic violet, and basic red, or mixtures thereof.
[0245] In another embodiment, suitable small molecule dyes include, by Color Index (Society of Dyers and Colourists, Bradford, UK) numbers, Direct Violet 9, Direct Violet 35, Direct Violet 48, Direct Violet 51, Direct Violet 66, Direct Violet 99, Direct Blue 1, Direct Blue 71, Direct Blue 80, Direct Blue 279, Acid Red 17, Acid Red 73, Acid Red 88, Acid Red 150, Acid Violet 15, Acid Violet 17, Acid Violet 24, Acid Violet 43, Acid Red 52, Acid Violet 49, Acid Violet 50, Acid Blue 1 5, Acid Blue 17, Acid Blue 25, Acid Blue 29, Acid Blue 40, Acid Blue 45, Acid Blue 75, Acid Blue 80, Acid Blue 83, Acid Blue 90, and Acid Blue 113, Acid Black 1, Basic Violet 1, Basic Violet 3, Basic Violet 4, Basic Violet 10, Basic Violet 35, Basic Blue 3, Basic Blue 16, Basic Blue 22, Basic Blue 47, Basic Blue 66, Basic Blue 75, Basic Blue 159, and mixtures thereof. In another aspect, suitable small molecule dyes include small molecule dyes selected from the group consisting of the Colour Index (Society of Dyers and Colourists, Bradford, UK) numbers Acid Violet 17, Acid Violet 43, Acid Red 52, Acid Red 73, Acid Red 88, Acid Red 150, Acid Blue 25, Acid Blue 29, Acid Blue 45, Acid Blue 113, Acid Black 1, Direct Blue 1, Direct Blue 71, Direct Violet 51, and mixtures thereof.In another aspect, suitable small molecule dyes include small molecule dyes selected from the group consisting of the Colour Index (Society of Dyers and Colourists, Bradford, UK) numbers Acid Violet 17, Direct Blue 71, Direct Violet 51, Direct Blue 1, Acid Red 88, Acid Red 150, Acid Blue 29, Acid Blue 113, or mixtures thereof.
[0246] Suitable polymeric dyes include polymeric dyes selected from the group consisting of polymers containing conjugated chromogens (dye-polymer conjugates), polymers with chromogens copolymerized into the backbone of the polymer, and mixtures thereof.
[0247] In another embodiment, suitable polymeric dyes include polymeric dyes selected from the group consisting of surface-substantive colorants sold under the name Liquitint® (Milliken, Spartanburg, South Carolina, USA), dye-polymer conjugates formed from at least one reactive dye and a polymer selected from the group consisting of polymers comprising a moiety selected from the group consisting of a hydroxyl moiety, a primary amine moiety, a secondary amine moiety, a thiol moiety, and mixtures thereof. In yet another aspect, suitable polymeric dyes include polymeric dyes selected from the group consisting of Liquitint® (Milliken, Spartanburg, South Carolina, USA) Violet CT, carboxymethylcellulose (CMC) conjugated with reactive blue, reactive violet, or reactive red dyes, e.g., CMC conjugated with CI Reactive Blue 19 sold by Megazyme (Wicklow, Ireland) under the trade name AZO-CM-CELLULOSE, product code S-ACMC, alkoxylated triphenyl-methane polymeric colorants, alkoxylated thiophene polymeric colorants, and mixtures thereof.
[0248] Preferred hueing dyes include the brighteners contained in WO 08 / 87497 A1. These brighteners may be characterized by the following structure (I):
[0249] [ka] wherein R1 and R2 may be independently selected from the following: a) [(CH2CR'HO) x (CH2CR”HO) y H] [Wherein, R' is H, CH3, CH2O(CH2CH2O) z H, and mixtures thereof, R″ is selected from the group consisting of H, CH2O(CH2CH2O) z H, and mixtures thereof, where x+y≦5, y≧1, and z=0-5; b) R1 = alkyl, aryl or arylalkyl, and R2 = [(CH2CR'HO) x (CH2CR”HO) y H] [Wherein, R' is H, CH3, CH2O(CH2CH2O) z H, and mixtures thereof, R″ is selected from the group consisting of H, CH2O(CH2CH2O) z H, and mixtures thereof, wherein x+y≦10, y≧1, and z=0-5; c) R1 = [CH2CH2(OR3)CH2OR4] and R2 = [CH2CH2(OR3)CH2OR4] [Wherein, R3 is H, (CH2CH2O) z H, and mixtures thereof, where z=0-10; R4 is (C1~C 16 ) alkyl groups, aryl groups, and mixtures thereof; d) In the formula, R1 and R2 can be independently selected from the amino addition products of styrene oxide, glycidyl methyl ether, isobutyl glycidyl ether, isopropyl glycidyl ether, t-butyl glycidyl ether, 2-ethylhexyl glycidyl ether, and glycidyl hexadecyl ether with 1 to 10 alkylene oxide units.
[0250] Preferred brighteners of the present disclosure may be characterized by the following structure (II):
[0251] [ka] [Wherein, R' is H, CH3, CH2O(CH2CH2O) z H, and mixtures thereof, R″ is selected from the group consisting of H, CH2O(CH2CH2O) z H, and mixtures thereof, where x+y≦5, y≧1, and z=0-5.
[0252] Further preferred brighteners of the present disclosure may be characterized by the following structure (III):
[0253] [ka]
[0254] This brightener is commonly referred to as "Violet DD". Violet DD is typically a mixture having a total of 5 EO groups. This structure is achieved by the following selection in Structure I of the following pendant groups shown in "part a" above:
[0255] [Table 1]
[0256] Further brightening agents include those described in US Patent Application Publication No. 2008 / 34511(A1) (Unilever). A preferred agent is "Violet 13".
[0257] Suitable dye-clay conjugates include dye-clay conjugates selected from the group consisting of at least one cationic / basic dye and smectite clay, and mixtures thereof. In another embodiment, suitable dye-clay complexes include dye-clay complexes selected from the group consisting of one cationic / basic dye selected from the group consisting of CI Basic Yellow 1-108, CI Basic Orange 1-69, CI Basic Red 1-118, CI Basic Violet 1-51, CI Basic Blue 1-164, CI Basic Green 1-14, CI Basic Brown 1-23, CI Basic Black 1-11, and a clay selected from the group consisting of montmorillonite clay, hectorite clay, saponite clay, and mixtures thereof. In yet another embodiment, suitable dye clay complexes include Montmorillonite Basic Blue B7 CI42595 complex, Montmorillonite Basic Blue B9 CI52015 complex, Montmorillonite Basic Violet V3 CI42555 complex, Montmorillonite Basic Green G1 CI42040 complex, Montmorillonite Basic Red R1 CI45160 complex, Montmorillonite CI Basic Black 2 complex, Hectorite Basic Blue B7 CI42595 complex, Hectorite Basic Blue B9 CI52015 complex, Hectorite Basic Violet V3 CI42555 complex, Hectorite Basic Green G1 CI42040 complex, Hectorite Basic Red R1 CI45160 complex, Hectorite CI Basic Black 2 complex, Saponite Basic Blue B7 CI42595 complex, Saponite Basic Blue B9 CI52015 complex, Saponite Basic Violet V3 CI 42555 Complex, Saponite Basic Green G1 CI 42040 Complex, Saponite Basic Red R1 CI 45160 Complex, Saponite CI Basic Black 2 Complex, and mixtures thereof.
[0258] Suitable pigments include pigments selected from the group consisting of flavanthrone, indanthrone, chlorinated indanthrone containing 1 to 4 chlorine atoms, pyranthrone, dichloropyranthrone, monobromodichloropyranthrone, dibromodichloropyranthrone, tetrabromopyranthrone, perylene-3,4,9,10-tetracarboxylic acid diimide (the imide group may be unsubstituted or substituted by C1-C3-alkyl or phenyl or heterocyclic radicals, the phenyl and heterocyclic radicals may further have substituents that do not impart water solubility), anthrapyrimidine carboxylic acid amide, violanthrone, isoviolanthrone, dioxazine pigments, copper phthalocyanines which may contain up to 2 chlorine atoms per molecule, polychloro- or polybromochloro-copper phthalocyanines containing up to 14 bromine atoms per molecule, and mixtures thereof.
[0259] In another embodiment, suitable pigments include pigments selected from the group consisting of Ultramarine Blue (CI Pigment Blue 29), Ultramarine Violet (CI Pigment Violet 15), and mixtures thereof.
[0260] The aforementioned fabric hueing agents can be used in combination (any mixture of fabric hueing agents can be used). Suitable fabric hueing agents can be purchased from Aldrich (Milwaukee, Wisconsin, USA), Ciba Specialty Chemicals (Basel, Switzerland), BASF (Ludwigshafen, Germany), Dayglo Color Corporation (Mumbai, India), Organic Dyestuffs Corp. (East Providence, Rhode Island, USA), Dystar (Frankfurt, Germany), Lanxess (Leverkusen, Germany), Megazyme (Wicklow, Ireland), Clariant (Muttenz, Switzerland), Avecia (Manchester, UK), and / or can be produced according to the examples contained herein. Suitable hueing agents are described in more detail in U.S. Pat. No. 7,208,459 (B2).
[0261] enzyme One or more enzymes may be present in the fiber elements and / or particles of the present disclosure. Non-limiting examples of suitable enzymes include proteases, amylases, lipases, carbohydrases including mannanases and endoglucanases, pectinases, hemicellulases, peroxidases, xylanases, phospholipases, esterases, cutinases, keratanases, reductases, oxidases, phenoloxidases, lipoxygenases, ligninases, pullulanases, tannases, pentosanases, malanases, glucanases, arabinosidases, hyaluronidases, chondroitinases, laccases, and mixtures thereof.
[0262] Enzymes can be included in the fiber elements and / or particles of the present disclosure for a wide variety of purposes, including, but not limited to, removing protein-based, carbohydrate-based, or triglyceride-based stains from substrates, preventing dye migration from released dyes during fabric laundering, and repairing fabrics. In one embodiment, the fiber elements and / or particles of the present disclosure can include proteases, amylases, lipases, cellulases, peroxidases, and mixtures thereof from any suitable source, such as plants, animals, bacteria, fungi, and yeasts. The choice of enzymes used is influenced by factors such as pH activity and / or stability optimum, thermal stability, and stability to other additives such as active agents (e.g., builders) present in the fiber elements and / or particles. In one embodiment, the enzymes are selected from bacterial enzymes (e.g., bacterial amylases and / or bacterial proteases), fungal enzymes (e.g., fungal cellulases), and mixtures thereof.
[0263] When present in the textile elements and / or particles of the present disclosure, the enzymes may be present in a concentration sufficient to provide a "cleaning effective amount". The term "cleaning effective amount" refers to an amount capable of producing a cleaning, stain removal, soil removal, whitening, deodorizing, or fresh feeling effect on a substrate, such as fabric, dishware, flooring, ceramics, metal surfaces, etc. As a practical matter for current commercial formulations, a typical amount of active enzyme is up to about 5 mg by weight, more typically 0.01 mg to 3 mg, per gram of textile elements and / or particles of the present disclosure. When specifically specified, textile elements and / or particles of the present disclosure typically comprise from about 0.001% to about 5% by weight, and / or from about 0.01% to about 3% by weight, and / or from about 0.01% to about 1% by weight, on a dry textile element basis, and / or on a dry particle basis, and / or on a dry textile structure basis.
[0264] After the fiber elements and / or particles have been produced, one or more enzymes may be applied to the fiber elements and / or particles.
[0265] The range of enzyme materials and means of incorporating them into the filament-forming composition of the present disclosure (which may also be a synthetic detergent composition) are disclosed in WO 9307263(A), WO 9307260(A), WO 8908694(A), U.S. Pat. Nos. 3,553,139, 4,101,457 and 4,507,219.
[0266] Enzyme Stabilization System When enzymes are present in the fiber elements and / or particles of the present disclosure, an enzyme stabilizer system may also be included in the fiber elements and / or particles. The enzymes can be stabilized by various techniques. Non-limiting examples of enzyme stabilization techniques are disclosed and exemplified in U.S. Pat. Nos. 3,600,319 and 3,519,570, European Patent Nos. 199,405 and 200,586, and WO 9401532(A).
[0267] In one embodiment, the enzyme stabilization system may include calcium ions and / or magnesium ions.
[0268] The enzyme stabilization system may be included in the fiber elements and / or particles of the present disclosure at a concentration of about 0.001% to about 10% by weight, and / or about 0.005% to about 8% by weight, and / or about 0.01% to about 6% by weight based on the dry fiber elements and / or on the dry particles and / or on the dry fiber structure. The enzyme stabilization system may be any stabilization system that is compatible with the enzymes present in the fiber elements and / or particles. Such enzyme stabilization systems may be inherently provided by other formulated actives or may be added separately, for example, by the enzyme formulator or manufacturer. Such enzyme stabilization systems may include, for example, calcium ions, magnesium ions, boric acid, propylene glycol, short chain carboxylic acids, boronic acids, and mixtures thereof, and are designed to address different stabilization problems.
[0269] Thermoforming Agent The fibrous elements and / or particles of the present disclosure may include a thermoforming agent. The thermoforming agent is formulated to generate heat in the presence of water and / or oxygen (e.g., oxygen in air, etc.), thereby accelerating the degradation rate of the fibrous structure in the presence of water and / or oxygen and improving the efficiency of one or more active substances in the fibrous elements. Alternatively, the thermoforming agent may be used to accelerate the release rate of one or more active substances from the fibrous structure. The thermoforming agent is formulated to undergo an exothermic reaction when exposed to oxygen (i.e., oxygen in air, oxygen in water, etc.). Many different materials and combinations of materials may be used as thermoforming agents. Non-limiting thermoforming agents that may be used in the fibrous structure include electrolyte salts (e.g., aluminum chloride, calcium chloride, calcium sulfate, cupric chloride, cuprous chloride, ferrous sulfate, magnesium chloride, magnesium sulfate, manganese chloride, manganese sulfate, potassium chloride, potassium sulfate, sodium acetate, sodium chloride, sodium carbonate, potassium sulfate, etc.), glycols (e.g., propylene glycol, dipropylene glycol, etc.), lime (e.g., quicklime, hydrated lime, etc.), metals (e.g., chromium, copper, iron, magnesium, manganese, etc.), metal oxides (e.g., aluminum oxide, iron oxide, etc.), polyalkyleneamines, polyalkyleneimines, polyvinylamines, zeolites, glycerin, 1,3, propanediol, polysorbate esters (e.g., Tweens 20, 60, 85, 80), and / or polyglycerol esters (e.g., Noobe, Drewpol and Drewmulze (Stepan)). Thermoforming agents may be formed from one or more materials. For example, magnesium sulfate alone may form the thermoformer. In another non-limiting example, a combination of about 2-25% by weight of activated carbon, about 30-70% by weight of iron powder, and about 1-10% by weight of a metal salt may form the thermoformer. As will be appreciated, other or additional materials may be used alone or together with other materials to form the thermoformer. Non-limiting examples of materials that may be used to form the thermoformer used in the fibrous structure are disclosed in U.S. Patent Nos. 5,674,270 and 6,020,040, and U.S. Patent Application Publication Nos. 2008 / 0132438 and 2011 / 0301070.
[0270] Decomposition accelerator The fibrous elements and / or particles of the present disclosure may include or contain a degradation accelerator used to accelerate the rate at which the fibrous structure degrades in the presence of water and / or oxygen. When used, the degradation accelerator is generally designed to release a gas when exposed to water and / or oxygen, agitating the area around the fibrous structure and accelerating the degradation or dissolution of the fibrous structure. When used, the degradation accelerator may or alternatively be used to accelerate the release rate of one or more active substances from the fibrous structure, but is not necessarily required. When used, the degradation accelerator may or alternatively be used to improve the efficiency of one or more active substances in the fibrous structure, but is not necessarily required. Degradation accelerators may include one or more substances including, but not limited to, alkali metal carbonates (e.g., sodium carbonate, potassium carbonate, etc.), alkali metal bicarbonates (e.g., sodium bicarbonate, potassium bicarbonate, sodium bicarbonate, etc.), ammonium carbonate, etc. The fibrous structure may optionally include one or more activators used to activate or increase the activation rate of one or more degradation accelerators in the fibrous structure. As can be understood, one or more active agents may be included in the fibrous structure even when the degradation accelerator is not present in the fibrous structure, but this is not necessary. For example, the active agent system may also include an acidic or basic compound that may degrade the accelerator or be used as a supplement to one or more active agents in the fibrous structure if not included in the fibrous structure. If used, non-limiting examples of active agents that may be included in the fibrous structure include organic acids (e.g., hydroxy-carboxylic acids (e.g., citric acid, tartaric acid, malic acid, lactic acid, gluconic acid, etc.), saturated aliphatic carboxylic acids (e.g., acetic acid, succinic acid, etc.), unsaturated aliphatic carboxylic acids (e.g., fumaric acid, etc.). Non-limiting examples of materials that may be used to form the degradation accelerators and active agents used in the fibrous structure are disclosed in U.S. Patent Application Publication No. 2011 / 0301070.
[0271] Foaming Agent The effervescent agent of the present disclosure includes compositions that are foamable. As defined herein, the term "effervescent" refers to any product capable of forming gas bubbles in a liquid environment, and may also be considered as any product capable of liberating carbon dioxide in or from a liquid environment. Similarly, "effervescent" refers to forming gas bubbles in a liquid environment, or liberating carbon dioxide in or from a liquid environment. Alternatively, "effervescent" refers to the fizzing or foaming of an article when it encounters a liquid or aqueous environment. In certain examples, the presence of gas bubbles is due to the formation of carbon dioxide. For example, when added to a liquid such as water, a mixture of at least one acid and at least one salt results in a chemical reaction that liberates carbon dioxide. In one embodiment, both the acid and the salt may be in anhydrous form.
[0272] Suitable acids for use in these exemplary embodiments include, but are not limited to, tartaric acid, citric acid, fumaric acid, adipic acid, malic acid, oxalic acid, or sulfamic acid, either alone or in combination. Typically, the effervescents in these embodiments are prepared from citric acid or a combination of citric acid and tartaric acid. Examples of suitable salts for use in the exemplary embodiments include, but are not limited to, alkali metal salts. Sodium carbonate, calcium carbonate, magnesium carbonate, ammonium carbonate, potassium carbonate, sodium bicarbonate, calcium bicarbonate, and combinations thereof may be used.
[0273] In other embodiments, the selection of the particular acid and / or salt and their ratios will depend, at least in part, on the carbon dioxide emission requirements. In some embodiments, the acid may be added in an amount of about 10% to about 60% by weight of the effervescent component, and the alkali metal salt may be added in an amount of about 10% to about 60% by weight of the effervescent component.
[0274] In one embodiment, the foaming component may comprise from about 0.1% to about 50% by weight, and / or from about 1% to about 40% by weight, and / or from about 5% to about 30% by weight, based on the dry fibrous element basis, and / or on the dry particle basis, and / or on the dry fibrous structure and / or dry article.
[0275] Coolant The purpose of the cooling agent is to provide a perceptible sensation to the user when and / or if a fluid insult is occurring in the textile structure or article, the sensation being the result of an actual temperature drop or a stimulant resulting in the perception of a temperature drop.
[0276] The coolant is in the form of a solid, which may include particles, flakes, fibers, aggregates, granules, powders, spheres, ground materials, and the like, as well as combinations thereof. The solid may have any desired shape, for example, cubic, rod-like, polyhedral, spherical or hemispherical, circular or semicircular, angular, irregular, etc. In one embodiment, the coolant is provided in a particulate form to facilitate processing in the described manner.
[0277] The amount of cooling agent may be expressed in basis weight units. Thus, the basis weight of the cooling active material alone may range from about 5 gsm to about 100 gsm, and / or from about 100 gsm to about 800 gsm, and / or from about 200 gsm to about 600 gsm.
[0278] In one example, the solubility of such coolants upon contact with an aqueous liquid, e.g., water, may be from about 0.01 to about 6 grams of material per gram of water (g / g), and / or from about 0.1 g / g to about 3 g / g.
[0279] The cooling agent responds to contact with the aqueous dissolution solution to provide a cooling effect. In one aspect, the mechanism by which this is achieved is through dissolution of the cooling agent in the aqueous dissolution solution. For example, the cooling agent may comprise particles that have a significant energy difference between the dissolved state and the crystalline state such that energy in the form of heat is absorbed. Alternatively, the cooling agent may comprise particles that provide a sensation of a significant energy difference.
[0280] In one embodiment, the fibrous structure and / or article may suitably provide a temperature change when insulted with an aqueous dissolution liquid of at least about 2°C, and / or at least about 5°C, and / or at least about 10°C, and / or from about 3°C to about 15°C.
[0281] Polyols such as xylitol particles may be selected as cooling agents. Xylitol particles absorb heat when dissolved in aqueous liquid, thus creating a cooling sensation. Alternatively, other polyols such as sorbitol or erythritol may be advantageously selected to provide a cooling sensation. In yet other embodiments, various combinations of the above cooling agents may be used. Suitable polyols are available from Roquette America, Inc. (a company with offices in Keokuk, Iowa, USA) under the trade names XYLISORB (xylitol) or NEOSORB (sorbitol). Such polyols are generally available from manufacturers in specific particle sizes, such as 90 micrometers, 300 micrometers, 500 micrometers, etc., for placement in fibrous webs or articles.
[0282] Other suitable coolants that absorb heat during dissolution include sodium acetate (HO), sodium carbonate (HO), sodium sulfate (HO), sodium thiosulfate (HO), and sodium phosphate (HO); anhydrous salts such as ammonium nitrate, potassium nitrate, ammonium chloride, potassium chloride, and sodium nitrate; organic compounds such as urea, or combinations thereof.
[0283] Additionally, as noted above, in some embodiments, the fibrous web or article desirably provides a surface temperature change when wet of from about 2° C. to about 15° C. To achieve this result, the temperature change material and the amount used should be such that the total energy change possible is from about 1 to about 30 calories per square centimeter (cal / cm 2 ), which is about 1 to about 20 cal / cm 2 and / or about 2 to about 15 cal / cm 2, or about 3 to about 10 cal / cm 2 may represent any of the possible total energy absorptions, such as
[0284] A temperature change agent that absorbs heat upon contact with an aqueous solution desirably has a heat of solution, hydration, or reaction of greater than about 5 cal / g and / or less than about -120 cal / g. The heat of solution, hydration, or reaction is preferably within the range of about 30 to about 90 cal / g, or about -30 to about -90 cal / g, for example, about 30 to about 70 cal / g, or about -30 to about -70 cal / g, such as -32 cal / g for xylitol and -60 cal / g for urea.
[0285] In one embodiment, the cooling agent may comprise from about 0.1% to about 50% by weight, and / or from about 1% to about 40% by weight, and / or from about 5% to about 30% by weight, based on the dry fibrous element basis, and / or on the dry particle basis, and / or on the dry fibrous structure and / or dry article basis.
[0286] Other activators Non-limiting examples of other active agents of the present disclosure may be present as or in a coating composition present, in one example, on the exterior surface and / or one or more surfaces of one or more fibrous elements, such as the interior surface of a fibrous structure ply of a multi-ply fibrous structure and / or multi-ply article of the present disclosure, and / or the exterior surface of a fibrous structure ply of a multi-ply fibrous structure and / or multi-ply article of the present disclosure.
[0287] In one embodiment, the article includes a coating composition present on an exterior surface of the article. In another embodiment, the article includes a multi-ply fibrous structure including two or more fibrous structure plies, and the coating composition is present on an interior surface of at least one of the two or more fibrous structure plies. In another embodiment, the article includes a multi-ply fibrous structure including two or more fibrous structure plies, and the coating composition is present on an exterior surface of at least one of the two or more fibrous structure plies.
[0288] Non-limiting examples of such other active agents, which may be water insoluble and / or non-volatile liquid active agents, include silicones such as silicone oils, cationic silicones, silicone rubbers, high refractive index silicones, functionalized silicones, silicone resins, and mixtures thereof, organic oils such as hydrocarbon oils, polyolefins, fatty acid esters, metathesized unsaturated polyol esters, silane modified oils, and mixtures thereof.
[0289] Silicone Activator Non-limiting examples of suitable silicone active agents according to the present disclosure include volatile silicones, non-volatile silicones, and mixtures thereof. In one embodiment, the active agent is a non-volatile silicone active agent. When a volatile silicone active agent is present, it is typically associated with the use as a solvent or carrier for non-volatile silicone active agents in commercial forms, such as silicone gums and / or silicone resins. The silicone active agent may be in the form of particles, may include silicone fluid active agents, and may further include other ingredients, such as silicone resins, to improve the deposition efficiency of silicone fluids and / or to enhance the gloss of treated surfaces, such as hair.
[0290] In one embodiment, the silicone active agent is selected from the group consisting of siloxanes, silicone gums, aminosilicones, amino-terminated silicones, alkylsiloxane polymers, cationic organopolysiloxanes, and mixtures thereof.
[0291] In one embodiment, the concentration of silicone active on and / or in the fibrous elements and / or fibrous structures and / or articles of the present disclosure is from about 0.5% to about 30%, and / or from about 1% to about 24%, and / or from about 2% to about 16%, and / or from about 3% to about 8%. Further non-limiting examples of suitable silicone actives and optional suspending agents for silicone actives are described in U.S. Reissue Patent No. 34,584, U.S. Patent Nos. 5,104,646, and 5,106,609. Silicone actives for use in the compositions of the present disclosure may have a viscosity, when measured at 25° C., of from about 20 to about 2,000,000 centipoise ("cPs"), and / or from about 1,000 to about 1,800,000 cPs, and / or from about 50,000 to about 1,500,000 cPs, and / or from about 100,000 to about 1,500,000 cPs.
[0292] Background material on silicones, including sections discussing silicone fluids, silicone rubbers, and silicone resins, and the manufacture of silicones, is found in Encyclopedia of Polymer Science and Engineering, vol. 15, 2d ed., pp. 204-308, John Wiley & Sons, Inc. (1989).
[0293] Silicone active agents of the present disclosure may include one or more silicones including high molecular weight polyalkyl or polyaryl siloxanes and silicone gums, low molecular weight polydimethylsiloxane fluids, and aminosilicones.
[0294] The high molecular weight polyalkyl or polyaryl siloxanes and silicone gums may exhibit a viscosity at 25° C. of about 100,000 mPa·s to about 30,000,000 mPa·s, and / or about 200,000 mPa·s to about 30,000,000 mPa·s, and / or a molecular weight of about 100,000 to about 1,000,000, and / or about 120,000 to about 1,000,000.
[0295] In one embodiment, higher molecular weight silicone compounds useful herein include polyalkylsiloxanes or polyarylsiloxanes having the following structure:
[0296] [ka] In the formula, R 93 are independently an alkyl group or an aryl group, and p is an integer of about 1,300 to about 15,000, more preferably about 1,600 to about 15,000. 8 are independently an alkyl group or an aryl group, and represent the group that blocks the end of the silicone chain. In one embodiment, the alkyl and / or aryl groups (R 93 ) or alkyl and / or aryl groups Z substituted at the ends of the siloxane chains 8 may have any structure, so long as the resulting silicone remains fluid at 23° C., is dispersible, non-irritating, non-toxic or otherwise harmful, is compatible with the other components of the composition, is chemically stable under normal conditions of use and storage, and is capable of being adhered to the treated hair. 8 Groups include hydroxy, methyl, methoxy, ethoxy, propoxy, and aryloxy. In one embodiment, two R groups on a silicon atom 93 The groups may represent the same or different groups. In one embodiment, two R 93 The groups represent the same group. 93Non-limiting examples of groups include methyl, ethyl, propyl, phenyl, methylphenyl, and phenylmethyl. In one embodiment, such silicone compounds are called polydimethylsiloxane, polydiethylsiloxane, and / or polymethylphenylsiloxane. In one embodiment, silicone compounds are polydimethylsiloxane, also known as dimethicone. Commercially available silicone compounds useful herein include, for example, those available from General Electric Company in the TSF451 series and those available from Dow Corning in the Dow Corning SH200 series.
[0297] Silicone compounds that may be used herein may also include silicone gums. As used herein, the term "silicone gum" refers to polyorganosiloxane materials having a viscosity of 1,000,000 mPa·s or greater at 25°C. It is recognized that the silicone gums described herein may have some overlap with the higher molecular weight silicone compounds disclosed above. This overlap is not intended to be limiting in any of these materials. "Silicone gums" typically have a mass molecular weight greater than about 165,000, generally from about 165,000 to about 1,000,000. Non-limiting examples of such silicone gums include polydimethylsiloxane, poly(dimethylsiloxane methylvinylsiloxane) copolymer, poly(dimethylsiloxane diphenylsiloxane methylvinylsiloxane) copolymer, and mixtures thereof. Commercially available silicone gums useful herein include, for example, TSE200A and CF330M available from General Electric Company.
[0298] In one embodiment, the lower molecular weight silicone has a viscosity at 25° C. of about 1 mPa·s to about 10,000 mPa·s, and / or about 5 mPa·s to about 5,000 mPa·s, and / or a weight average molecular weight of about 400 to about 65,000, and / or about 800 to about 50,000.
[0299] In one embodiment, the lower molecular weight silicone compounds useful herein include polyalkylsiloxanes or polyarylsiloxanes having the following structure:
[0300] [ka] In the formula, R 93 is independently an alkyl group or an aryl group, and p is an integer of about 7 to about 850, more preferably about 7 to about 665. 8 are independently an alkyl group or an aryl group, and represent a group that blocks the end of the silicone chain. The alkyl or aryl group (R 93 ) or an alkyl or aryl group Z substituted at the end of the siloxane chain 8 In one embodiment, R is an alkyl or aryl group substituted on the siloxane chain. 93 ) or an alkyl or aryl group Z substituted at the end of the siloxane chain 8 may have any structure, so long as the resulting silicone remains fluid at 23° C., is dispersible, non-irritating, non-toxic or otherwise harmful, is compatible with the other components of the composition, is chemically stable under normal conditions of use and storage, and is capable of being adhered to the treated hair. 8 Groups include hydroxy, methyl, methoxy, ethoxy, propoxy, and aryloxy. In one embodiment, two R groups on a silicon atom 93 The groups may represent the same or different groups. In one embodiment, two R 93 The groups represent the same group. 93Non-limiting examples of groups include methyl, ethyl, propyl, phenyl, methylphenyl, and phenylmethyl. In one embodiment, such silicone compounds are called polydimethylsiloxane, polydiethylsiloxane, and / or polymethylphenylsiloxane. In one embodiment, silicone compounds are polydimethylsiloxane, also known as dimethicone. Commercially available silicone compounds useful herein include, for example, those available from General Electric Company in the TSF451 series and those available from Dow Corning in the Dow Corning SH200 series.
[0301] In one embodiment, the silicone active agent of the present disclosure comprises one or more aminosilicones.The aminosilicones provided herein are silicones that contain at least one primary amine, secondary amine, tertiary amine, or quaternary ammonium group.In one embodiment, the aminosilicones of the present disclosure can have less than about 0.5% by weight of the aminosilicone, and / or less than about 0.2% by weight, and / or less than about 0.1% by weight of nitrogen.In one embodiment, the aminosilicones of the present disclosure have at least one silicone block with more than 200 siloxane units.
[0302] In one embodiment, the aminosilicones of the present disclosure exhibit a viscosity at 25° C. of from about 1,000 centipoise ("cPs") to about 100,000 cPs, and / or from about 2,000 cPs to about 50,000 cPs, and / or from about 4,000 cPs to about 40,000 cPs, and / or from about 6,000 cPs to about 30,000 cPs.
[0303] In one embodiment, the aminosilicone of the present disclosure is water-soluble. By "water-insoluble aminosilicone" is meant an aminosilicone having a solubility of 10 g / 100 g water or less, and / or 5 g / 100 g water or less, and / or 1 g / 100 g water or less at 25°C. In one embodiment, by "water-insoluble aminosilicone" is meant an aminosilicone that is substantially free of copolyol groups. If copolyol groups are present, they are present at a concentration of less than 10% by weight of the aminosilicone, and / or less than 5% by weight, and / or less than 1% by weight, and / or less than 0.1% by weight.
[0304] In one embodiment, the aminosilicones of the present disclosure, when present, may be present in a concentration of from about 0.5% to about 30% by weight, and / or from about 1.0% to about 24% by weight, and / or from about 2.0% to about 16% by weight, and / or from about 3.0% to about 8% by weight.
[0305] Non-limiting examples of suitable aminosilicones of the present disclosure include aminosilicones according to the general formula (I): (R 1 ) a G 3-a -Si-(-OSiG2) n -(-OSiG b (R 1 ) 2-b ) m -O-SiG 3-a (R 1 ) a (I) (wherein G is hydrogen, phenyl, hydroxy, or C1-C8 alkyl, preferably methyl; a is an integer having a value of 1 to 3, such as 0 or 1; b is 0, 1, or 2, such as 1; a is 0 and b is not 2; n is a number from 0 to 1,999; m is an integer from 0 to 1,999, the sum of n and m is a number from 1 to 2,000, neither a nor m is 0; 1 is the general formula CqH 2q L, where q is an integer having a value of 2 to 8, and L is -N(R 2 )CH2-CH2-N(R2 )2, -N(R 2 )2, -N(R 2 ) + 3A  ̄ , -N(R 2 )CH2-CH2-NR 2 H2A - , wherein R 2 is hydrogen, phenyl, benzyl, or a saturated hydrocarbon radical, for example, from about C to about C 20 where A is a halide ion.
[0306] In one embodiment, the aminosilicone corresponds to formula (I) where m=0, a=1, q=3, G=methyl, n is about 1500 to about 1700, e.g., about 1600, and L is -N(CH3)2 or -NH2, e.g., -NH2. Other aminosilicones can include those corresponding to formula (I) where m=0, a=1, q=3, G=methyl, n is about 400 to about 600, e.g., about 500, and L is -N(CH3)2 or -NH2, e.g., -NH2. These aminosilicones can also be referred to as terminal aminosilicones because one or both ends of the silicone chain are terminated with a nitrogen-containing group.
[0307] A representative aminosilicone corresponding to formula (I) is the polymer known as "trimethylsilylamodimethicone", which is shown below in formula (II):
[0308] [ka] In the formula, n is a number from 1 to 1,999, and m is a number from 1 to 1,999.
[0309] Silicone can also be terminal amino silicone.As defined herein, "terminal amino silicone" refers to a silicone polymer that contains one or more amino groups at one or both ends of the silicone backbone.In one embodiment, the coating composition that includes the active agent of the present disclosure, for example, the active agent of the present disclosure, which can be a hydrophobic coating composition, can be free or substantially free of any silicone compound other than terminal amino silicone.
[0310] In one embodiment, the amino group at at least one end of the silicone backbone of the amino-terminated silicone is selected from the group consisting of primary amines, secondary amines, and tertiary amines. The amino-terminated silicone may conform to Formula III: (R1) a G 3-a -Si-(-OSiG2) n -O-SiG 3-a (R1) a III (wherein G is hydrogen, phenyl, hydroxy, or C1-C8 alkyl, preferably methyl; a is an integer having a value of 1 to 3 or is 1; b is 0, 1, or 2 or is 1; n is a number from 0 to 1,999; and R1 is a group represented by the general formula CqH 2q is a monovalent radical according to the formula: L, where q is an integer having a value of 2 to 8, and L is -N(R2)CH2-CH2-N(R2)2, -N(R2)2, -N(R2)3A - , -N(R2)CH2-CH2-NR2H2A - where R2 is hydrogen, phenyl, benzyl, or a saturated hydrocarbon radical, and A is a halide ion. In one aspect, R2 is an alkyl radical having 1 to 20 carbon atoms, or 2 to 18 carbon atoms, or 4 to 12 carbon atoms.
[0311] In one embodiment, suitable terminal amino silicones correspond to formula III, where a=1, q=3, G=methyl, n is about 1000 to about 2500, and / or about 1500 to about 1700, and L is -N(CH3)2. In another embodiment, suitable terminal amino silicones correspond to formula III, where a=0, G=methyl, n is about 100 to about 1500, and / or about 200 to about 1000, and L is selected from the following groups: -N(R2)CH2-CH2-N(R2)2; -N(R2)2, -N(R2)3A  ̄ ;-N(R2)CH2-CH2-NR2H2A  ̄ , such as -NH2, where R2 is hydrogen, phenyl, benzyl, or a saturated hydrocarbon radical, and A is a halide ion. In one embodiment, R2 is an alkyl radical having 1 to 20 carbon atoms, and / or 2 to 18 carbon atoms, and / or 4 to 12 carbon atoms. In yet another embodiment, the terminal amino silicone is selected from the group consisting of bis-aminomethyl dimethicone, bis-aminoethyl dimethicone, bis-aminopropyl dimethicone, bis-aminobutyl dimethicone, and mixtures thereof.
[0312] Non-limiting examples of suitable amino terminated silicones include aminopropyl terminated polydimethylsiloxane (e.g., having a viscosity of 4,000-6,000 cSt (4-6 Pa·s) and available from Gelest, Inc. under the trade designation DMS-A35), polydimethylsiloxane, trimethylsiloxy terminated (e.g., having a viscosity of 5,000 cSt (5 Pa·s) and available from Gelest, Inc. under the trade designation DMS-T35), polydimethylsiloxane, trimethylsiloxy terminated (e.g., having a viscosity of 1,000 cSt (1 Pa·s) and available from Gelest, Inc. under the trade designation DMS-T31), aminopropyl terminated polydimethylsiloxane, siloxane (e.g., having a viscosity of 900-1,100 cSt (0.9-1.1 Pa·s) and available from Gelest, Inc. under the trade name DMS-A31), polydimethylsiloxane, trimethylsiloxy-terminated (e.g., having a viscosity of 50 cSt (0.05 Pa·s) and available from Gelest, Inc. under the trade name DMS-T15), aminopropyl-terminated polydimethylsiloxane (e.g., having a viscosity of 50-60 cSt (0.05-0.06 Pa·s) and available from Gelest, Inc. under the trade name DMS-A15), bis-aminopropyl dimethicone (e.g., having a viscosity of 10,220 cSt (10.2 Pa·s) and available from Momentive Performance Materials Inc.), and mixtures thereof.
[0313] Non-limiting examples of suitable alkylsiloxane polymers are described in U.S. Patent Application Publication Nos. 2011 / 0243874(A1), 2011 / 0243875(A1), 2011 / 0240065(A1), 2011 / 0243878(A1), 2011 / 0243871(A1), and 2011 / 0243876(A1).
[0314] Non-limiting examples of suitable cationic organopolysiloxanes are described in U.S. Patent Application Publication No. 2014 / 0030206(A1), WO 2014 / 018985(A1), WO 2014 / 018986(A1), WO 2014 / 018987(A1), WO 2014 / 018988(A1), and WO 2014 / 018989(A1).
[0315] organic oil Non-limiting examples of organic oils of the present disclosure include hydrocarbon oils, polyolefins, fatty acid esters, metathesized unsaturated polyol esters, silane-modified oils, and mixtures thereof.
[0316] In one embodiment, the concentration of organic oil active on and / or in the fibrous elements, and / or fibrous structures, and / or articles of the present disclosure may be from about 0.5% to about 20%, and / or from about 0.05% to about 10%, and / or from about 0.05% to about 3%, and / or from about 0.08% to about 1.5%, and / or from about 0.1% to about 1%.
[0317] In one embodiment, the organic oil activator comprises an average carbon chain length of greater than 20, and / or greater than 30, and / or greater than 40.
[0318] Non-limiting examples of hydrocarbon oils include hydrocarbon oils having at least about 10 carbon atoms, such as cyclic hydrocarbons, straight chain aliphatic hydrocarbons (saturated or unsaturated), and branched chain aliphatic hydrocarbons (saturated or unsaturated), including polymers and mixtures thereof. In one embodiment, the hydrocarbon oil is an oil having at least about C 12 ~About C 19 In another embodiment, the hydrocarbon oil is a branched chain oil, such as a hydrocarbon polymer having a carbon chain length of greater than 19 carbon atoms.
[0319] Non-limiting examples of suitable hydrocarbon oils include paraffin oil, mineral oil, saturated and unsaturated dodecane, saturated and unsaturated tridecane, saturated and unsaturated tetradecane, saturated and unsaturated pentadecane, saturated and unsaturated hexadecane, polybutene, polyisobutylene, polydecene, and mixtures thereof. Branched chain isomers of these compounds and long chain hydrocarbons can also be used, including highly branched, saturated or unsaturated alkanes such as permethyl-substituted isomers, for example, permethyl-substituted isomers of hexadecane and eicosane, such as 2,2,4,4,6,6,8,8-dimethyl-10-methylundecane and 2,2,4,4,6,6-dimethyl-8-methylnonane (available from Permethyl Corporation). Hydrocarbon polymers such as polybutene and polydecene are also suitable as organic oil activators. In one embodiment, the hydrocarbon polymer is polybutene, such as a copolymer of isobutylene and butene. A commercially available material of this type is L-14 polybutene manufactured by Amoco Chemical Corporation.
[0320] Non-limiting examples of suitable polyolefins include liquid polyolefins such as liquid poly-alpha olefins, e.g., hydrogenated liquid poly-alpha olefins. In one embodiment, the liquid polyolefins of the present disclosure are from about C4 to about C 14 , and / or about C6 to about C 12 The liquid polyolefins may be prepared by polymerization of olefin monomers such as ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, branched chain isomers such as 4-methyl-1-pentene, and mixtures thereof. Olefin-containing refinery feedstocks and / or effluents are also suitable for preparing liquid polyolefins. In one embodiment, the liquid polyolefin is a liquid poly-alpha olefin, such as 1-hexene to 1-hexadecene, 1-octene to 1-tetradecene, and mixtures thereof.
[0321] Non-limiting examples of suitable fatty acid esters of the present disclosure include fatty acid esters having at least 10 carbon atoms. Non-limiting examples of such fatty acid esters include esters with hydrocarbyl chains derived from fatty acids or alcohols (e.g., monoesters, polyhydric alcohol esters, and di- and tri-carboxylic acid esters). In one embodiment, the hydrocarbyl radical of the fatty acid esters herein may contain or be covalently bonded to other compatible functional groups, such as amide and alkoxy moieties (e.g., ethoxy or ether linkages).
[0322] Non-limiting examples of fatty esters of the present disclosure include isopropyl isostearate, hexyl laurate, isohexyl laurate, isohexyl palmitate, isopropyl palmitate, decyl oleate, isodecyl oleate, hexadecyl stearate, decyl stearate, isopropyl isostearate, dihexyldecyl adipate, lauryl lactate, myristyl lactate, cetyl lactate, oleyl stearate, oleyl oleate, oleyl myristate, lauryl acetate, cetyl propionate, oleyl adipate, and mixtures thereof.
[0323] In one embodiment, the aliphatic esters of the present disclosure are monocarboxylic acid esters of the general formula R'COOR, where R' and R are independently alkyl or alkenyl radicals, and the sum of the carbon atoms in R' and R is at least 10 and / or at least 22.
[0324] In another embodiment, the aliphatic esters of the present disclosure include esters of C4-C8 dicarboxylic acids (e.g., C1-C esters of succinic acid, glutaric acid, and adipic acid). 22and preferably C1-C6 esters).Non-limiting examples of di- and tri-alkyl and alkenyl esters of carboxylic acids include isocetyl stearyol stearate, diisopropyl adipate, dibutyl adipate, tristearyl citrate, and mixtures thereof.
[0325] In yet another embodiment, the fatty ester of the present disclosure includes polyhydric alcohol esters. Non-limiting examples of such polyhydric alcohol esters include alkylene glycol esters such as ethylene glycol mono- and di-fatty acid esters, diethylene glycol mono- and di-fatty acid esters, polyethylene glycol mono- and di-fatty acid esters, propylene glycol mono- and di-fatty acid esters, polypropylene glycol monooleate, polypropylene glycol 2000 monostearate, ethoxylated propylene glycol monostearate, glyceryl mono- and di-fatty acid esters, polyglycerol poly fatty acid esters, ethoxylated glyceryl monostearate, 1,3-butylene glycol monostearate, 1,3-butylene glycol distearate, polyoxyethylene polyol fatty acid esters, sorbitan fatty acid esters, and polyoxyethylene sorbitan fatty acid esters.
[0326] In yet another embodiment, the fatty acid esters of the present disclosure include glycerides, e.g., mono-, di-, and tri-glycerides, e.g., di- and tri-glycerides, such as triglycerides. Non-limiting examples of suitable glycerides include glycerol and C 10 ~C 22These include mono-, di-, and tri-esters with long chain carboxylic acids such as carboxylic acids. A variety of these types of glycerides can be obtained from vegetable and animal fats and oils such as castor oil, safflower oil, cottonseed oil, corn oil, olive oil, cod liver oil, almond oil, avocado oil, palm oil, sesame oil, lanolin, and soybean oil. Synthetic oils include, but are not limited to, triolein and tristearin glyceryl dilaurate.
[0327] In another embodiment, fatty acid esters suitable for the present disclosure may include water-insoluble synthetic fatty acid esters. A non-limiting example of such a synthetic fatty acid ester corresponds to the general formula (IX):
[0328] [ka] (In the formula, R 1 are independently a C7-C9 alkyl, alkenyl, hydroxyalkyl, or hydroxyalkenyl group, such as a saturated alkyl group, e.g., a saturated straight chain alkyl group, n is a positive integer having a value from 2 to 4, such as 3, and Y is an alkyl, alkenyl, hydroxy, or carboxy substituted alkyl or alkenyl having from about 2 to about 20 and / or from about 3 to about 14 carbon atoms. In one embodiment, such synthetic fatty acid esters conform to the general formula (X):
[0329] [ka] (In the formula, R 2 are C8~C independently 10 It is an alkyl, alkenyl, hydroxyalkyl, or hydroxyalkenyl group, such as a saturated alkyl group, for example a saturated straight chain alkyl group, and n and Y are as defined above in formula (XI).
[0330] Non-limiting examples of suitable synthetic aliphatic esters of the present disclosure include P-43 (C8-C 10triester), MCP-684 (tetraester of 3,3 diethanol-1,5 pentanediol), MCP121 (C8-C adipic acid 10 diesters), all of which are commercially available from Mobil Chemical Company.
[0331] Non-limiting examples of metathesized unsaturated polyol esters and their starting materials are described in US Patent Application Publication Nos. 2009 / 0220443 (A1) and 2016 / 0244915 (A1). Metathesized unsaturated polyol ester refers to the product obtained when one or more unsaturated polyol ester components are subjected to a metathesis reaction. Metathesis is a catalytic reaction that involves the exchange of alkylidene units between compounds containing one or more double bonds (i.e., olefinic compounds) through the formation and cleavage of carbon-carbon double bonds. Metathesis can occur between two identical molecules (often referred to as self-metathesis) and / or between two different molecules (often referred to as cross-metathesis).
[0332] Non-limiting examples of suitable silane-modified oils include silane-modified oils having a hydrocarbon chain selected from the group consisting of saturated oils, unsaturated oils, and mixtures thereof, and a hydrolyzable silyl group covalently bonded to the hydrocarbon chain.Non-limiting examples of suitable silane-modified oils are described in US Patent Application Publication No. 2014 / 0335032(A1).
[0333] Active agent release One or more active agents may be released from the fiber elements and / or particles and / or fiber structures when the fiber elements and / or particles and / or fiber structures are exposed to a triggering condition. In one example, one or more active agents may be released from the fiber elements and / or particles and / or fiber structures, or a part thereof, when the fiber elements and / or particles and / or fiber structures, or a part thereof, lose their identity, in other words, lose their physical structure. For example, the fiber elements and / or particles and / or fiber structures lose their physical structure when the filament-forming material melts, dissolves, or undergoes some other transformation process such that the structure is lost. In one example, one or more active agents are released from the fiber elements and / or particles and / or fiber structures when the morphology of the fiber elements and / or particles and / or fiber structures changes.
[0334] In another example, one or more active agents may be released from the fibrous elements and / or particles and / or fibrous structures, or portions thereof, when the identity of the fibrous elements and / or particles and / or fibrous structures, or portions thereof, changes, in other words, when the physical structure of the fibrous elements and / or particles and / or fibrous structures changes, rather than losing, its physical structure. For example, the fibrous elements and / or particles and / or fibrous structures change their physical structure but retain their filament-forming properties when the filament-forming material expands, contracts, stretches and / or shortens.
[0335] In another example, one or more active agents may be released from the fibrous elements and / or particles and / or fibrous structures without changing their morphology (losing or changing their physical structure).
[0336] In one example, the fibrous elements and / or particles and / or fibrous structures may release an active agent when the fibrous elements and / or particles and / or fibrous structures are exposed to triggering conditions that cause the fibrous elements and / or particles and / or fibrous structures to release the active agent, for example by causing the fibrous elements and / or particles and / or fibrous structures to lose or change their identity as described above. Non-limiting examples of triggering conditions include exposing the fibrous elements, particles, and / or fibrous structures to solvents, polar solvents (such as alcohol and / or water), and / or non-polar solvents (which may be done sequentially depending on whether the filament-forming material includes polar solvent-soluble materials and / or non-polar solvent-soluble materials); exposing the fibrous elements, particles, and / or fibrous structures to heat, such as temperatures above 75° F., and / or above 100° F., and / or above 150° F., and / or above 200° F., and / or above 212° F.; exposing the fibrous elements, particles, and / or fibrous structures to cold temperatures, such as temperatures below 40° F., and / or below 32° F., and / or below 0° F.; exposing the fibrous elements, particles, and / or fibrous structures to a force, such as a stretching force applied by a consumer using the fibrous elements, particles, and / or fibrous structures; exposing the fiber elements and / or particles and / or fiber structures to a chemical reaction; exposing the fiber elements and / or particles and / or fiber structures to conditions that cause a phase change; exposing the fiber elements and / or particles and / or fiber structures to a pH change and / or a pressure change and / or a temperature change; exposing the fiber elements and / or particles and / or fiber structures to one or more chemicals that result in the fiber elements and / or particles and / or fiber structures releasing one or more active agents; exposing the fiber elements and / or particles and / or fiber structures to ultrasound; exposing the fiber elements and / or particles and / or fiber structures to light and / or specific wavelengths; exposing the fiber elements and / or particles and / or fiber structures to various ionic strengths; and / or exposing the fiber elements and / or particles and / or fiber structures to an active agent released from another fiber element and / or particle and / or fiber structure.
[0337] In one embodiment, one or more active agents may be released from the fiber elements and / or particles of the present disclosure when a fiber structure product comprising the fiber elements and / or particles is exposed to an inducing process selected from the group consisting of: pretreating a stain on a fabric article with the fiber structure; forming a wash liquor by contacting the fiber structure product with water; spinning the fiber structure product in a dryer; heating the fiber structure product in a dryer; and combinations thereof.
[0338] Filament-forming composition The fiber elements of the present disclosure are manufactured from a filament-forming composition. The filament-forming composition is a polar solvent-based composition. In one embodiment, the filament-forming composition is an aqueous composition comprising one or more filament-forming materials and one or more active agents.
[0339] The filament forming composition of the present disclosure has a shear viscosity of 3,000 s when measured according to the shear viscosity test method described herein. -1 At a shear rate and processing temperature (50°C to 100°C), the shear viscosity may be from about 1 Pascal x sec to about 25 Pascal x sec, and / or from about 2 Pascal x sec to about 20 Pascal x sec, and / or from about 3 Pascal x sec to about 10 Pascal x sec.
[0340] The filament-forming composition may be treated at a temperature of from about 50°C to about 100°C, and / or from about 65°C to about 95°C, and / or from about 70°C to about 90°C when producing fiber elements from the filament-forming composition.
[0341] In one embodiment, the filament-forming composition may comprise at least 20% by weight, and / or at least 30% by weight, and / or at least 40% by weight, and / or at least 45% by weight, and / or at least 50% by weight to about 90% by weight, and / or to about 85% by weight, and / or to about 80% by weight, and / or to about 75% by weight of one or more filament-forming materials, one or more active agents, and mixtures thereof. The filament-forming composition may comprise from about 10% by weight to about 80% by weight of a polar solvent, such as water.
[0342] In one embodiment, the non-volatile components of the filament-forming composition may comprise from about 20% and / or from about 30% and / or from 40% and / or from 45% and / or from 50% to about 75% and / or from 80% and / or from 85% and / or from 90% by weight based on the total weight of the filament-forming composition. The non-volatile components may comprise the filament-forming composition, such as the backbone polymer, the active agent, and combinations thereof. The remaining percentages of the non-volatile components of the filament-forming composition may comprise a range of 10% to 80% by weight based on the total weight of the filament-forming composition.
[0343] In the spinning process of fiber elements, the fiber elements need to have initial stability when they leave the spinning die. The capillary number is used to characterize this initial stability criterion. At the die conditions, the capillary number should be at least 1, and / or at least 3, and / or at least 4, and / or at least 5.
[0344] In one embodiment, the filament-forming composition exhibits a capillary number of at least 1 and up to about 50, and / or at least 3 and up to about 50, and / or at least 5 and up to about 30, such that the filament-forming composition can be effectively polymer-processed into fiber elements.
[0345] As used herein, "polymer processing" refers to any spinning operation and / or spinning process in which fibrous elements comprising processed filament-forming material are formed from a filament-forming composition. The spinning operation and / or process may include spunbond, meltblown, electrospinning, rotary spinning, continuous filament production, and / or tow fiber production operations / processes. As used herein, "processed filament-forming material" refers to any filament-forming material that has been subjected to melt processing operations and subsequent polymer processing operations, resulting in fibrous elements.
[0346] The capillary number is a dimensionless number used to characterize the break-off potential of this droplet. A larger capillary number indicates greater fluid stability upon exiting the die. The capillary number is defined as:
[0347]
number
[0348] The capillary number is defined for the conditions at the exit of the die. The fluid velocity is the average velocity of the fluid passing through the holes in the die. The average velocity is defined as:
[0349]
number
[0350] If the die holes are circular holes, the fluid velocity can be defined as:
[0351]
number
[0352] Fluid viscosity is temperature dependent and can be shear rate dependent. The definition of a shear thinning fluid includes a dependence on shear rate. Surface tension is dependent on the composition of the fluid and the temperature of the fluid.
[0353] In one embodiment, the filament forming composition can include one or more release agents and / or lubricants. Non-limiting examples of suitable release agents and / or lubricants include fatty acids, fatty acid salts, fatty alcohols, fatty esters, sulfonated fatty acid esters, fatty amine acetates, and fatty acid amides, silicones, aminosilicones, fluoropolymers, and mixtures thereof.
[0354] In one example, the filament forming composition may include one or more antiblocking and / or detackifying agents. Non-limiting examples of suitable antiblocking and / or detackifying agents include starch, modified starch, crosslinked polyvinylpyrrolidone, crosslinked cellulose, microcrystalline cellulose, silica, metal oxides, calcium carbonate, talc, and mica.
[0355] The active agents of the present disclosure may be added to the filament forming composition prior to and / or during fiber element formation, and / or may be added to the fiber elements after fiber element formation. For example, a perfume active agent may be applied to the fiber elements and / or fiber structures after forming the fiber elements and / or fiber structures including the fiber elements according to the present disclosure. In another example, an enzyme active agent may be applied to the fiber elements and / or fiber structures after forming the fiber elements and / or fiber structures including the fiber elements according to the present disclosure. In yet another example, one or more particles (which may not be suitable for passing through a spinning process to produce the fiber elements) may be applied to the fiber elements and / or fiber structures after forming the fiber elements and / or fiber structures including the fiber elements according to the present disclosure.
[0356] Elongation aid In one example, the fiber elements include an elongation aid, non-limiting examples of which can include polymers, other elongation aids, and combinations thereof.
[0357] In one example, the elongation aid has a weight average molecular weight of at least about 500,000 Da. In another example, the weight average molecular weight of the elongation aid is about 500,000 to about 25,000,000, in another example, about 800,000 to about 22,000,000, in yet another example, about 1,000,000 to about 20,000,000, and in another example, about 2,000,000 to about 15,000,000. Higher molecular weight elongation aids are preferred in some embodiments due to their ability to increase elongational melt viscosity and reduce melt fracture.
[0358] The elongation aid, when used in a meltblowing process, is added to the composition of the present disclosure in an amount effective to appreciably reduce melt and capillary breakage of the fiber during the spinning process, allowing for the melt spinning of substantially continuous fibers with relatively consistent diameters. Regardless of the process used to manufacture the fiber elements and / or particles, the elongation aid, when used, can be present in one example from about 0.001% to about 10% by weight on a dry fiber element basis and / or dry particle basis and / or dry fiber structure basis, in another example from about 0.005% to about 5% by weight on a dry fiber element basis and / or dry particle basis and / or dry fiber structure basis, in yet another example from about 0.01% to about 1% by weight on a dry fiber element basis and / or dry particle basis and / or dry fiber structure basis, and in another example from about 0.05% to about 0.5% by weight on a dry fiber element basis and / or dry particle basis and / or dry fiber structure basis.
[0359] Non-limiting examples of polymers that can be used as elongation aids include alginates, carrageenans, pectins, chitin, guar gum, xanthan gum, agar, gum arabic, gum karaya, gum tragacanth, locust bean gum, alkyl celluloses, hydroxyalkyl celluloses, carboxyalkyl celluloses, and mixtures thereof.
[0360] Non-limiting examples of other elongation aids include modified and unmodified polyacrylamide, polyacrylic acid, polymethacrylic acid, polyvinyl alcohol, polyvinyl acetate, polyvinylpyrrolidone, polyethylene vinyl acetate, polyethyleneimine, polyamides, polyalkylene oxides (including polyethylene oxide, polypropylene oxide, polyethylene propylene oxide), and mixtures thereof.
[0361] Method for manufacturing a textile element The fiber elements of the present disclosure can be manufactured by any suitable process. Non-limiting examples of suitable processes for making fiber elements are described below.
[0362] As shown in Figures 14 and 15, the fiber element of the present disclosure may be manufactured as follows. The fiber element may be formed by a small-scale apparatus, the schematic diagram of which is shown in Figures 14 and 15. A pressurized tank 39 suitable for batch operation is filled with a suitable filament-forming composition according to the present disclosure. A pump 40, such as the Zenith® PEP II manufactured by the Zenith Pump Division of Parker Hannifin Corporation (Sanford, NC, USA) and having a capacity of 5.0 cubic centimeters per revolution (cc / rev), may be used to facilitate the transport of the filament-forming composition to a spinning die 42 through a pipe 41. The flow rate of the filament-forming composition from the pressurized tank 39 to the spinning die 42 may be controlled by adjusting the revolutions per minute (rpm) of the pump 40. The pipe 41 is used to connect the pressurized tank 39, the pump 40, and the spinning die 42.
[0363] The spinning die 42 shown in FIG. 15 has several rows of circular extrusion nozzles (fiber element forming holes 44) spaced apart from one another by a pitch P of about 0.060 inches. The nozzles have individual inner diameters of about 0.012 inches and individual outer diameters of about 0.032 inches. Each individual nozzle is surrounded by an annular, diverging, flared orifice (concentric attenuation fluid hole 48) for supplying attenuation air to each individual molten capillary 46. The filament-forming composition being extruded through the nozzles is surrounded and attenuated by a generally cylindrical stream of moist air supplied through the orifice.
[0364] In one embodiment, as shown in Figs. 14 and 15, a method 47 for producing a fiber element 10 according to the present disclosure comprises the following steps: a. providing a filament-forming composition comprising one or more filament-forming materials and, optionally, one or more active agents; b. spinning the filament-forming composition, for example via a spinning die 42, into one or more fiber elements, e.g., filaments 10, comprising one or more filament-forming materials and, optionally, one or more active agents. The one or more active agents may be releasable from the fiber elements upon exposure to intended use conditions. The total concentration of the one or more filament-forming materials, e.g., filaments 10, present in the fiber elements, when the active agents are present therein, may be less than 80% by weight, and / or less than 70% by weight, and / or less than 65% by weight, and / or less than 50% by weight, based on the dry fiber element and / or on the dry fiber structure, and the total concentration of the one or more active agents, when present in the fiber elements, may be more than 20% by weight, and / or more than 35% by weight, and / or more than 50% by weight, more than 65% by weight, and / or more than 80% by weight, based on the dry fiber element and / or on the dry fiber structure.
[0365] As shown in FIG. 15 , the spinning die 42 may include a plurality of fiber element forming cavities 44 including dissolved capillaries 46 surrounded by concentric attenuation fluid holes 48 through which a fluid (such as air) passes as it exits the fiber element forming cavities 44 to facilitate attenuation of the filament forming composition into fiber elements, such as fiber elements 10.
[0366] Attenuated air may be provided by heating compressed air from a supply with an electric resistance heater, such as heaters manufactured by Chromalox, a division of Emerson Electric (Pittsburgh, Pa., USA). A suitable amount of flow was added to saturate or nearly saturate the heated air at conditions in the electrically heated, thermostatically controlled delivery pipe. Condensate is removed in an electrically heated, thermostatically controlled separator.
[0367] The embryonic fiber elements are dried by a drying air stream having a temperature of about 149° C. (about 300° F.) to about 315° C. (about 600° F.) provided by electrical resistance heaters (not shown) and delivered through a drying nozzle and emitted at an angle of about 90° relative to the general orientation of the embryonic fiber elements being extruded. The dried embryonic fiber elements are collected on a collection device (e.g., a movable foraminous belt or a patterned collection belt, etc.). A vacuum source may be added beneath the formation zone to aid in fiber collection.
[0368] In one embodiment, any volatile solvent (e.g., water) included in the filament-forming composition is removed, such as by drying, during the spinning process as the fiber elements 10 are formed. In one embodiment, more than 30% by weight, and / or more than 40% by weight, and / or more than 50% by weight of the volatile solvent (e.g., water) of the filament-forming composition is removed during the spinning process, such as by drying the fiber elements being produced.
[0369] The filament-forming composition may comprise any suitable total concentration of filament-forming material and any suitable concentration of active agent, so long as the fiber elements produced from the filament-forming composition comprise a total concentration of filament-forming material in the fiber elements, on a dry fiber element basis, and / or on a dry particle basis, and / or on a dry fiber structure basis, of about 5% to 50% by weight or less, and an active agent in the fiber elements, on a dry fiber element basis, and / or on a dry particle basis, and / or on a dry fiber structure basis, of 50% to about 95% by weight.
[0370] In one embodiment, the filament-forming composition may include any suitable total concentration of filament-forming material and any suitable concentration of active agent, so long as the fiber elements produced from the filament-forming composition include a total concentration of filament-forming composition in the fiber elements and / or particles of about 5% to 50% by weight or less, on a dry fiber element basis, and / or dry particle basis, and / or dry structure basis, and a total concentration of active agent in the fiber elements and / or particles of 50% to about 95% by weight, on a dry fiber element basis, and / or dry particle basis, and / or dry structure basis, and the weight ratio of filament-forming material to total concentration of active agent is 1 or less.
[0371] In one example, the filament-forming composition comprises from about 1% by weight, and / or from about 5% by weight, and / or from about 10% by weight, to about 50% by weight, and / or from about 40% by weight, and / or from about 30% by weight, and / or from about 20% by weight of the filament-forming composition; from about 1% by weight, and / or from about 5% by weight, and / or from about 10% by weight, to about 50% by weight, and / or from about 40% by weight, and / or from about 30% by weight, and / or from about 20% by weight of the filament-forming composition; and from about 20% by weight, and / or from about 25% by weight, and / or from about 30% by weight, and / or from about 40% by weight, and / or from about 80% by weight, and / or from about 70% by weight, and / or from about 60% by weight, and / or from about 50% by weight of the filament-forming composition. The filament-forming composition may contain small amounts of other active agents, for example less than 10% by weight of the filament-forming composition, and / or less than 5% by weight, and / or less than 3% by weight, and / or less than 1% by weight of plasticizers, pH adjusters, and other active agents.
[0372] The filament-forming composition is spun into one or more fiber elements and / or particles by any suitable spinning process, such as meltblowing, spunbonding, electrospinning, and / or rotary spinning. In one embodiment, the filament-forming composition is spun into a plurality of fiber elements and / or particles by meltblowing. For example, the filament-forming composition may be pumped from a tank to a meltblowing spinnerette. Upon exiting one or more filament-forming holes in the spinneret, the filament-forming composition is attenuated by air to form one or more fiber elements and / or particles. The fiber elements and / or particles may then be dried to remove any residual solvent (e.g., water) used for spinning.
[0373] The fibrous elements and / or particles of the present disclosure may be collected on a belt (eg, a patterned belt) to form a fibrous structure comprising the fibrous elements and / or particles.
[0374] Method for producing a fiber structure As shown in Figure 16, a fibrous structure, such as a fibrous structure layer or ply 22 of the present disclosure, may be produced by spinning a filament-forming composition from a spinning die 42, as shown in Figures 14 and 15, to form a plurality of fibrous elements, such as filaments 10, which may then optionally combine with one or more particles 26 provided by a particle source 50, such as a sifter or airlaid forming head. The particles 26 may be dispersed within the fibrous elements, such as filaments 10. The mixture of particles 26 and fibrous elements, such as filaments 10, may be collected on a collection belt 52, such as a patterned collection belt, which imparts a texture, such as a three-dimensional texture, to at least one surface of the fibrous structure layer or ply 22.
[0375] Figure 17 illustrates one embodiment of a method for producing an article 20 according to Figure 5. The method includes forming a first fibrous structure layer 22 of a plurality of fibrous elements, e.g., filaments 10, such that pockets 28 are formed in a surface of the first fibrous structure layer 22. One or more particles 26 are deposited in the pockets 28 from a particle source 50. A second fibrous structure layer 24 comprising a plurality of fibrous elements, e.g., filaments 10 produced from a spinning die 42, is then formed on the surface of the first fibrous structure layer 22 such that the particles 26 are encapsulated in the pockets 28.
[0376] Figure 18 illustrates yet another embodiment of a method for manufacturing the article 20 according to Figure 4. The method includes forming a first fibrous structure layer 22 of a plurality of fibrous elements, e.g., filaments 10. One or more particles 26 are deposited on a surface of the first fibrous structure layer 22 from a particle source 50. A second fibrous structure layer 24 comprising a plurality of fibrous elements, e.g., filaments 10 produced from a spinning die 42, is formed over the particles 26 such that the particles 26 are positioned between the first fibrous structure layer 22 and the second fibrous structure layer 24.
[0377] Dry initial fiber elements, e.g., filaments, may be collected on a molding member as described above. The structure of the molding member provides regions of air permeability depending on the inherent structure. The filaments used to construct the molding member are air permeable, while the void regions between the filaments are air permeable. In addition, a pattern may be applied to the molding member, further providing air permeable regions that may be essentially continuous, discontinuous, or semi-continuous. A vacuum applied in place is used to deflect the fibers into the pattern of the present invention. One example of one of these molding members is shown in FIG. 19.
[0378] In addition to the techniques described herein, other techniques may be applied to form regions in a fibrous structure with different properties (e.g., average density) to achieve suitable results. One example is the embossing technique to form such regions. Suitable embossing techniques are described in U.S. Patent Application Publication Nos. 2010 / 0297377, 2010 / 0295213, 2010 / 0295206, 2010 / 0028621, and 2006 / 0278355.
[0379] In one embodiment, in a multi-ply article, one or more fibrous structure plies may be formed and / or deposited directly onto a pre-existing fibrous structure ply to form a multi-ply fibrous structure. Two or more pre-existing fibrous structure plies may be joined with one or more other pre-existing fibrous structure plies to form a multi-ply article of the present disclosure, for example, by thermal bonding, gluing, embossing, perforating, lodging, rotary knife drilling, die cutting, die punching, needle punching, knurling, pneumatic forming, hydroforming, laser cutting, tufting, and / or other mechanical joining processes.
[0380] Non-limiting examples of fibrous structures (F) Examples 1F, 2F, and 3F - Fibrous structures are prepared according to the present disclosure from the formulas set forth in Table 1 below.
[0381] [Table 2]
[0382] Non-limiting Examples of Articles (A) Example 1A - A roll of the fibrous structure of Example 1F is provided that is 21 inches wide. Three 6 inch by 10 inch sheets can be cut from the web using a rule die cutter 45 and labeled A, B, and C. The rule die cutter can be positioned to set the 6 inch dimension in the cross machine direction. The rule die cutter 45 can be four sharp metal pieces 47 positioned within a Lexan base 49 as shown in FIG. 20, two of the sharp metal pieces are 10 inches long and the other two are 6 inches long.
[0383] Sheet C can be spun fabric side down on the countertop and Sheet B can be spun fabric side down on Sheet C. Sheet A can be spun fabric side up on Sheet B. Optionally, liquid additives such as perfumes, silicones, perfume microcapsule (PMC) solutions, other benefit active solutions, or combinations thereof can be sprayed, coated, or applied to Sheet B. Also, optionally, dry benefit additives or particles such as salts, enzymes, brighteners, other benefit active particles, or combinations thereof can be sprinkled, added, or incorporated into Sheet B.
[0384] The tool 51 used to form the edge seals of the articles may be made of stainless steel. Such a tool 51 is shown, for example, in Figures 21A-21C. Figure 21A shows a top view of the tool 51 used to make five samples. Figure 21B shows a cross-sectional view of the tool enclosed by the letters AA in Figure 21A. Figure 21C shows a cross-sectional detail of the tip of the tool that contacts the web to be sealed. As shown in Figure 22, this tool 51 is bolted to the heated top plate 53 and bottom plate of a typical laboratory mechanical press 55 using a 10 inch air cylinder 57. One example of a mechanical press is manufactured by Machinteck Corporation, 3721 Port Union Rd., Fairfield, Ohio 45014.
[0385] The air pressure can be set at 25-35 psi, the temperature can be set at 145°F, and the dwell time can be set at 5 seconds. The stack of three 6" x 10" sheets can be transferred to a heated mechanical press 55 and placed under a heated top plate 53 having a tool 51 bolted thereto. The press 55 can be actuated to lower the heated top plate 53 onto the 6" x 10" stack of webs to form five sealed samples, still contained within the 6" x 10" stack of webs. Once the first compression cycle is complete, a second compression cycle can be completed with an increased air pressure of 90-100 psi, and the sealed samples can be severed from the remainder of the web. As shown in FIG. 21C, the edge seal width can be determined by the width of the tip of the tool 51 that contacts the web. In such an embodiment, the edge seal width can be half the width of the tool tip. For example, if the tip width is 0.13 inches, the edge seal width will be 0.065 inches.
[0386] Example 2A - A roll of the fibrous structure of Example 3F that is 21 inches wide and a roll of the fibrous structure of Example 2F that is 21 inches wide are provided. A 6"x10" rule die cutter 45 can be used to cut the sheets of web. The rule die cutter can be four sharp metal pieces 47 positioned within a Lexan base 49 as shown in FIG. 20, two of the sharp metal pieces are 10 inches long and the other two are 6 inches long.
[0387] The rule die cutter 45 can be positioned to set the 6 inch dimension in the cross machine direction of the web roll. Three 6 inch by 10 inch sheets can be cut from the web of Example 2F using the rule die cutter 45 and labeled A, B, and C. Two 6 inch by 10 inch sheets can be cut from Example 3F (without particles) using the rule die cutter 45 and labeled D and E. Sheet E can be spun fabric side down on a countertop and Sheet C can be spun fabric side down on Sheet E. Sheet B can be spun fabric side up on Sheet C. Sheet A can be spun fabric side up on Sheet B to coat the perfume and silicone material. Sheet D can be spun fabric side up on Sheet A. Optionally, liquid additives such as perfumes, silicones, perfume microcapsule (PMC) solutions, other benefit active solutions, or combinations thereof may be sprayed, coated, or applied to Sheets A, B, and / or C. Also, optionally, dry benefit additives or particles such as salts, enzymes, brighteners, other benefit active particles, or combinations thereof may be sprinkled on, added to, or incorporated into A, B, and / or C.
[0388] As described in FIG. 1A, the tool 51 used to form the edge seals of the article may be made of stainless steel. Such a tool 51 is shown, for example, in FIGS. 21A-21C. FIG. 21A shows a top view of the tool 51 used to make five samples. FIG. 21B shows a cross-sectional view of the tool enclosed by the letters AA in FIG. 21A. FIG. 21C shows a cross-sectional detail of the tip of the tool that contacts the web to be sealed. As shown in FIG. 22, the tool 51 is bolted to the heated top plate 53 and bottom plate of a typical laboratory mechanical press 55 using a 10 inch air cylinder 57. One example of a mechanical press is manufactured by Machinteck Corporation, 3721 Port Union Rd., Fairfield, Ohio 45014.
[0389] The air pressure can be set at 50 psi, the temperature can be set at 145°F, and the dwell time can be set at 5 seconds. The stack of five 6" x 10" sheets can be transferred to a heated mechanical press 55 and placed under a heated top plate 53 with a bolted tool 51. The press 55 can be actuated to lower the heated top plate 53 onto the 6" x 10" stack of webs to form five sealed samples, which are still contained within the 6" x 10" stack of webs. Once the first compression cycle is complete, a second compression cycle can be completed with an increased air pressure of 90-100 psi, and the sealed samples can be severed from the remainder of the web. As shown in FIG. 21C, the edge seal width can be determined by the width of the tool tip that contacts the web. In such an embodiment, the edge seal width can be half the width of the tool tip. For example, if the tip width is 0.13 inches, the edge seal width will be 0.065 inches.
[0390] Table 2 below shows the respective properties exhibited by the articles of Examples 1A and 2A of the present disclosure. For example, the data shows that the desired edge seal strength and edge seal width performance levels are achieved in the articles of the present disclosure.
[0391] [Table 3]
[0392] Automatic dishwashing machine items An automatic dishwashing article comprises one or more of the fibrous structures and surfactant systems of the present disclosure, and optionally one or more optional ingredients known in the cleaning art (e.g., ingredients useful for cleaning dishes in an automatic dishwashing machine). Examples of these optional ingredients include antiscalants, chelating agents, bleaches, fragrances, dyes, antimicrobials, enzymes (e.g., proteases, amylases), cleaning polymers (e.g., alkoxylated polyethyleneimine polymers), anti-redeposition polymers, hydrotropes, suds suppressors, carboxylic acids, thickeners, preservatives, disinfectants, glass and metal care agents, pH buffering means such that the automatic dishwashing solution has an overall pH of 3 to 14 (alternatively 8 to 11), or mixtures thereof. Examples of automatic dishwasher actives are described in U.S. Patent Nos. 5,679,630, 5,703,034, 5,703,034, 5,705,464, 5,962,386, 5,968,881, 6,017,871, and 6,020,294.
[0393] Scale formation can be a problem. This can result from the precipitation of alkaline earth metal carbonates, phosphates, and silicates. Examples of scale inhibitors include polyacrylates and polymers based on acrylic acid combined with other groups. Sulfonated versions of these polymers are particularly effective in implementing phosphate-free formulations. Examples of scale inhibitors include those described in U.S. Pat. No. 5,783,540 (column 15, line 20 to column 16, line 2) and European Patent No. 0 851 022(A2) (page 12, lines 1-20).
[0394] In one embodiment, an automatic dishwashing article comprising a fibrous structure of the present disclosure may typically contain a dispersion polymer in the range of 0 to about 30% by weight, and / or about 0.5% to about 20% by weight, and / or about 1% to about 10% by weight of the automatic dishwashing article. The dispersion polymer may be an ethoxylated cationic diamine or an ethoxylated cationic polyamine as described in U.S. Pat. No. 4,659,802. Other suitable dispersion polymers include copolymers synthesized from acrylic acid, maleic acid, and methacrylic acid, such as ACUSOL® 480N and ACUSOL 588® supplied by Rohm & Haas, and acrylic-maleic (80 / 20 ratio) phosphono end groups sold under the trade names Acusol 425N® available from Rohm & Haas. Polymers containing both carboxylate and sulfonate monomers, such as ALCOSPERSE® polymers (supplied by Alco), are also acceptable dispersion polymers. In one example, ALCOSPERSE® polymer, sold under the trade name ALCOSPERSE® 725, is a copolymer of styrene and acrylic acid. ALCOSPERSE® 725 may also provide metal corrosion inhibition. Other dispersion polymers are low molecular weight modified polyacrylate copolymers, such as the low molecular weight copolymers of unsaturated aliphatic carboxylic acids disclosed in U.S. Patents 4,530,766, and 5,084,535, and European Patent Application Publication No. 66,915 (published December 15, 1982).
[0395] In one embodiment, an automatic dishwashing article comprising the fibrous structure of the present disclosure may comprise a non-ionic surfactant, a sulfonated polymer, an optional chelating agent, an optional builder, and an optional bleaching agent, and mixtures thereof. A method of washing dishes is provided that comprises dispensing an automatic dishwashing article of the present disclosure into an automatic dishwashing machine.
[0396] Hand washing items The hand dishwashing article comprises one or more fibrous structures of the present disclosure, including a surfactant system and, optionally, one or more optional ingredients known in the cleaning and hand care arts (e.g., useful in hand dishwashing). Examples of these optional ingredients include fragrances, dyes, pearlescent agents, antimicrobial agents, enzymes (e.g., proteases), cleaning polymers (e.g., alkoxylated polyethyleneimine polymers), cationic polymers, hydrotropes, moisturizers, emollients, hand care agents, polymeric foam stabilizers, bleaches, diamines, carboxylic acids, thickeners, preservatives, sanitizing agents, pH buffering means such that the dishwashing liquid has an overall pH of 3-14, and / or 8-11, or mixtures thereof. Examples of hand dishwashing actives are described in U.S. Pat. Nos. 5,990,065 and 6,060,122.
[0397] In one embodiment, the surfactant in the hand dishwashing article is selected from the group consisting of alkyl sulfates, alkoxy sulfates, alkyl sulfonates, alkoxy sulfonates, alkylaryl sulfonates, amine oxides, betaines or derivatives of aliphatic or heterocyclic secondary and tertiary amines, quaternary ammonium surfactants, amines, mono- or polyalkoxylated alcohols, alkyl polyglycosides, fatty acid amide surfactants, C8-C 20 These include ammonia amides, monoethanolamides, diethanolamides, isopropanolamides, polyhydroxy fatty acid amides, or mixtures thereof.
[0398] A method of washing dishes is provided that includes dispensing a hand dishwashing article of the present disclosure into a sink or bowl suitable for containing soiled dishes. The sink or bowl may contain water and / or soiled dishes.
[0399] Hard surface cleaning articles The hard surface cleaning article comprises one or more fibrous structures of the present disclosure that include one or more components known in the cleaning art (e.g., useful for cleaning hard surfaces), such as an acidic component, such as an acidic component that provides good coal dregs removal performance (e.g., formic acid, citric acid, sorbic acid, acetic acid, boric acid, maleic acid, adipic acid, lactic acid, malic acid, malonic acid, glycolic acid, or mixtures thereof). Examples of components that may be included in an acidic hard surface cleaning article include those described in U.S. Pat. No. 7,696,143. Alternatively, the hard surface cleaning article includes an alkaline component (e.g., an alkanolamine, a carbonate, a bicarbonate compound, or mixtures thereof). Examples of components that may be included in an alkaline hard surface cleaning article include those described in U.S. Patent Application Publication No. 2010 / 0206328 A1. A method of cleaning a hard surface includes using or administering a hard surface cleaning article in a method of cleaning a hard surface. In one embodiment, the method includes dispensing the hard surface cleaning article into a bucket or similar container, and optionally adding water to the bucket before or after dispensing the article into the bucket. In another embodiment, the method includes dispensing the hard surface cleaning article into a toilet bowl, and optionally scrubbing a surface of the toilet bowl after dissolving the article in the water in the toilet bowl.
[0400] Toilet flushing head A toilet cleaning head for a toilet cleaning implement is provided that includes one or more fibrous structures of the present disclosure. The toilet cleaning head may be disposable. The toilet cleaning head may be removably attached to a handle, so that the user's hands remain away from the toilet by the handle. In one embodiment, the toilet cleaning head may include a water-dispersible shell. The water-dispersible shell may then include one or more fibrous structures of the present disclosure. The water-dispersible shell may encase a core. The core may include at least one granular material. The granular material of the core may include surfactants, organic acids, fragrances, disinfectants, bleaches, detergents, enzymes, particulates, or mixtures thereof. Optionally, the core may be cellulose-free and may include one or more fibrous structures of the present disclosure. An example of a suitable toilet cleaning head may be manufactured according to U.S. Patent Application No. 12 / 901,804, assigned to the assignee of the present disclosure. Suitable toilet bowl cleaning heads containing a starch material may be manufactured according to commonly assigned U.S. patent application Ser. Nos. 13 / 073,308, 13 / 073,274, and / or 13 / 07,3346. A method of cleaning a toilet bowl surface is provided that includes contacting a toilet bowl cleaning head of the present disclosure with the toilet bowl surface.
[0401] How to use The fibrous structure of the present disclosure, comprising one or more fabric care actives according to the present disclosure, may be utilized in a method for treating a fabric article. The method for treating a fabric article may include one or more steps selected from the group consisting of: (a) pretreating the fabric article before washing the fabric article, (b) contacting the fabric article with a wash liquor formed by contacting the fabric structure with water, (c) contacting the fabric article with the fibrous structure in a dryer, (d) drying the fabric article in the presence of the fibrous structure in a dryer, and (e) combinations thereof.
[0402] In some examples, the method may further include a step of pre-wetting the fibrous structure before contacting the fabric article to be pretreated. For example, the fibrous structure may be pre-wetted with water and then attached to a portion of the fabric containing the stain to be pretreated. Alternatively, the fabric may be wetted and the fibrous structure may be placed on or attached to the fabric. In some examples, the method may further include a step of selecting only a portion of the fibrous structure for use in treating the fabric article. For example, if only one fabric care article is to be treated, a portion of the fibrous structure may be cut and / or torn and placed on or attached to the fabric, or placed in water to form a relatively small amount of wash liquor, which may then be used to pre-treat the fabric. In this manner, the user may customize the fabric treatment method according to the task at hand. In some examples, at least a portion of the fibrous structure may be applied to the fabric to be treated using an apparatus. Exemplary apparatus include, but are not limited to, brushes, sponges, and tapes. In still other examples, the fibrous structure may be applied directly to the surface of the fabric. Any one or more of the above steps may be repeated to achieve the desired fabric treatment effect.
[0403] Test Method Unless otherwise specified, all tests described herein, including those described in the Definitions section, and the following test methods are performed on samples that have been conditioned for a minimum of two hours prior to testing in a room conditioned to a temperature of 23°C ± 1.0°C and a relative humidity of 50 ± 2%. The samples tested are "usable units." As used herein, "usable units" means sheets, flat sections obtained from roll material, pre-converted flat sections, sheets, and / or single-ply or multi-ply products. All tests are performed under the same environmental conditions and in a room so conditioned. Samples with defects such as wrinkles, tears, holes, etc. are not tested. Samples conditioned as described herein are considered to be dry samples (e.g., "dry filament") for testing purposes. All instruments are calibrated according to manufacturer's specifications.
[0404] Basis Weight Test Method The basis weight of the fibrous structures is measured using a top-pan analytical balance with a resolution of ±0.001 g, stacked with 12 usable units. The balance is protected from air currents and other disturbances using a wind shield. A precision die cutter measuring 3.500 in. ±0.0035 in. by 3.500 in. ±0.0035 in. is used to prepare all samples.
[0405] Using a precision cutting die, cut the samples into squares. Stack the cut squares together to a thickness of 12 samples. Measure the mass of the stacked samples and record the result to the nearest 0.001 g.
[0406] Basis weight is: lbs / 3000ft 2 or g / m 2 It is calculated as follows. Basis weight = (mass of stacked samples) / [(area of one square of stacked samples) x (number of squares in stacked samples)] for example, Basis weight (lbs / 3000ft 2 ) = [[mass of stacked samples (g) / 453.6 (g / lbs)] / [12.25 (in 2 ) / 144(in 2 / ft 2 )×12]]×3000 or, Basis weight (g / m 2 ) = mass of stacked samples (g) / [79.032(cm 2 ) / 10,000(cm 2 / m 2 )×12] The result is 0.1lbs / 3000ft 2 or 0.1 g / m 2 The sample size can be altered or varied using a precision cutter similar to that described above to provide at least 100 square inches of sample area within the laminate.
[0407] Moisture content test method The moisture (moisture) content present in the fibrous elements, and / or particles, and / or fibrous structures is measured using the following moisture content test method. The fibrous elements, and / or particles, and / or fibrous structures in the form of pre-cut sheets, or portions thereof ("samples") are placed in a room conditioned to a temperature of 23°C ± 1.0°C and a relative humidity of 50% ± 2% for at least 24 hours prior to testing. Each fibrous structure sample has an area of at least 4 square inches, but is small enough in size to fit adequately on the weighing pan of a balance. Under the above temperature and humidity conditions, using a balance capable of measuring to at least 4 decimal places, the weight of the sample is recorded every 5 minutes until the change from the previous (measured) weight is less than 0.5% in 10 minutes. The final weight is recorded as the "equilibrated weight". Within 10 minutes, the sample is placed on foil in a forced air dryer for drying at a temperature of 70°C ± 2°C and a relative humidity of 4% ± 2% for 24 hours. After drying for 24 hours, the sample is removed and its weight is measured within 15 seconds - this weight is called the "dry weight" of the sample.
[0408] Calculate the moisture (water) content of the sample as follows:
[0409]
number
[0410] Dissolution Test Method Apparatus and materials (see also Figures 23 to 25): 600mL Beaker 54 Magnetic Stirrer 56 (Labline Model No. 1250 or equivalent) Magnetic Stir Bar 58 (5cm) Thermometer (1~100℃+ / -1℃) Punching Die - Stainless steel punching die measuring 3.8cm x 3.2cm Timer (0-3,600 seconds or 1 hour), accurate to the second. The timer used must have a total time measurement range sufficient for samples showing dissolution times greater than 3,600 seconds. However, the timer must be accurate to the second. Polaroid 35 mm Slide 60 (available from Polaroid Corporation, or equivalent) 35mm Slide Holder 62 (or equivalent) Cincinnati city tap water or equivalent having the following characteristics: total hardness = 155 mg / L (as CaCO3); calcium content = 33.2 mg / L; magnesium content = 17.5 mg / L; phosphate content = 0.0462.
[0411] Testing Protocol Equilibrate the sample for at least 2 hours in a constant temperature and humidity environment of 23°C ± 1.0°C and 50% RH ± 2%. Measure the basis weight of the fibrous structure sample to be measured using the basis weight test method defined herein. Cut three dissolution test specimens from the article, e.g., fibrous structure sample, using a die to fit within a 35 mm slide 60 with hole area dimensions of 24 x 36 mm (3.8 cm x 3.2 cm). Fix each specimen to a separate 35 mm slide 60. Place a magnetic stir bar 58 in a 600 mL beaker 54. Turn on tap water (or equivalent) and measure the water temperature with a thermometer, adjusting with hot or cold water as necessary to maintain the test temperature. The test temperature is water at 15°C ± 1°C. Once the test temperature is reached, fill the beaker 54 with 500 mL ± 5 mL of tap water at 15°C ± 1°C. The filled beaker 54 is placed on the magnetic stirrer 56, the stirrer 56 is turned on, and the stirring speed is adjusted until a vortex is created and the bottom of the vortex reaches the 400 mL mark of the beaker 54. The 35 mm slide base 60 is secured to the alligator clamp 64 of the 35 mm slide base holder 62 so that the long end 66 of the slide base 60 is parallel to the water surface. The alligator clamp 64 should be centered on the long end 66 of the slide base 60. The depth adjuster 68 of the holder 62 should be set so that the distance between the bottom of the depth adjuster 68 and the bottom of the alligator clamp 64 is .about.11+ / -0.125 inches. This positioning positions the sample surface perpendicular to the water flow. In one motion, lower the secured slide and clamp into the water and start a timer. The sample is lowered so that it is in the center of the beaker. Disintegration occurs when the nonwoven structure breaks apart. This is recorded as the disintegration time. Once all visible nonwoven structure has been released from the slide platform, the slide is removed from the water while continuing to monitor the solution for undissolved nonwoven structure fragments. Dissolution has occurred when all nonwoven structure fragments are no longer visible in the water. This is recorded as the dissolution time.
[0412] Three replicates of each sample are tested and the average disintegration and dissolution times are recorded. The average disintegration and dissolution times are in seconds.
[0413] The average disintegration time and average dissolution time can be normalized for basis weight by dividing each by the sample basis weight as determined by the Basis Weight Method defined herein. The basis weight normalized disintegration time and dissolution time are expressed in seconds / gsm of sample (s / (g / m 2 ) is a unit of mass.
[0414] Median Particle Size Test Method This test method must be used to determine the average particle size.
[0415] A median particle size test is performed to determine the median particle size of the seed material using ASTM D 502-89, "Standard Test Method for Particle Size of Soaps and Other Detergents," approved May 26, 1989, with further specifications for the size of sieves used in the analysis. According to section 7, "Procedure using machine-sieving method," clean, dry nested sieves are required, including American Standard (ASTM E11) sieves #8 (2360 um), #12 (1700 um), #16 (1180 um), #20 (850 um), #30 (600 um), #40 (425 um), #50 (300 um), #70 (212 um), and #100 (150 um). The nested sieves listed above are used for the prescribed machine-sieving method. The seed material is used as the sample. Suitable sieve shakers can be obtained from WS Thiler Company (Mentor, Ohio, USA).
[0416] The data is plotted on a semi-log plot with the micrometer opening size of each sieve plotted on the log abscissa and the cumulative mass percent (Q3) plotted on the linear ordinate. An example of such data representation is given in Figure A.4 of ISO 9276-1:1998, "Representation of results of particle size analysis - Part 1: Graphical Representation". For purposes of this disclosure, the median particle size (D 50) is defined as the abscissa value at the point where the cumulative mass percent equals 50 percent and is calculated by linear interpolation between the data points just above (a50) and just below (b50) the 50% value using the following equation: D 50 =10^[Log(D a50 )-(Log(D a50 )-Log(D b50 )) * (Q a50 -50%) / (Q a50 -Q b50 )] (In the formula, Q a50 and Q b50 are the cumulative mass percentiles of the data just above and just below the 50th percentile, respectively, and D a50 and D. b50 are the micrometer sieve size values corresponding to these data).
[0417] If the 50th percentile value is smaller than the finest sieve size (150 um) or larger than the coarsest sieve size (2360 um), additional sieves must be added to the nest according to a geometric progression of 1.5 or less until the median falls between the two measured sieve sizes.
[0418] The distribution span of the seed material is a measure of the total width of the seed size distribution about the median (median particle size). It is calculated according to: Span=(D 84 / D 50 +D 50 / D 16 ) / 2 In the formula, D 50 is the median particle size, and D 84 and D. 16 are the particle sizes at the 16th and 84th percentiles, respectively, on the cumulative mass percent plot.
[0419] D 16 If the value is smaller than the finest sieve size (150um), the Span is calculated according to the following: Span=(D 84 / D 50 ).
[0420] D 84 If the value is greater than the coarsest sieve size (2360 um), the Span is calculated according to the following: Span=(D 50 / D 16 ).
[0421] D 16 The value is smaller than the finest sieve size (150um) and D 84 If the value is greater than the coarsest sieve size (2360 um), the distribution span is set to a maximum value of 5.7.
[0422] Diameter Test Method The diameter of individual fiber elements or fiber elements in a fiber structure is determined using a scanning electron microscope (SEM) or optical microscope and image analysis software. A magnification between 200 and 10,000 times is selected to appropriately magnify the fiber elements for measurement. If an SEM is used, the sample is sputtered with gold or palladium compounds to avoid charging and vibration of the fiber elements in the electron beam. A manual procedure is used to measure the diameter of the fiber elements from the image (on the monitor screen) obtained with the SEM or optical microscope. The mouse and cursor tool are used to locate the edge of a randomly selected fiber element and then measure across its width (i.e. perpendicular to the direction of the fiber element at that point) to the other edge of the fiber element. A calibrated image analysis tool with a scale provides a scale to obtain an actual reading in μm. For fiber elements in a fiber structure, several fiber elements are randomly selected from the entire fiber structure sample using the SEM or optical microscope. At least two portions of the fiber structure are cut and tested in this manner. For statistical analysis, a total of at least 100 such measurements are performed and all data is then recorded. The recorded data is used to calculate the mean (average) fiber element diameter, the standard deviation of the fiber element diameter, and the median fiber element diameter.
[0423] Another useful statistic is to calculate the amount of fiber element population that is below a particular upper limit. To determine this statistic, the software is programmed to count how many of the fiber element diameter results are below the upper limit, and this count (divided by the total number of data and multiplied by 100%) is recorded as a percentage that is below the upper limit (e.g., percent that are below 1 micrometer in diameter, or percent that are submicron). We refer to the measured diameter (in μm) of an individual circular fiber element as di.
[0424] In cases where the fiber elements have a non-circular cross section, the diameter measurement of the fiber elements is determined as and equal to the hydraulic diameter, which is the cross-sectional area of the fiber element multiplied by four divided by the perimeter of the cross section of the fiber element (the outer perimeter in the case of hollow fiber elements). The number-average diameter, or mean diameter, is calculated as follows:
[0425]
number
[0426] Tensile Testing: Elongation, Tensile Strength, TEA, and Modulus Elongation, tensile strength, TEA, and tangent modulus are measured at a constant rate on a computer-interfaced extension tensile tester (a suitable instrument is an EJA Vantage from Thwing-Albert Instrument Co., Wet Berlin, NJ, USA) using a load cell where the force measured is within 10%-90% of the cell limits. Both the movable (upper) and fixed (lower) pneumatic jaws are fitted with smooth stainless steel lined jaws 25.4 mm high and wider than the width of the test specimen. Air pressure of approximately 60 psi is supplied to the jaws.
[0427] The eight usable units of the fibrous structure are divided into two stacks of four samples each. Each stack is ensured to be oriented in the machine direction (MD) and cross direction (CD). One stack is for testing in the MD and the other for testing in the CD. Using a 1 inch precision cutter (Thwing Albert JDC-1-10 or similar), cut four MD strips from one laminate and four CD strips (1.00 inch ± 0.01 inch wide x 3.0-4.0 inch long) from the other laminate. Each strip of one usable unit thickness is treated as a single specimen for testing.
[0428] The tensile tester is programmed to ramp the crosshead to a speed of 2.00 in / min (5.08 cm / min) and perform the extension test while collecting force and extension data at an acquisition rate of 20 Hz until the specimen breaks. The break sensitivity is set to 80%, i.e., the test ends when the measured force drops to 20% of the maximum peak force, after which the crosshead returns to the starting position.
[0429] Set the gage length to 1.00 inch. Zero the crosshead and load cell. Insert the single specimen into the upper jaw, align it vertically in the upper and lower jaws, and close the upper jaw. Insert the single specimen into the lower jaw and close. The single specimen should be under a tensile force sufficient to remove any slack, but less than 5.0 g of force on the load cell. Start the tensile tester and begin data collection. Repeat the test for all four CD and four MD single specimens in the same manner. Program the software to calculate the following from the constructed force (g) vs. extension (in) curve:
[0430] Tensile strength is determined by dividing the maximum peak force (g) by the sample width (in) and is reported in g / in with units of 1 g / in.
[0431] The adjusted gauge length is calculated as the extension (in) measured when a force of 3.0 g is applied to the original gauge length (in).
[0432] Elongation was calculated by dividing the elongation at maximum peak force (in) by the adjusted gauge length (in) multiplied by 100 and is reported as a % to the nearest 0.1%.
[0433] Total energy (TEA) is the area (g) under the force curve integrated from zero extension to the extension at the maximum peak force. * Calculate the gage length (in) divided by the product of the adjusted gage length (in) and the width of the test piece (in), and * in / in 2 Report in units.
[0434] The force (g) vs. extension curve (in) is replotted as a force (g) vs. strain curve, where strain is defined as the extension (in) divided by the adjusted gauge length (in).
[0435] Program the software to calculate the following from the constructed force (g) versus strain curve: The tangent modulus was calculated as the slope of a linear line drawn between two data points on the force (g) versus strain curve, where one data point is the first data point recorded after a force of 28 g and the other data point is the first data point recorded after a force of 48 g. This slope was then divided by the specimen width (2.54 cm) and reported in g / cm.
[0436] Tensile strength (g / in), elongation (%), total energy (g * in / in 2 ), and tangent modulus (g / cm) are calculated for the four CD and four MD single specimens. The average of each parameter is calculated separately for the CD and MD specimens.
[0437] Calculation: Geometric mean tensile strength = square root of [MD tensile strength (g / in) × CD tensile strength (g / in)] Geometric mean peak elongation = square root of [MD elongation (%) x CD elongation (%)] Geometric mean TEA=[MD TEA(g * in / in2 )×CD TEA(g / in 2 )] square root Geometric mean elastic modulus = square root of [MD elastic modulus (g / cm) × CD elastic modulus (g / cm)] Total dry tensile strength (TDT) = MD tensile strength (g / in) + CD tensile strength (g / in) Total TEA = MD TEA (g * in / in 2 )+CD TEA(g * in / in 2 ) Total modulus = MD modulus (g / cm) + CD modulus (g / cm) Tensile ratio = MD tensile strength (g / in) / CD tensile strength (g / in)
[0438] Thickness Test Method The thickness of the fibrous structure and / or the height of the article were measured using a ProGage Thickness Tester (Thwing-Albert Instrument Company, West Berlin, NJ) with a circular pressure foot diameter of 2.00 inches (3.14 inches). 2 area), 15.5g / cm 2 Five samples are cut of the fibrous structure sample such that each cut sample is a size larger than the pressure foot face and prepared to be free of wrinkles, folds, and obvious defects. If the article has a length or width smaller than the diameter of the pressure foot, a smaller diameter pressure foot may be used, while a pressure of 15.5 g / cm 2 Make appropriate adjustments so that a pressure of 15.5 g / cm at 0.03 in / sec is still being applied. Individual specimens are placed on the anvil to center the specimen under the pressure foot or at the center of the article's maximum height. 2 The pressure foot is lowered until a pressure of 1.0 mm is applied. A reading is taken after a dwell time of 3 seconds and the pressure foot is raised. The measurement is repeated in the same manner for the remaining four samples. The thickness or article height is calculated as the average thickness of the five samples and reported to the nearest 0.01 mm.
[0439] Shear Viscosity Test Method The shear viscosity of the filament-forming compositions of the present disclosure is measured using a capillary rheometer, a Goettfert Rheograph 6000 manufactured by Goettfert USA (Rock Hill SC, USA). Measurements are performed using a capillary die having a diameter D of 1.0 mm and a length L of 30 mm (i.e., L / D=30). The die is attached to the lower end of the 20 mm barrel of the rheometer and held at a die test temperature of 75° C. A 60 g sample of the filament-forming composition, preheated to the die test temperature, is loaded into the barrel region of the rheometer. Any trapped air is removed from the sample. A series of selected speeds from 1,000 to 10,000 seconds is run. -1 The sample is extruded from the barrel through the capillary die at . The apparent shear viscosity can be calculated using the rheometer software from the pressure drop across the sample as it travels from the barrel through the capillary die and the flow rate of the sample through the capillary die. Log(apparent shear viscosity) can be plotted against log(shear rate) and this plot can be expressed by the equation η=Kγ n-1 where K is the viscosity constant of the material, n is the thinning exponent of the material, and γ is the shear rate. The reported apparent shear viscosities of the filament-forming compositions herein can be fitted with a power law relationship according to the following equation: -1 It is calculated from the interpolation to
[0440] Weight average molecular weight The weight average molecular weight (Mw) of a material (e.g., a polymer) is determined by gel permeation chromatography (GPC) using a mixed bed column. A high performance liquid chromatograph (HPLC) with the following components is used: Millenium®, Model 600E pump, system controller and controller software version 3.2, Model 717 Plus autosampler, and CHM-009246 column heater (all from Waters Corporation, Milford, MA, USA). The column is a PL gel 20 μm mixed A column (gel molecular weight: 1,000 g / mol to 40,000,000 g / mol) with a length of 600 mm and an internal diameter of 7.5 mm, and the guard column is a PL gel 20 μm with a length of 50 mm and an ID of 7.5 mm. The column temperature is 55° C. and the injection volume is 200 μL. The detector is a DAWN® Enhanced Optical System (EOS) equipped with Astra® software, version 4.73.04 detector software, a laser light scattering detector with a K5 cell and a 690 nm laser from Wyatt Technology (Santa Barbara, CA, USA). The gain of the odd-numbered detector is set to 101. The gain of the even-numbered detector is set to 20.9. The Wyatt Technology Optilab® differential refractometer is set to 50° C. The gain is set to 10. The mobile phase is HPLC grade dimethyl sulfoxide with 0.1% w / v LiBr, and the mobile phase flow rate is 1 mL / min isocratic. The run time is 30 minutes.
[0441] Samples are prepared by dissolving material in mobile phase at nominally 3 mg of material per mL of mobile phase. The samples are capped and then stirred using a magnetic stirrer for approximately 5 minutes. The samples are then placed in a convection oven at 85° C. for 60 minutes. The samples are then allowed to cool to room temperature. The samples are then filtered through a 5 μm nylon membrane (Type: Spartan-25, Schleicher & Schuell, Keene, NH, USA) via a 5 mL syringe into a 5 milliliter (mL) autosampler vial.
[0442] For each series of measurement samples (three or more samples of material), the solvent of the blank sample is injected into the column. A check sample is then prepared in the same manner as for the above samples. The check sample contains 2 mg / mL pullulan (Polymer Laboratories) with a weight average molecular weight of 47,300 g / mol. The check sample is analyzed before each sample set is analyzed. The blank sample, check sample, and material test sample are tested in duplicate. The blank sample is used for the final measurement. The light scattering detector and differential refractometer are used according to the "Dawn EOS Light Scattering Instrument Hardware Manual" and the "Optilab® DSP Interferometric Refractometer Hardware Manual" (both produced by Wyatt Technology Corp., Santa Barbara, CA, USA, both of which are incorporated herein by reference).
[0443] The detector software is used to calculate the weight average molecular weight of the sample. A dn / dc (differential change in refractive index with concentration) value of 0.066 is used. The baselines of the laser light detector and the refractive index detector are corrected to remove detector dark current and solvent scattering interference. If the laser light detector signal is saturated or exhibits excessive noise, its value is not used in the molecular mass calculation. The region for molecular weight characterization is selected such that the 90° detector signals for laser light scattering and refractive index are both greater than three times their respective baseline noise levels. Typically, the high molecular weight side of the chromatogram is limited by the refractive index signal and the low molecular weight side is limited by the laser light signal.
[0444] The weight average molecular weight can be calculated using the "first order Zimm plot" defined in the detector software. If the weight average molecular weight of the sample is greater than 1,000,000 g / mol, both the first order and second order Zimm plots are calculated and the result with the least error of the regression fit is used to calculate the molecular mass. The weight average molecular weight reported is the average of two runs of the material test sample.
[0445] Fiber Element Composition Test Method To prepare the fiber elements for fiber element composition measurement, the fiber elements are conditioned by removing any removable coating compositions and / or materials present on the exterior surface of the fiber element. An example of how to do this is to wash the fiber element three times with a suitable solvent that removes the exterior coating without altering the fiber element. The fiber element is then air dried at a temperature of 23° C.±1.0° C. until the fiber element has less than 10% moisture. Chemical analysis of the conditioned fiber element is then completed to determine the composition of the fiber element's composition with respect to filament forming materials and active agents present within the fiber element.
[0446] The composition of the fiber element forming materials and active agents may also be determined by completing a cross-sectional analysis using TOF-SIMS or SEM. Yet another method for determining the composition of the fiber elements is to use fluorescent dyes as markers. Furthermore, as always, fiber element manufacturers must know the composition of their fiber elements.
[0447] Modified circular bend test method The modified circular bend of the fiber construct sample to be tested is measured with a constant rate of extension tensile tester (a suitable instrument is MTS Alliance using Testworks 4.0 Software, available from MTS Systems Corp., Eden Prairie, Minn.) using a load cell that measures forces within 10% to 90% of the cell limits. All testing is performed in a room controlled at 23° C.±3° C. and 50%±2% relative humidity.
[0448] As shown in Figures 26A and 26B, the lower fixture 92 consists of a smooth polished stainless steel horizontal platform 94 measuring 102.0 mm wide by 102.0 mm long by 6.35 mm thick. The platform 94 has an 18.75 mm diameter orifice 96 at its center, the overlapping edges 98 of which are angled at 45 degrees to a depth of 4.75 mm (i.e., the outer diameter of the bevel is 28.25 mm). The lower fixture 92 is constructed to have at least 20 mm of clearance below the platform 94. The platform 94 has an adapter 100 that fits into the tensile tester, which can hold the platform 94 horizontally and perpendicular to the pulling direction of the tensile tester. The upper fixture 102 consists of a cylindrical plunger 104 with an overall length of 70 mm and a diameter of 6.25 mm. The plunger 104 has a contact tip 106 that is a ball nose with a radius of 2.97 mm. The plun...
Claims
1. An article, one or more fiber elements, at least one of said fiber elements comprising one or more filament-forming materials and one or more active agents releasable from said fiber element; an edge seal generally positioned along at least a portion of a periphery of the article; The article exhibits an edge seal strength of 0.1 N / in to 4 N / in when measured according to the Edge Seal Strength Test Method.
2. The article of claim 1 , wherein the edge seal comprises one or more particles.
3. 3. The article of claim 1 or 2, wherein the article exhibits an average disintegration time of less than 360 seconds when measured according to the dissolution test method described herein.
4. The article of any one of claims 1 to 3, wherein the article exhibits an average dissolution time of less than 3600 seconds when measured according to the dissolution test method described herein.
5. The article according to any one of claims 1 to 4, wherein the article comprises two or more textile structure plies in the form of a multi-ply article, preferably the article comprises a first outermost ply and a second outermost ply, and respective ends of the first outermost ply and the second outermost ply form the edge seal, more preferably the article comprises one or more inner plies, the one or more inner plies being surrounded by the first outermost ply and the second outermost ply, and the one or more inner plies do not form the edge seal.
6. 6. The article of claim 5, wherein at least one of the two or more fibrous structure plies comprises one or more particles, preferably the article comprises a first outermost ply and a second outermost ply, and the edge seal is formed along an edge of each of the first outermost ply and the second outermost ply, more preferably the article comprises one or more inner plies, the one or more inner plies being surrounded by the first outermost ply and the second outermost ply, the one or more inner plies comprising the one or more particles, more preferably the first outermost ply and the second outermost ply are substantially free of particles, and even more preferably the one or more inner plies do not form the edge seal.
7. The article comprises: Width: 1cm to 11cm Length: 1cm to 20cm Height of 0.01mm to 50mm, a mass between 0.25 g and 50 g; A volume between 0.25cc and 60cc, and The article of any one of claims 1 to 6, having one or more of the following: a density of 0.05 g / cc to 0.8 g / cc.
8. 8. The article of any one of claims 1 to 7, wherein said one or more active agents comprise one or more foaming agents, preferably said one or more foaming agents constitute 0.1% to 50% by weight based on the dry fiber component, preferably said one or more foaming agents are selected from the group consisting of tartaric acid, citric acid, fumaric acid, adipic acid, malic acid, oxalic acid, or sulfamic acid, preferably said one or more foaming agents are selected from the group consisting of sodium carbonate, calcium carbonate, magnesium carbonate, ammonium carbonate, potassium carbonate, sodium bicarbonate, calcium bicarbonate.
9. 9. The article of any one of claims 1 to 8, further comprising one or more particles, the one or more particles being active agent-containing particles, the one or more active agents and the active agent-containing particles each comprising a surfactant, and the surfactant in the particles and the surfactant in the fiber elements are different from each other.
10. The article of any one of claims 1 to 9, wherein the edge seal is continuous.
11. The article of any one of claims 1 to 9, wherein the edge seal is discontinuous.
12. A product transport assembly comprising one or more of the articles of any one of claims 1 to 11.
Citation Information
Patent Citations
Bag made of water-soluble sheet
JP1992053900A
Film active substance carrier
JP2002523359A
Fibers containing starch and biodegradable polymers
JP2004533551A
Cosmetic or dermatological article containing water-soluble medium
JP2006206586A
Polymer fiber structure and method for producing the same, and composite fiber structure
JP2014152424A